Primary biliary cirrhosis and rheumatoid arthritis: a comprehensive study combining genetics and transcriptomics - Mingyi Yang; Honghao Ren; Xiaodong Ren; Pengfei Wen; Jiale Xie; Xianjie Wan; Ke Xu; Lin Liu; Weikun Hou; Zhi Yang; Peng Xu (Mammalian Genome, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Development of an isoform-discriminating RT-qPCR assay for transcript-level profiling of human ASAH2 in colorectal cancer cell models - You Shan Ngui; Yi-Wen Huang; Shao-Chi Hung; Shih-Han Huang; Chieh-Ju Wen; Yi-An Chang; Hsing-Chen Wu; Hsiu-Chuan Chan; Mei-Lin Chan; Liang-Yin Ke; Hua-Chen Chan (Molecular Biology Reports, 2026)

Ecological regime shifts decouple organic carbon sequestration from nutrient-driven productivity in Anthropocene shallow lakes - Shixin Huang; Ke Zhang; Wenwei Zhao; Qi Lin; David Taylor; Ji Shen (Global and Planetary Change, 2026)

Associations of low-level multi-metal exposure with peripheral blood-based inflammatory indices and the mediating role of gut microbiota: evidence from lifestyle-standardized men - Yao Wang; Tao Lin; Xudong Zhang; Ke Li; Zixin Guo; Erxian Li; Xinwei Wu; Yongxian Li; Degang Wu; Qifei Deng; Peng He (Environmental Research, 2026)

Seasonal–diurnal nonlinear and interactive associations between built–natural–topographic indicators and land surface temperature in a coastal urban agglomeration - Aifang Weng; Baoyin Li; Yuying Lin; Linsheng Wen; Sunbowen Zhang; Chuanmao Hua; Chengshu Ke; Yilin Zou (Energy and Buildings, 2026)

A novel efficient numerical method for 3D bi-anisotropic photonic crystal simulation - Ke Gui; Tiexiang Li; Wen-Wei Lin; Xing-Long Lyu (Computer Physics Communications, 2026)

Generation, characteristics, and resource recovery of copper smelting solid wastes: A review - Yun Li; Yiwei Deng; Xiaobo Min; Lin Tian; Changhao He; Yunyan Wang; Yong Ke; Cong Peng; Min Chen (Chemical Engineering Journal, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

Differential migration, partitioning behavior, and ecological risks of corticosteroids versus phenolic estrogens in coastal riverine tidal flats and bed sediments - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang; Wei Tao; Qi-Hang Wu; Shen-Ao Liu; Dong-Hao Luo; et al. (Marine Pollution Bulletin, 2026)

Microplastics from catchment to offshore: Salinity gradients and seasonal discharge control estuarine trapping efficiency and tidal reimport - Kazi Belayet Hossain; Junge Wang; Yang Zhou; Xiangrong Xu; Lang Lin; Xiaoshan Zhu; Yang Liu; Bin Chen; Hongwei Ke; Minggang Cai (Water Research, 2026)

Targeted discovery of linear lipopeptides from the marine-derived fungus Myrothecium inundatum by a building blocks-based molecular networking strategy - Bin Hu; Jinghao Hu; Eunyoung Seo; Yingjie Sun; Bin Wang; Ke Ma; Wenhan Lin (Phytochemistry Letters, 2026)

Dynamics of coral rubble on reef flats: from individual clast mobilisation to rubble strip morphological change - Aitana Gea-Neuhaus; Tim Scott; Gerd Masselink; Ana Vila-Concejo; Paul S. Kench; Mathilde Lindhart; Floortje E. Roelvink; Tom Hamilton; Ke Lin; Xianfeng Wang (Marine Geology, 2026)

Connectivity and function determine whether ponds act as sources or sinks of nonpoint-source phosphorus - Xiaofen Bai; Chen Lin; Ke Song; Wenlan Feng; Junfeng Xiong; Siyu Ge; Wanqian Yu; Jianchun Chen; Yijun Tong (Journal of Hydrology, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Cu-based MOFs@TiO2/PVDF composite membrane for efficient oil-water separation and bacterial isolation and sterilization - Lin-Lin Liu; Xue-Ling Zeng; Xuan Shi; Yu-Zhuo Fan; Wen-Yan Zeng; Ze-Hui Bai; Rong-Ke You; Xue-Qin Zhan; Fang-Chang Tsai; Ning Ma (Journal of Environmental Chemical Engineering, 2026)

Elemental sulfur-enhanced hydrothermal stabilization of arsenic in arsenic sulfide sludges: Mechanism of sulfur-induced structure transformation and practical application - Hui Xu; Wanlan Wu; Qiujing Xu; Yong Ke; Yun Li; Cong Peng; Lin Yu; Zhumei Sun; Yunyan Wang; Xiaobo Min (Journal of Environmental Chemical Engineering, 2026)

Enhanced aluminum removal via K+–NH4+ composite alum precipitation from beryllium leachates: Mechanism validation and application - Lin Yu; Xiaobo Min; Yunyan Wang; Yulin Zhou; Zhou Liao; Yun Li; Cong Peng; Hui Xu; Zhiyan Zeng; Yong Ke (Hydrometallurgy, 2026)

Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

Safety evaluation and probiotic properties of Bacillus velezensis YK-19 capable of degrading deoxynivalenol: In vitro characterization and in vivo safety assessment in mice - Yukai Lin; Jingjing Zhao; Bo Wen; Songbiao Chen; Lei Wang; Xiaojing Xia; Yanzhao Xu; Yanyan Jia; Rongxian Guo; Ke Shang; Zuhua Yu; Chengshui Liao; et al. (Food Bioscience, 2026)

Algal-bacterial biofilm reactors for petrochemical wastewater: Matrix-dependent DOM transformation and stage-specific applicability - Yueying Liu; Yuan Lin; Sijia Ma; Juntao Shu; Hongqiang Ren; Ke Xu (Environmental Research, 2026)

Linking emission sources to secondary carbon monoxide formation: A chemical reaction chain sensitivity-based analysis - Kai Xie; Yulong Yan; Xiaolin Duan; Shijie Yang; Ke Yue; Jiaqi Dong; Dongmei Hu; Lin Peng (Environmental Pollution, 2026)

Compression and shear stability capacity design for a composite wall combining concrete-filled steel tubes and corrugated steel plates - Xiang-Yu Zhao; Yan-Lin Guo; Ke Wang; Jin-Song Duan; Wen-Ke Zheng (Engineering Structures, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Decoupling the synergy of dipole moment and planarity in donor–acceptor conjugated polymers via bridge atom engineering for photocatalytic H₂ evolution - Ke Wang; Lin Wang; Di Wang; Zhaohang Ben; Yucheng Liu; Bo Cheng; Zongzhao Liu; Qiang Zhang; Yan Lu (Chemical Engineering Journal, 2026)

Mechanochemical engineering of interfacial M-Ov-Ni sites in CeZrO/Ni catalysts for reinforced low-temperature CO2 methanation - Xiaopo Niu; Yeben Liu; Yining Xia; Xinyu Hu; Zhengguo Wang; Chuqiao Song; Quanli Ke; Xiaoli Wei; Guokai Cui; Qingfa Wang; Lili Lin; Hanfeng Lu (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

Development of magnetic solid-phase extraction with magnetic graphene oxide composite nanospheres for sensitive determination of perfluoroalkyl substances in tea beverages - Xin-Li Song; Tong Sun; Ke-Chao Liao; Hui Lv; Pin-Pin Wang; Dong-Dong Wang; Yan Lu; Lin Li (Analytica Chimica Acta, 2026)

Pyridyl ethyl diazoacetate derivatization enables LC-MS annotation of cholesterol and its metabolites - Wenhao Ke; Yikang Wang; Yang Chen; Hanchu Ye; Wen-Di Duan; Feifei Lin; Yingying Wang; Zhengjun Zhou; Zhiyong Yu; Youhong Hu; Jia Liu (Analytica Chimica Acta, 2026)

Overexpression of DR1372 gene from Deinococcus radiodurans improves the salt and drought tolerance in soybean - Lili Zhou; Ke Zang; Xinyan Liu; Peilin Wang; Wenfang Guo; Xiaofeng Su; Mahideen Afridi; Jin Wang; Min Lin; Hongmei Cheng; Huiming Guo (Plant and Soil, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Assessing global flood-induced occurrence and transmission risks of biological contaminants - Ke Shi; Qian-Hang Huang; Yu-Xin Lin; Bin-Yuan Gao; Yu-Qi Wang; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2026)

Modal transition and fluid–structure energy transfer mechanisms in vortex-induced vibration of a full-scale hang-off riser during typhoon evacuation towing - Yuankun Sun; Shuqing Wang; Xiuquan Liu; Jiasong Wang; Zhiyuan Zhou; Ke Lin (Ocean Engineering, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Deciphering the effects of sulfonamide antibiotics on denitrification from a metagenomic perspective: inhibition of nitrite reduction and succession patterns of functional microorganisms - Qinmao Zhou; Yuyang Wang; Hebin Liang; Jin Huang; Jiayu Zhang; Ke Yu; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2026)

Unraveling the structure–performance relationship of Co–Co/Co–N dual active sites in ZIF-8 derived nitrogen–doped carbon catalysts for efficient N2O decomposition - Ke Zheng; Ruirui Wang; Longqing Wang; Ruifang Wu; Xiangqian Lin; Xiaoting Du; Liangliang Zhang; Chengming Zhang; Yongzhao Wang (Journal of Hazardous Materials, 2026)

Integrative transcriptomic and functional analysis reveals fatty acyl elongases involved in sex pheromone biosynthesis in rice leaffolder, Cnaphalocrocis medinalis (Lepidoptera: Pyraloidea) - Ling-Yue Chen; Xiao-Yang Lin; Ke-Xin Wang; Xiao Feng; Hong-Ting Tang; Shuang-Lin Dong; Ling-Ling Zheng; Yi-Han Xia (Insect Biochemistry and Molecular Biology, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Eccentric compressive performance of CFST columns reinforced with annular stiffeners - Ke-Rong Luo; Bing-Lin Lai; Liang Yu; Bu-Hui Li; Gan-Ping Shu (Engineering Structures, 2026)

Evolution of multiscale pore structure in saturated silty clay under non-coaxial F-T cycles - Chuang Lin; Jiahao Zhang; Han Zhao; Ke Yin; Feng Zhang; Decheng Feng (Engineering Geology, 2026)

Settlements sculpted by water: Revealing the shaping power of water networks on urban morphology in China - Lin Fang; Ke Song; Qiong Liu; Minghao Ou (Environmental Impact Assessment Review, 2026)

A Pt/h-Co-Nc nanozyme hydrogel air-fuel cell mediating cascade DNA walking for point-of-care detection - Ning Li; Lin Sun; Kaili Wang; Lihui Mao; Xuecai Tan; Haibo Wang; Ke-Jing Huang; Shaogang Liu (Chemical Engineering Journal, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Self-powered trickling-filter bioelectro-Fenton removal of gaseous isopropanol using sulfur-modified Fe-biochar fillers and a melanin-modified cathode - Chi-Wen Lin; Yu-Sheng Yang; Shu-Hui Liu; Wei Tong Chen; Xiang-En Ke (Chemical Engineering Journal, 2026)

See and destroy bacterial spores: Visual detection and in situ inactivation using a terbium-porphyrin nanoplatform - Shan Sun; Ke Cheng; Jiayi Feng; Hongbo Juan; Kefeng Zhou; Mingyan Zhao; Heng Zhang; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

LC-MS-based metabolomics reveals the In Vivo effects of cognitive formula 1 in rats with Aβ-induced Alzheimer’s disease - Di Wu; Yanling Lin; Wenjun Guo; Zengling Wang; Yan Chang; Jing Yan; Daqing Han; Ke Xiang; Zhen Yang (Experimental Brain Research, 2026)

Research progress on the toxicological characteristics and biodegradation of deoxynivalenol and its derivatives - Jingjing Zhao; Yukai Lin; Yanwei Li; Meinan Chang; Lei Wang; Xiaojing Xia; Yanzhao Xu; Bo Wen; Ruibiao Wang; Ke Ding (Archives of Toxicology, 2026)

Diosmetin alleviates retinal ischemia-reperfusion injury through SIRT1-mediated suppression of oxidative stress, inflammation, and PANoptosis - Peng Fu; Xiaobo Wan; Chunrong Zheng; Xiaonian Wu; Ke Xu; Qiuyu Lin; Minli Huang (Immunologic Research, 2026)

Retraction notice to “Applying thallium isotopic compositions as novel and sensitive proxy for Tl(I)/Tl(III) transformation and source apportionment” [Sci. Total Environ. 913 (2024) 169542] - Juan Liu; Lulu Wang; Jingfen Lin; Wenhuan Yuan; Liangzhong Li; Yung-Kang Peng; Xinni Xiong; Huimin Cao; Xudong Wei; Qi'en Ouyang; Holger Lippold; Jin Wang; et al. (Science of The Total Environment, 2026)

Maternal PAN2 selectively maintains mRNA Poly(A) tail homeostasis to regulate RNA degradation during oocyte-to-early embryo transition in mice - Xuan Wu; Hua Zhang; Yu-Ke Wu; Zhuo-Yue Niu; Jing-Wen Liu; Lu Chen; Jia-Jia Cao; Yu-Lin Chen; Shu-Yan Ji; Fa-Long Lu; Heng-Yu Fan (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Nonlinear coupled dynamic response of TLP wind turbine with redundant mooring under complex environmental loads and multi-tendon failures - Mingyang Wei; Jianhua Zhang; Ke Sun; Yian Chen; Zaibin Lin; Yan Geng; Hongwen Liu; Yanghua Ou (Ocean Engineering, 2026)

Online proteolysis and specific affinity enrichment of ACE inhibitory peptides on a magnetic nanoplatform from Torreya grandis protein - Kexin Liu; Jiajun Cui; Ke Xu; Jiaqi Zheng; Yixuan Xiao; Lin Chen; Sha Li; Jiyou Yang; Hongying Guo; Xin Wang; Fei Gao; Jie Li; et al. (Food Chemistry, 2026)

Structure-property evolution of insoluble dietary fiber from wheat bran under solid-state fermentation and its effect on functional and processing properties - Wei Liang; Qian Lin; Ke Xiong; Wenhao Li (Food Chemistry, 2026)

Melanoidins-derived active-N species alleviate endogenous minerals-initiated inhibitory effect during pyrolysis of waste activated sludge: Promoting methane and short-chain hydrocarbons recovery - Yimeng Jiao; Yifei Wu; Yuxin Liu; Jingqi Yuan; Zhengda Lin; Ke Wang; Yu Tian; Jun Zhang (Environmental Research, 2026)

Engineering cellulose nanocrystal-regulated UiO-66 as a bifunctional platform for enhanced fluoroquinolone antibiotic removal - Dongdong Liu; Runkai Wang; Huiqin Wang; Kunlin Ke; Lin Li; Jiangyan Ji; Tong Wu; Xiaoli Zhu (Chemical Engineering Journal, 2026)

Laser-assisted growth of ligand-free nanocrystals for grain-boundary passivation and suppression of non-radiative defects in lead-free Cs3Sb2I9 solar cells - Wenbin Lin; Yuhua Jin; Cai Yan; Ke Sun; Yu Cao; Aumber Abbas; Ali Hassan (Chemical Engineering Journal, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Quantifying the drivers of CO decline in a typical industrial city: A data-driven framework integrating de-weather, SHAP analysis and constrained regression - Kai Xie; Yulong Yan; Jiaqi Dong; Ke Yue; Lin Peng (Atmospheric Pollution Research, 2026)

High-frequency redox fluctuations in deep-lacustrine basin and their impact on organic carbon burial: Records from micrometer-scale laminae in the Triassic Yanchang Formation Shale, Ordos Basin - Ke Li; Kelai Xi; Yingchang Cao; Zhe Zhao; Xiujuan Wang; Miruo Lin; Keyu Liu; Fang Hao (Science China Earth Sciences, 2026)

Engineering a root-associated bacterium Pseudomonas stutzeri A1501 with nitrogen fixation and phosphate solubilization activities for enhanced growth of host rice - Changyan Yin; Dongqi Wang; Bodan Su; Yaoyao Liu; Yuhua Zhan; Wei Lu; Haichao Feng; Yongliang Yan; Xiubin Ke; Min Lin (Plant and Soil, 2026)

Plant–soil feedback persists beyond host death to shape density-dependent plant competition - Ching-Lin Huang; Joe Wan; Shuo Wei; Chia-Hao Chang-Yang; Po-Ju Ke (Plant and Soil, 2026)

Pharmacogenomic screening strategy and indicative screening efficiency for antithyroid drug-induced agranulocytosis in the Southern Han Chinese - Li Ma; Sujie Ke; Peiji Huang; Yao Chen; Qian Lin; Menghua Lin; Guanlian He; Laiyu Zou; Xiaoling Chen; Xiaoying Liu; Libin Liu; Lijing Wang (European Journal of Clinical Pharmacology, 2026)

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

PIP4K2A: A Novel CD8+ T Cell-Related Biomarker Associated with Lung Function Decline in COPD - Shu Huang; Shiya Lin; Junyi Ke; Siyu Lei; Zhixiong He; Minchao Duan (Biochemical Genetics, 2026)

Exploring the complex relationship between vestibular symptoms and migraine: a resting‑state functional MRI study - Lin Han; Xing Xiong; Jiajie Lu; Kai Zhang; Jun Ke; Hongru Zhao (Brain Imaging and Behavior, 2026)

Encounter Scenario Generation and Simulation Based on a Wasserstein Generative Adversarial Network with Gradient Penalty for Autonomous Ships - Jie Shi; Shengzheng Wang; Xiuzhi Chen; Xinwei Lin; Ranxuan Ke (Journal of Marine Science and Engineering, 2026)
Virtual testing is one of the key methods for evaluating the collision avoidance capabilities of autonomous ships, and test scenarios provide the fundamental basis for its implementation. However, generating test scenarios that are both diverse and physically realistic remains a significant challenge in this field. This paper proposes a ship encounter scenario generation and dynamic simulation method for encounter situations based on a Wasserstein Generative Adversarial Network with Gradient Penalty (WGAN-GP). Specifically, the proposed framework consists of a Collision Risk Index-guided-WGAN-GP (CRI-WGAN-GP) for initial encounter scenario generation and a Physics-Informed Conditional WGAN-GP (PI-CWGAN-GP) for dynamic encounter scenario simulation. In the first stage, the CRI-WGAN-GP is developed to generate initial encounter scenarios with collision-risk characteristics. The Collision Risk Index (CRI) is directly embedded into the discriminator of the WGAN-GP. This mechanism forces the latent space to learn risk correlations, enabling effective exploration of high-risk boundaries and generating test cases with collision risks for the target ship. In the second stage, the PI-CWGAN-GP is designed to generate sequential dynamic simulation scenarios conditioned on the current encounter situation. By incorporating constraints related to ship motion performance, the PI-CWGAN-GP ensures that the generated ship behaviors are physically realistic. The proposed method is experimentally evaluated based on scenario diversity and physical realism, and the experimental results demonstrate that the proposed method can generate initial scenarios with collision risks and simulate ship behavior in encounter situations. Compared to existing random sampling and general generative adversarial network methods, the proposed approach shows significant advantages in generating more realistic and high-risk scenarios. In addition, a stress-test analysis is conducted based on a real encounter scenario, with the historical own-ship trajectory replayed as a reference response. Since no specific collision-avoidance algorithm is exposed to the generated scenarios in closed loop, the evaluation is limited to examining the encounter pressure imposed by the generated target-ship behaviors. The results show that the generated counterpart scenarios reduce the original spatial and temporal safety margins and create more demanding encounter conditions.

Targeted co-delivery of curcumin and TRAIL via engineered extracellular vesicles: a synergistic therapy against resistant cancers - Lang Liu; Jiahong Jiang; Zelin Wu; Xiaoli Wu; Jun Peng; Nuo Xu; Xudong Lin; Ronghui Sun; Yuyi Kang; Changhong Ke; Caijun Zhao; Qilin Huang; et al. (Drug Delivery and Translational Research, 2026)

Critical assessment of synthetic microbial community strategies in vinegar brewing: from design paradigms to industrialization bottlenecks - Shiyuan Lin; Yongjian Yu; Yuanyuan Zhu; Ke Wang; Zhen Yu; Yuqin Wang; Dong Han; Xuezhi Wu; Nan Zhang; Shuaiwei Dou; Yunsong Yang (Critical Reviews in Food Science and Nutrition, 2026)

Shared inflammatory targets of phthalate plasticizers in MODS-related syndromes: An integrative network toxicology study with representative DEHP in vitro validation - Lin Song; Aifeng He; Wei Jiang; Ke Liu; Jingyi Ma; Jing Wang; Keran Shi; Jiangquan Yu; Ruiqiang Zheng (Toxicology and Applied Pharmacology, 2026)

Hemodynamic decoding for multimodal connected cardiovascular healthcare - Yun Ke; Ruijun Pan; Jun Li; Wanghuai Xu; Dalong Ni; Zhou Li; Zhong Lin Wang; Fan Yang (Science Bulletin, 2026)

Experimental study on dynamic response of a calcareous seabed around a trenched pipeline under non-linear wave–current loading - Zuodong Liang; Dajun Liu; Lin Cui; Mengxiao Li; Zheng Wang; Dayu Chang; Hailun Chen; Ke Sun; Jisheng Zhang; Dong-Sheng Jeng (Ocean Engineering, 2026)

Efficient degradation and toxicity reduction of 6PPD-quinone in wastewater by a reactive electrochemical membrane: Performance and mechanisms - Juntao Shu; Yongsheng Chen; Tianxiang Wu; Chengyu Gu; Yueying Liu; Sijia Ma; Yuan Lin; Yi Xue; Hongqiang Ren; Ke Xu (Journal of Hazardous Materials, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

An adaptor protein CRK mediates antiviral immunity against white spot syndrome virus via JAK/STAT signaling pathway in Cherax quadricarinatus - Zi-Han Fan; Ling-Ke Liu; Wen-Lin Wu; Hai-Peng Liu (Fish & Shellfish Immunology, 2026)

Frame field guided optimal design for fiber-reinforced cellular structure under variable loading conditions - Ke Xu; Canhui Lin; Chenli Zhou; Kehan Feng; Yingguang Li (Engineering Structures, 2026)

Flexural behavior and ultimate moment capacity calculation of R-UHTCC-recycled concrete composite beams - Zhiqiang Gu; Zuobiao Li; Dong Wei; Danying Gao; Lin Yang; Dong Fang; Ke Shi (Engineering Structures, 2026)

Particle crushing of embedded carbonate sand within granular assemblies: A DEM analysis of stress path and particle shape effects - Zong-Lei Dong; Xian-Kang Liu; Chen-Xi Tong; Shi-Lin Luo; Ke-Chen Liu; Deng-Jie Zhang; Sheng Zhang (Computers and Geotechnics, 2026)

Linking Mo/Fe ion conversion to green treatment of sulfonylurea pesticides in farmland drainage: Role of directed electron transfer and self-produced hydrogen peroxide - Bingkun Liu; Weijun Tian; Bingjie Huo; Xinbo Wang; Xinran Yu; Wei Bao; Ke Yang; Minghan Li; Yushan Wei; Yinming Ji; Daoqing Lin (Chemical Engineering Journal, 2026)

Polyacrylamide based hydrogel with high temperature and salinity tolerance: the role of aminated distilled spent grain - Xue-Li Long; Kang-Lin Chen; Hong-Ke Yang; Hong-Li Dong; Hong-Kui He; Li-Chun Dai; Zu-Guo Yang; Zhi-Xiang Xu (Biomass and Bioenergy, 2026)

More caution or more lenient: deciphering the role of negative affect in recognition and inference - Lu Li; Hehe Lu; Ke Jiang; Huilin Qiu; Chunting Lin (Cognitive Processing, 2026)

Environmental Factors Drive Neurodegenerative Diseases Through Glutamate Excitotoxicity: A Convergent Mechanistic Pathway - Yulu He; Tingting Yi; Meixin Min; Ke Xu; Huan Lin; Rong Xu; Dan Deng; Xiaoping Xiao (Neuroscience Bulletin, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Assessing the climate and environmental benefits of new urban district development using mobile monitoring and gradient boosting decision trees - Li Han; Ke Li; Lin Luo; Yuejing Gao; Wei Ding; Jingyuan Zhao (Urban Climate, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Dinemasone D — a new polyketide derivative with anti-inflammatory activity from Phaeosphaeria poagena - Li-Bin Lin; Jia-Hao Ning; Kang-Hong Zhao; Jia-Yao Hu; Guang-Yu Bai; Pan Deng; Shao-Qi Tang; Wen-Ke Dou; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2026)

Eremophilane-type sesquiterpenes from Ligularia hodgsonii: isolation, structural characterization, and pro-angiogenic potential - Zhenhua Wan; Huilin Peng; Chunping Tang; Jiangjiang Qin; Bintao Hu; Changqiang Ke; Sheng Yao; Ligen Lin; Yang Ye (Phytochemistry, 2026)

Transition from galloping to suppression in flow-induced vibration of a circular cylinder with a flexible plate at subcritical Reynolds numbers - Yuankun Sun; Jiasong Wang; Shuqing Wang; Junfeng Du; Xiancang Song; Ke Lin; Chao Shang (Ocean Engineering, 2026)

Exploring the potential of generative AI to complement multi-stakeholder landscape preference assessment - Jingya Lin; Chongzhi Chen; Tian Feng; Sigao Huo; Kexin Zhang; Baiyu Dong; Shanshan Xiang; Ke Wang; Lu Huang (Landscape and Urban Planning, 2026)

Effects of inoculum sources from different depths and oxygen concentration on bioleaching and microbial community assembly in mine waste dump - Zi Han Lin; Bing Zhou; Chen Sheng Zhang; Xuan Qi Zhang; Yan Bo Chen; Min Liang Fei; Xiao Fei Wei; Zhang Zheng Cai; Tian Shou Hu; Jie Hu; Han Ke (Journal of Hazardous Materials, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Investigating the modulation effects of fermented dietary fiber on structure–property relationships during dough fermentation: A mechanistic study - Wei Liang; Wenqing Zhao; Qian Lin; Haiyan Gao; Jie Zeng; Ke Xiong; Wenhao Li (Food Chemistry, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Sense, think, and robot control: Multimodal material recognition sensing integrated with large language model reasoning - Zuowei Wang; Fuzheng Zhang; Qijing Lin; Yueming Gao; Bin Sun; Hongze Ke; Na Liu; Bian Tian; Libo Zhao; Zhuangde Jiang (Chemical Engineering Journal, 2026)

Facile synthesis of strontium/calcium aluminate-based persistent phosphors for enhanced functionally additive manufacturing - Yukun Li; Ke Chen; Jiaren Du; Hengli Zhu; Jiaping Zhang; Sisi Wang; Senkai Ye; Hengwei Lin (Chemical Engineering Journal, 2026)

Reactive-oxygen-species-unlocking fusogenic liposome for spatially-selectively cytoplasmic antioxidant delivery and synergistic acute liver injury treatment - Yongkang Du; Huimin Kong; Huijuan Zheng; Xiaobing Lin; Tinghua Lu; Yingting Zhao; Ke Wang; Jiadong Zhou; Ruihua Huang; Shengchun Zhang; Guang Shi; Chunxiong Zheng; et al. (Chemical Engineering Journal, 2026)

Benzotriazole ultraviolet stabilizers impair trophoblast function at nanomolar concentrations via GPER signaling: implications for placental health - Ze-Pei Zhao; Shi-Ye Zhu; Ying-Huang Hu; Yu-Ke Wan; Shang-Jun Xu; Jie-Zhi Ma; Deng-Ni Lai; An-Wei Chen; Yuan Yang; Lin Luo; Lin-Ying Cao (Chemico-Biological Interactions, 2026)

Multistage-enhanced stochastic inverse modeling approach for efficient source characterization of groundwater organic contamination - Zeyu Hou; Yifan Fu; Yingzi Lin; Ke Zhao; Tongzhe Liu; Wenxi Lu (Stochastic Environmental Research and Risk Assessment, 2026)

A Systematic Review and Meta-analysis of Empirical Evidence for the Simple Bayesian Model of Autism - Ke Cui; Xiaoxiao Lin; Ruirui Gao; Shiqi Jing; Fei Luo; Jinyan Wang (Neuropsychology Review, 2026)

Behavioral responses of juvenile grass carp (Ctenopharyngodon idella) to temporal-spectral variants of a predator-derived sound - Yujiao Wu; Ji Yang; Guoyong Liu; Jiawei Xu; Senfan Ke; Dongqing Li; Chenyu Lin; Xiaotao Shi (Environmental Biology of Fishes, 2026)

Mg2+-driven triple nucleic acid cascades amplify Ru-encoded bimetallic MOF sign PFOA monitoring - Lin-Yi Liu; Ya-Qian Xie; Yue Peng; Si-Yi Ren; Ke-Dao Lai; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2026)

Consensus control for relative configuration maintenance of large-scale LEO constellations - Xiaoyu Zuo; Ke Li; Ziyuan Yang; Lin Chen (Advances in Space Research, 2026)

Study on prestack reservoir prediction of deep volcanic rock gas reservoirs in Chaganhua sub-sag of Songnan Fault Depression - Qin-lin Yang; Xue-pei Fan; Chen-chen Bi; Lan-mei Ke; Ye Yang; Da Zhang; Shu Wang (Applied Geophysics, 2026)

Neutrophil extracellular traps in post-traumatic urethral microenvironment promote hypertrophic urethral stricture via the TLR9/NF-kB/Smad3/IL-8 axis - Ye-Hui Chen; Zhi-Bin Ke; Bo-Han Lin; Yi-Cheng Xu; Xue-Yi Xue; Qing-Shui Zheng; Xiong-Lin Sun; Yong Wei; Ying-Chun Liang; Ning Xu (Apoptosis, 2026)

Alternative stable states in coral communities along a latitudinal gradient simplify sediment bacterial assemblages but stabilize biogeochemical functions - Wentao Zhu; Zihan Qiu; Pei Yang; Jingzhao Ke; Xiangbo Liu; He Zhao; Jiquan Lin; Yuxiao Ren; Duanjie Huang; Xiubao Li (Ocean & Coastal Management, 2026)

Partial sympatry of two interspersed Uroteuthis edulis (Loliginidae) clades reveals cryptic stock structure in the southern Taiwan Strait - Rui-Yi Hong; Lorenzo C. Halasan; Ke-Yang Chang; Chia-Hui Wang; Hsiu-Chin Lin (Fisheries Research, 2026)

Inertial-buoyant coupling and bi-directional flow effects on plume deflection in inclined tunnel fires under natural ventilation - Tianhang Zhang; Lei Liu; Ke Wu; Shaorun Lin; Shiyi Wang; Xin Zhang (Tunnelling and Underground Space Technology, 2026)

Influence of hydro-mechanical parameter coupling on the dynamic behavior of unsaturated railway subgrades - Shumeng Wu; Liqun Zeng; Jing Hu; Zhongfeng Yang; Hongyang Ke; Xin Ding; Zhihang Lin; Xuecheng Bian (Soil Dynamics and Earthquake Engineering, 2026)

Hollow-structured covalent organic framework nanocapsules enable sustained benzaldehyde release for antimicrobial preservation of postharvest peach fruit - Dan Jiang; Yuting Ma; Xubin Wu; Zhihao Li; Siyin Lin; Kunsong Chen; Jian Wu; Ke Zhu; Pingwei Liu; Bo Zhang (Postharvest Biology and Technology, 2026)

Crustacean cardioactive peptide activates pupal ecdysial behavior in the 28-spotted larger potato ladybird - Yi-Kuan Wu; Nan Wu; Wei-kang Zheng; Li-ke Ding; Yi-fei Wu; Lin Jin; Guo-Qing Li (Pesticide Biochemistry and Physiology, 2026)

A comprehensive review on all-solid-waste cementitious materials: activation, preparation, sustainable performance and applications - Yuliang Hu; He Wang; Yuxuan Duan; Kailun Chen; Jinglin Li; Li Lin; Endian Hu; Jingwen Chang; Ke Liu; Jianguo Jiang (Journal of Environmental Management, 2026)

Genetic diversity analysis of three geographical populations of Triplophysa yarkandensis macroptera in arid northwestern China - Ya Liu; Hangyu Lin; Hongyu Ke; Han Zhao; Zhongmeng Zhao; Shengqi Su; Qiang Li (Journal of Arid Environments, 2026)

Lithium isotope fractionation in LCT pegmatite systems: a density functional theory study - He-Feng Lin; Wen-Bin Zhu; Hai-Zhen Wei; Xi-Sheng Xu; Zhi-Qin Xu; M.R. Palmer; Shuang Chen; Jing Ma; Yin-Chuan Li; Da-Sheng Zuo; Ke Yang (Geochimica et Cosmochimica Acta, 2026)

Hierarchical intelligent braided silk yarns for ligament reconstruction and prognosis assessment - Ke Ma; Ke Wang; Shou-Shan Yu; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2026)

Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

The combination of Astragalus membranaceus and Lycium barbarum polysaccharides is superior to either alone in enhancing growth and health of grass carp (Ctenopharyngodon idellus) - Wei Zhang; Lin Ma; Yi-Geng Meng; Ke-Ming Liu; Hong-Qing Sun; Chao Cai; Ming-Ze Li; Yuan-Yuan Dai; Wen-Wen Li; Xin Luo; Nan Li (Animal Feed Science and Technology, 2026)

Discovery and engineering of a new BvCas12a nuclease for mammalian genome editing and nucleic acid detection - Xuechun Shen; Lei Huang; Dan Wang; Chen Qi; Baitao Li; Chuan Liu; Ke Chen; Yuanqiang Zou; Liang Xiao; Yuan Jiang; Qiupeng Lin; Hongxia Lan; et al. (Science China Life Sciences, 2026)

Spatiotemporal distribution of polycyclic aromatic hydrocarbons in seawater and surface sediments of the Daya Bay, China - Weihua Deng; Yingshi Lin; Yayuan Xiao; Ke Yuan; Tiangang Luan; Li Lin (Regional Studies in Marine Science, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Evaluating the role of onboard carbon capture and storage system in remedial unit balancing under the IMO net-zero framework: Insights from GFI and 4E analysis - Yihang Zhou; Shuai Deng; Zhen Tian; Ke Li; Meng Lin; Li Zhao; Chunfeng Li; Xiaohan Zhao; Yijiang Tian; Wenjing Zhang; Min Shi (Journal of Cleaner Production, 2026)

Sorbitol-enhanced butyric acid production in mixed-culture anaerobic fermentation of potato peel waste - Yu Lu; Ke Zheng; Fei Zhao; Lin Ding; Limin Zheng; Jiying Zhu (Journal of Environmental Management, 2026)

Efficient roxarsone degradation via in-situ H2O2 generation through 2e−ORR over a Pd-Fe2O3 catalyst system - Ruibin Yang; Shuang Yao; Yijun Chen; Zhiwen Jiang; Hangyu Zhang; Ke Wang; Dapeng Li; Feng Liu; Feiyue Qian; Hailiang Yang; Sanjian Ma; Zixia Lin; et al. (Journal of Environmental Management, 2026)

Deciphering the clearance efficacy on the soil of slag stockpiles via lead isotopic signatures - Zhenghua Tao; Lina Zhang; Lin Jia; Ke Pan; Rongfei Wei; Shanshan Chen; Xiaoying Zhu; Ningning Wang; Danhua Yang; Tianxiang Xia (Journal of Environmental Management, 2026)

Corrigendum to “Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration”. [229 (2026) 118495/FRIN 118495] - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Unveiling the flavor evolution and metabolic mechanism in closed solid-state fermentation of vinegar: a multimodal omics integration - Nan Zhang; Yong jian Yu; Ke Wang; Yuan yuan Zhu; Yu qin Wang; Dong Han; Xue zhi Wu; Yun song Yang; Shuai wei Dou; Shi yuan Lin (Food Research International, 2026)

Ferulic acid vs. p-coumaric acid: Divergent effects on gluten/glutenin/gliadin multi-level structure and physicochemical properties—from aggregation behavior and spatial conformation perspective - Qian Lin; Wei Liang; Wenqing Zhao; Ke Xiong; Wenhao Li (Food Hydrocolloids, 2026)

Integrated electricity‒heat scheduling optimization strategy for biomass-PV-battery islanded microgrid with micro turbine in high-latitude regions - Gong Wang; Ke Dong; Yuanhua Song; Shengxian Cao; Liuming Gao; Mingli Yu; Hao Gan; Chuanjie Lin; Guichao Duan; Huijing Sun (Biomass and Bioenergy, 2026)

Functional reorganization of microbial ecological clusters is associated with citrus soil health enhancement under greenhouse cultivation - Chenhong Liu; Qi Zhao; Lin Zhang; Fuzhi Ke; Xuebin Xu; Senxiang Yu; Jiaping Lang; Tida Ge; Cong Wang; Haoqing Zhang (Plant and Soil, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Magmatic evolution and mush processes of the Xiarihamu Ni-Cu deposit: insights from olivine-orthopyroxene-clinopyroxene chemistry - Xu-Yang Zheng; Ya-Jing Mao; Fang-Lin Yuan; Yi Li; Wen-Jun Li; Ke-Zhang Qin (Mineralium Deposita, 2026)

Integrated Analysis of mRNA-seq and miRNA-seq Reveal the Dynamics of the Gonadal Differentiation of Procypris Mera - Zhenling Ke; Weijun Wu; Zhe Li; Yusen Li; Yaoquan Han; Jun Shi; Lilong Chen; Kangqi Zhou; Dapeng Wang; Yong Lin; Min Li; Hua Ye (Marine Biotechnology, 2026)

Haplotype-resolved chromosome-level genome assembly of European chestnut (Castanea sativa) and comparative analysis in the genus of Castanea - Xingyan Li; Ke Lin; Po Hong; Ting Yu; Qian Qiao; Dongzi Zhu; Jiawei Wang; Qingzhong Liu (Plant Biotechnology Reports, 2026)

Nondecomposer-mediated nutrient transfer in soils: experimental evidence from Drosophila - Yunchao Luo; Run Liu; Tingting Cao; Jiayue Zhang; Mengna Zhao; Ke Li; Zunian Ran; Lin Wang; Xingjun Tian (Applied Soil Ecology, 2026)

Tracing thallium pollution in arsenic mining/smelting areas using high-precision thallium isotopic composition - Xudong Wei; Shunlong Jiang; Jin Wang; Hangfei Guo; Dieyu Chen; Ke Lin; Meiling Yin; Wanpeng Chen; Yinyin Lu; Yurong Gao; Juan Liu (Applied Geochemistry, 2026)

Molecular mechanisms of per- and polyfluoroalkyl substances (PFASs) removal from sludge alkaline fermentation liquid by coagulation: Role of interactions between DOM and PFASs - Chengyu Gu; Sijia Ma; Yuan Lin; Yi Xue; Hongqiang Ren; Ke Xu (Water Research, 2026)

Ecological regime shifts weaken sedimentary carbon sequestration in shallow Lake liangzi - Jinglin Hou; Qi Lin; Jiasheng Zhang; Shixin Huang; Yuan Jin; Yanhua Wang; Haibo He; Pierre Taillardat; David Taylor; Ke Zhang; Michael E. Meadows (Water Research, 2026)

Deformation response and damage evolution of subway station under earthquake and post-earthquake fire - Jun-Xing Rao; Zhen-Dong Cui; Zhang-Lin Zhu; Ke-Xuan Li (Tunnelling and Underground Space Technology, 2026)

A scalable and efficient framework for city-scale building energy modeling with microclimate considerations - Ke Liu; Xiaodong Xu; Deqing Lin; Ran Zhang; Linzhi Zhao; Abudureheman Abuduwayiti; Francesco Causone (Sustainable Cities and Society, 2026)

Microwave-driven molecular activation enables efficient hydrogen recovery via low-carbon plastic recycling - Jinglin Li; Endian Hu; Kailun Chen; Li Lin; Jingwen Chang; Ke Liu; Yukun Zhao; Jianguo Jiang (Resources, Conservation and Recycling, 2026)

Robust high-temperature macroscale superlubricity enabled by interface engineering of boronized surfaces and hydroxyl-rich polyol lubricants - Yixuan Zhang; Hongxing Wu; Hang Li; Lin Wang; Junqin Shi; Ke Hua; Haifeng Wang; Feng Zhou; Weimin Liu (Science Bulletin, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Sustainable production-oriented systematic-dynamic assessment framework for integrated risks in China's energy internet - Lei Xu; Lin Zhu; Ke Shen; Yanfei Deng (Journal of Cleaner Production, 2026)

Accelerated photo- and electrocatalytic processes for hydrated electron-induced degradation of perfluorooctanoic acid: Defluorination mechanisms, affecting parameters, and future horizons - Huiqi Zheng; Amin Zhou; Abdelkader Labidi; Ke Zhao; Yuhan Lin; Chuanyi Wang (Journal of Environmental Sciences, 2026)

Microbial metabolic remodeling under the electric field: A CUE-centered mechanism for enhanced petroleum bioremediation - Ruijuan Fan; Ke Li; Yang Lin; Bingyan Yin; Xingfu Yan (International Biodeterioration & Biodegradation, 2026)

How wheat bran color gradients shape phenolic acid profiles and antioxidant activity: A comparative and analytical study - Qian Lin; Wenqing Zhao; Xiangrui Ren; Wei Ling; Ke Xiong; Wenhao Li (Food Research International, 2026)

Blue food proteins-derived immunomodulatory peptides: sources, preparation, identification techniques, mechanisms, and critical challenges of commercial application - Yu-Han Wu; Yan Chen; Ke-Lin Zhang; Fang-Miao Yu; Bin Wang; Qi Zeng (Food Research International, 2026)

Bioinspired Janus starch film with dual functionality via citral nanoemulsion-mediated interfacial self-assembly for fresh-cut fruits and vegetables preservation - Ying Xie; Yuying Sun; Yawen Li; Ke Ding; Shikai Zhang; Saiqing Xu; Huan Li; Shuhua Lin; Yang Shan; Rongrong Wang; Shenghua Ding (Food Hydrocolloids, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

Effects of forest-medicinal plant intercropping on soil carbon pools in coastal saline-alkali land - Kaiwen Huang; Jinling Wang; Jie Kuai; Xin Liu; Jiajun Ou; Jiayi Miao; Ke Huang; Jie Lin (Plant and Soil, 2026)

Morusin attenuates myocardial ischemia/reperfusion injury by inhibiting ferroptosis via dual activation of the Nrf2/HO-1 pathway and mTORC1-dependent GPX4 synthesis - Zhiqiang Lin; Douli Ke; Mingyu Zheng; Hanhan Qiu; Binghuang Huang; Yiting Wei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluating adverse events reported for non-steroidal anti-inflammatory drugs in osteoarthritis: a real-world pharmacovigilance study - Kesong Zhang; Honghao Ren; Xiaodong Ren; Pengfei Wen; Ke Xu; Lin Liu; Peng Xu; Ming Zhang; Zhi Yang; Mingyi Yang (Inflammopharmacology, 2026)

Hydrochemical characteristics and evolutionary mechanism of karst groundwater in the Xujiagou spring area of North China plain - Yun Lin; Xiao-ke Wang; Ya-zun Wu (Carbonates and Evaporites, 2026)

Boron and oxygen isotopes fractionation between borate minerals and fluids and implications for borate deposit formation - Da-Sheng Zuo; Hai-Zhen Wei; Jian-Jun Lu; M.R. Palmer; A.E. Williams-Jones; Jun-Lin Wang; Shao-Yong Jiang; Ke Yang; He-Feng Lin; Simon V. Hohl; Yi-Chu Chen (Applied Geochemistry, 2026)

Autumnicola aciditolerans sp. nov., a novel member of the genus Autumnicola isolated from tidal flat in Zhoushan - Yang Li; Dong-Yan He; Jia-Wei Gao; Ke Cao; Yun-Fei Cao; Xing-Cheng Wang; Lin Xu; Yan Bai; Can Chen; Cong Sun (Antonie van Leeuwenhoek, 2026)

Experimental Study of the Combined Action of Random Waves and Current Induced Hydrodynamics and Seabed Response Around a Protective Three-Dimensional Pipeline - Dayu Chang; Risheng Wang; Wenqi Si; Mengxiao Li; Zheng Wang; Dajun Liu; Ke Sun; Dong-Sheng Jeng; Lin Cui; Dejian Wei (Journal of Marine Science and Engineering, 2026)
Submarine pipelines serve as the primary transportation infrastructure for offshore energy resources and are becoming increasingly important in modern industrial and domestic applications. A series of laboratory experiments on the dynamic seabed response of three-dimensional pipeline-seabed systems under random wave and current conditions was conducted. The results demonstrate as follows: (1) Under the combined action of random waves and ambient currents, the wave profiles in the vicinity of the submarine pipeline exhibit distinct irregular and nonlinear characteristics; (2) Compared with random waves acting alone, the superposition of random waves and currents modifies wave propagation behavior: a co-directional current enhances wave propagation, whereas a countercurrent suppresses it; (3) For a pipeline subjected to the three-dimensional random waves, pore-pressure amplitude decreases with increasing wave-incidence angle. Specifically, maximum values corresponding to incidence angles of 30° and 45° are generally lower than those at 0° and 15°, at a seabed depth of z/d = 0.0938, and the value at an incident angle of 45 degrees attenuates by 21.31% compared to that of 0°; (4) Coarse sand exhibits weaker pore-pressure attenuation than fine sand around the three-dimensional pipeline-seabed scheme, indicating that sediment grain size exerts a substantial influence on seabed response; (5) The protective effect of geotextile and stone is more obvious, whereas PVC is limited to the front and underside of the pipe. The deeper the seabed, the smaller the effect of protective measures. For reproducibility, the test matrix covered wave-incidence angles α = 0°, 15°, 30°, and 45°, irregular-wave conditions with H1/3 = 0.08–0.14 m and T1/3 = 1.2–1.8 s, and currents U = –0.2 m/s at a constant still-water depth h = 0.45 m.

Differences in Habitat Substrate Preference Selection Among Sexes and Populations of Leptobotia elongata - Lixiong Yu; Min Wang; Jiaxin Li; Fengyue Zhu; Yuliang Yuan; Huiwu Tian; Mingdian Liu; Weiwei Dong; Ji Yang; Senfan Ke; Chenyu Lin; Xinbin Duan (Fishes, 2026)
Cascade hydropower development in the upper Yangtze River has substantially altered riverine habitat conditions. However, quantitative information on fish substrate preferences remains limited. Based on field surveys, six representative substrate types were identified in the Yibin and Jiangjin reaches, and substrate selection patterns of Leptobotia elongata were quantified under controlled flume conditions. This study examined sex-specific and population-level differences in substrate preference. A total of 50 samples were analyzed using one-way ANOVA and the Kolmogorov–Smirnov test. The results are summarized as follows: (1) Substrates of 40–20 mm: Individual female L. elongata exhibited the longest residence time on the 40 mm substrate (1640 s), while individual males also spent the longest time on the 40 mm substrate (1549 s). Within this substrate range, males showed a preference only for the 40 mm substrate (PR = 739), whereas females preferred three substrate types, with the strongest preference for the 40 mm substrate (PR = 7543). (2) Substrates of 10–2.5 mm: Female individuals spent the longest time on the 10 mm substrate (1468 s), and male individuals likewise showed the longest residence time on the 10 mm substrate (1568 s). In this range, males did not show a significant preference for any substrate (PR = −907), whereas females preferred three substrate types, with the 2.5 mm substrate exhibiting the highest preference intensity (PR = 2059). (3) Population-level patterns for 40–20 mm substrates: The population spent the longest time on the 40 mm substrate (1799 s) and preferred three substrate types, among which the 20 mm substrate had the highest preference ratio relative to the other preferred substrates (PR = 4750). (4) Population-level patterns for 10–2.5 mm substrates: The longest residence time was observed on the 10 mm substrate (1762 s). The population preferred three substrate types, with the 10 mm substrate showing the highest preference ratio (PR = 5709). Overall, L. elongata showed a general tendency to prefer larger-sized substrates. This preference is likely associated with enhanced habitat complexity, improved foraging opportunities, and the formation of low-velocity refuges. Our results suggest that maintaining or restoring coarse substrate patches in regulated reaches may improve habitat suitability for L. elongata and potentially benefit other benthic fishes with similar ecological requirements.

Research on rule of law system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area - Ke Zhang; Er-He Chen; Yu-Lin Chen; Jun-Jie Li; Tao Huang; Wei Liu; Si-Hao Wei; Yu-Kang Tu (Frontiers in Marine Science, 2026)
The development of a legal system for marine environmental protection in the Guangdong-Hong Kong-Macao Greater Bay Area is a critical issue for cross-border ecological governance under the unique context of "One Country, Two Systems, Three Jurisdictions." This issue directly affects regional ecological security and the high-quality development of the marine economy. This paper uses comparative law and empirical analysis to systematically review the institutional frameworks and current practices of the three regions across four dimensions: Legislation, law enforcement, judicial adjudication, and legal regulation of public participation. The study finds that the current system faces core difficulties, including a disconnect in legislative coordination mechanisms, insufficient effectiveness in joint law enforcement, uncoordinated judicial collaboration, and insufficient legal safeguards for public participation. The root causes lie in the differences between regional legal systems, the absence of coordination mechanisms, poor resource integration, and fragmented participation channels. Based on this, the paper proposes a comprehensive improvement path. At the legislative level, we should establish a normalized coordination mechanism to promote the alignment of rules and standards. At the enforcement level, we should build a unified coordination platform to deepen cross-border collaboration and resource sharing. At the judicial level, we should improve cross-border collaboration norms and improve mechanisms for identifying and repairing ecological damage. At the level of public participation, we should build a unified cross-border platform to strengthen collaborative systems and public interest cooperation. The research aims to provide a governance model for regional marine environmental protection under "One Country, Two Systems, Three Jurisdictions," offering theoretical support and practical guidance for solving cross-border ecological governance problems, and assisting in the construction of a strong maritime nation and the improvement of the global marine governance system.

Research on Combustion Strategies for Marine Low-Speed Two-Stroke Direct Injection Ammonia/Diesel Dual Fuel Engines - Ye-Peng Li; En-Zhe Song; Ke-Shuai Sun; Yi-Lin Ning (Journal of Marine Science and Engineering, 2026)
This study investigates the combustion and emission characteristics of a marine low-speed two-stroke engine using diesel-ignited ammonia dual direct injection. Using a validated 3D CFD model, the impact of ammonia blending ratios (Ra) was systematically explored. Results indicate that the strategy of shifting energy from early diesel injection to late ammonia injection physically repositions the combustion phasing. Rather than ammonia delaying the heat release, this late injection strategy avoids the overly early combustion observed at low ammonia concentrations, thereby lowering peak in-cylinder temperatures while maintaining robust work extraction. Consequently, indicated power at the N90 condition increases by 3.5% (to 1689 kW) over the diesel baseline, with a minimum EISFC of 165.5 g/kWh. High-ratio ammonia blending achieves deep decarbonization: at N90, peak CO and soot emissions are reduced by over 90% and 95%, respectively. Additionally, NOx emissions decrease by approximately 70% at N90 compared to the N20 peak, attributed to the thermal DeNOx mechanism. However, the low-temperature environment introduces trade-offs, leading to increased ammonia slip (4 ppm at N90) and elevated N2O emissions (peaking at N70). These findings clarify the mechanisms governing ammonia combustion and provide theoretical support for optimizing zero-carbon marine propulsion systems.

Whole-genome sequencing reveals the genetic diversity of Aeromonas from freshwater fish and the presence of novel genomic islands carrying clinically important antimicrobial resistance genes - Xiao-Qin Wang; Ke Wu; Run-Min Kang; Heng Lin; Lu-Ya Liu; Ting Xian; Yi-Zhi Tang; Xin Yang; An-Yun Zhang; Hong-Ning Wang; Chang-Wei Lei (Aquaculture, 2026)

Co-pyrolysis-to-co-gasification continuum of Pennisetum hydridum and waste tires: Temperature/atmosphere/synergy characterization of tar/char/gas products - Sen Lin; Xin Chen; Guopeng Ke; Jingyong Liu; Zhibin Chen; Leyao Tao; Weijie Li; Fatih Evrendilek; Sheng Zhong; Zuoyi Yang; Yao He; Liangzhong Li (Journal of Cleaner Production, 2026)

Autonomous DNA walker-driven bioelectrocatalytic system with spatiotemporal control for ultrasensitive molecular diagnostics - Bei Zhang; DanYao Tang; Lin Sun; Haibo Wang; Jiawen Wu; Yanni Luo; Ke-Jing Huang; Shengyu Xie (Journal of Environmental Chemical Engineering, 2026)

Bacillus and lactic acid bacteria inoculation to transform kitchen waste using Hermetia illucens - Guoyou Deng; Min Yan; Shengzhi Yang; Lin Ji; Xinfeng Han; Xiumei Yu; Ke Zhao; Likou Zou (Journal of Environmental Sciences, 2026)

Orbital forcing across a predominantly eolian record of the Eocene–Oligocene transition, Inner Mongolia, China - Ke Xu; Nan Wu; Jianye Ren; David B. Kemp; Lin Ye; Zhongheng Sun; Xiangrong Yang; Xianghui Zhang; Mingsong Li (Global and Planetary Change, 2026)

Pore structure reconfiguration and microscale fluid response in bituminous coal under CO2 and flue gas-enhanced coalbed methane recovery - Ke Li; Chuanjie Zhu; Jiawei Wang; Xuanye fan; Yuchen Liu; Cheng zhai; Baiquan Lin (Fuel, 2026)

Organic substitution for synthetic fertilizer mitigates the negative effects of warming on soil quality, greenhouse gas emissions, and soybean yields - Xiaoyu Wang; Jiangsen Chu; Mengyou Zhang; Mingjun Hou; Ke Zheng; Leili Lin; Zhengjun Yan; Xiaoxiao Li; Zhao Che; He Song; Gong Wu (Field Crops Research, 2026)

Bio-based TEMPO-CNC reinforced Fe-doped UiO-66 with hierarchical porosity for efficient enrofloxacin removal - Dongdong Liu; Shun-xin Chen; Runkai Wang; Lin Li; Jiangyan Ji; Tong Wu; Kunlin Ke; Fei Chai (Environmental Research, 2026)

Coeffects of iron oxides and phosphorus fractions on soil organic carbon stabilization in rubber-based tropical agroforests - Liping Wang; Chaoxian Wei; Bigui Lin; Xiwang Ke; Qinfen Li; Beibei Liu; Yukun Zou (Journal of Soils and Sediments, 2026)

Effect of forest trail vegetation density on health benefits: an empirical study based on mobile measurements - Chengcheng Zeng; Ke Wang; Wei Lin; Qibing Chen (European Journal of Forest Research, 2026)

Two new amino acid-derived oximes from the mangrove-sediment-derived fungus Lecanicillium kalimantanense SCSIO 41702 - Xu-Meng Ren; Lin-Fang Zhong; Ke-Yue Wu; Xiao Liang; Shu-Hua Qi (Natural Product Research, 2026)

Post-cyclic undrained behaviour of marine soft clay under cyclic loading with variable confining pressure - Junhao Tong; Dongyang Yuan; Changjun Li; Haozheng Wang; Dingyu Ni; Ke Wu; Pixian Si; Qiang Wang; Lin Guo (Marine Georesources & Geotechnology, 2026)

Spatiotemporal variations of halogenated polycyclic aromatic hydrocarbons in sediments of Pearl River Estuary: Occurrence, sources, and potential ecological risks - Fan Lin; Yan Li; Li Lin; Ke Yuan; Lihua Yang; Yongshun Huang; Baowei Chen; Tiangang Luan (Marine Pollution Bulletin, 2026)

Molecular identification and population genetic analysis of a three-way cross hybrid abalone - Haichen Zhang; Qizhen Xiao; Weihong Lin; Zekun Huang; Benben Miao; Yang Gan; Chengyun Li; Caihuan Ke; Xuan Luo; Weiwei You (Aquaculture, 2026)

Carbon quantum dot-induced bio-hybrid of Shewanella oneidensis MR-1 for enhanced extracellular hexavalent chromium reduction - Wenkang Zhang; Ke Shen; Fangjing Lin; Rongmei Tan; Heng Ding; Xiaojie Hu; Yanzheng Gao; Hefei Wang (Water Research, 2026)

Mitigating antibiotic resistance genes in chicken manure composting through hydrothermal carbonization solution of sewage sludge - Guangchun Shan; Ke Wang; Weiguang Li; Zhenling Li; Jie Liu; Lin Zhu; Xiaoshu Wei; Beidou Xi; Wenbing Tan (Process Safety and Environmental Protection, 2026)

Characterization of the mechanism of action of a re-engineered spider toxin acting on insect voltage-gated sodium channels - Felipe Andreazza; Wilson Valbon; Joseph Tourtois; Cadence Flohrschutz; Lucy Bell; Kyle Schneider; Lin Bao; Ke Dong (Pesticide Biochemistry and Physiology, 2026)

Synergy between monomer oxygen vacancies and oxygen vacancy clusters in MnO2 enables efficient catalytic decomposition of N2O - Hui Dang; Wanjun Zhao; Chengming Zhang; Ruifang Wu; Liangliang Zhang; Ke Zheng; Shize Hu; Xiangqian Lin; Aiping Jia; Zhenxing Ren; Yongzhao Wang; Yongxiang Zhao (Journal of Hazardous Materials, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

Occurrence of beryllium and its microscale interactions with coexisting phases in beryllium-containing sludge - Xiaobo Min; Lin Yu; Yong Ke; Yunyan Wang; Wenming Zeng; Hui Xu; Yun Li; Cong Peng; Zhumei Sun (Journal of Environmental Sciences, 2026)

Anti-inflammatory effect of high-abundance Core oligopeptides from white tea via the PI3K/AKT/NF-κB signaling pathway - Zhizhan Lao; Xiaoqing Lin; Xiuqin Ye; Weihao Ke; Cong Wu; Xuelian You; Xiaojuan Wang; Feng Zhao (Food Chemistry, 2026)

Exposure to triclosan and triclocarban is associated with estrogen metabolism in Chinese pregnant women - Min Huang; Yi Wang; Yuanping Wang; Baochang Sun; Guankai Lin; Ke Zhao; Jiaqi Liu; You Zhou; Xiaoting Wen; Xiaoyang Xu; Sumiao Hong; Yuanyuan Chen; et al. (Environmental Research, 2026)

Alloy-sulfide co-engineered thin Li anodes suppress dead-Li for practical high-energy-density lithium metal batteries - Qiyang Chen; Jing Zhu; Yuanfan Zhao; Wenrui Zheng; Hanqing Pan; Yinlong Lin; Yating Ke; Xinghui Wang (Chemical Engineering Journal, 2026)

Sulfone site enables H2O2 practical fabrication over metal-free photocatalyst - Zhi-Peng Tao; Lin Liu; Ke-Chao Wang; Chen-Ning Li; Jia-Qi Chu; Zhen-Hui Kang; Zheng-Bo Han (Chemical Engineering Journal, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Constructing an integrated photocatalytic-Fenton-like system for rapid sterilization by S-scheme SCN@CuS heterojunction with manipulated charge dynamics and activated H2O2 - Mingzhu Yuan; Ran Qiu; Weile Xie; Yan Ke; Yangyang Li; Yuanxu Liu; Zibing Liu; Yupeng Yuan; Qinghua Liu; Xiangang Lin (Chemical Engineering Journal, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

AI-driven framework for high-precision seamless sunshine duration estimation using Himawari-8 satellite and ground observations - Honglei Wu; Zhaohua Liu; Zhaoliang Zeng; Ke Gui; Zhijian Lin; Peng Xie; Ruqing Zhu; Zhehao Liang; Yaqiang Wang; Huizheng Che (Atmospheric Research, 2026)

Applying Interpretable Machine Learning for Hypoxia Mitigation: an Operational Framework Coupling Predictive Modeling and Causal Inference for Urban River Management - Jia-yun Chen; Da-wei Wang; Zu-lin Hua; Ke-jian Chu; Li Gu (Water Resources Management, 2026)

Full-Scale Linear Cutting Experiment to Study the Rock Breaking Characteristics of the SBM Inclined-Mounted Cutter - Jing Xiao; Yimin Xia; Mei Yang; Zhiyong Ji; Wei Ke; Laikuang Lin (Rock Mechanics and Rock Engineering, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

Fluvoxamine Attenuates Blood–Brain Barrier Disruption in Drug-Resistance Epilepsy and inhibits Ferroptosis via the Sigma-1 Receptor-TAMM41 signaling in bEnd.3 cells - Lin Guo; Siyu Liu; Na Lv; Jianlun Ji; Xinting Lin; Ying Ke; Zhidong Liu; Congcong Sun; Yun Wang (Molecular Neurobiology, 2026)

Comparative study on organic composts in blueberry: insights into soil physicochemical properties and heavy metal control - Hao Tang; Ying Dai; Lijuan Tang; Juan Guo; Ke Wen; Fangke Yuan; Lin Li; Yuan Jin; Jinlu Li; Min Xiao; Heng Xu (Environmental Geochemistry and Health, 2026)

Experimental study on dynamic level monitoring of steam generator under different main steam line break conditions - Biaoxin Wang; Jianhao Chen; Hanbing Ke; Mei Lin; Qiuwang Wang (Annals of Nuclear Energy, 2026)

Characteristics of Extratropical Cyclones and Associated Precipitation Across the Huang‐Huai River Basin, East China - Zhiqiang Lin; Long Jiang; Xiuping Yao; Linyi Lyu; Ke Li; Caiyun Feng (International Journal of Climatology, 2026)
The Huang‐Huai River Basin (HHRB) in East China is highly susceptible to frequent floods and droughts, making it one of the most disaster‐prone regions in China. Extratropical cyclones (ETCs) are the primary weather systems generating precipitation over the HHRB. This study investigates the spatiotemporal characteristics and precipitation patterns of ETCs affecting the HHRB, based on a long‐term dataset (1979–2022) derived from ERA5 reanalysis. On average, 33.2 ETCs traverse the HHRB annually, exhibiting a statistically insignificant increasing trend over the study period. Most ETC activity occurs during summer months and nighttime hours. ETCs contribute to approximately 60% of the HHRB's total precipitation, with their contribution increasing for more intense precipitation events. Based on source regions and tracks, the ETCs are classified into five distinct types: locally generated systems and those originating from northwestern, northeastern, southwestern, and southern China. Locally generated ETCs produce the largest total precipitation, whereas those originating from southwestern China trigger the most intense rainfall events. ETC‐induced precipitation plays a crucial role in driving summer floods and droughts over the HHRB. Consequently, a deeper understanding of the characteristics, formation mechanisms, and precipitation‐generating processes of these systems is essential for effective disaster prevention and mitigation strategies.

Geophysical Characteristics and Prospecting Significance of the Halong’erma Polymetallic Deposit in the East Kunlun Metallogenic Belt - You Zhou; Zhi-Qiang Zhang; Ji-En Dong; Hai-Yue Fu; Fa-Long Qi; Wen-ke Fan; Hao Ren; Xue-lin Huang (Applied Geophysics, 2025)

Two new phenylethanol glycosides from the roots of eleutherococcus senticosus (rupr. et maxim.) maxim - Jia-Tong Wu; Ke Xiao; Hao-Lin Yang; Hui-Chen Zhu; Si-Yi Wang; Juan Pan; Meng-Meng Li; Wei Guan; Hai-Xue Kuang; Yan Liu (Natural Product Research, 2025)

NiCl2@g-C3N4-based Label-free Dual-mode Sensing Platform for Highly Sensitive and Selective Detection of MicroRNA-183-5p in Serum - Jinxiong Xue; Jingping Huang; Xue Lin; Wuyuan Pan; Fang Ke (Journal of Fluorescence, 2025)

Structure and biological activity of a novel polysaccharide from marine Cladosporium velox SCAU272 - Lingzhen Ye; Ke Xu; Youhong Li; Wenshen Lin; Lingshan Zou; Xiaoyong Zhang; Riming Huang; Jun Liu; Bin Wang (Natural Product Research, 2025)

Aquatic community synchrony dynamics in response to multitrophic regime shifts: Paleoecological insights from a shallow lake - Yuan Jin; Ke Zhang; Qi Lin; Shixin Huang; Xin Zhou; Junming Ren; Michael E. Meadows (Water Research, 2025)

Enantioselective study of hexythiazox in earthworms (Eisenia fetida): Bioaccumulation, degradation, enantiomer-specific profiling and perturbed metabolic pathways - Mengting Zhang; Yiyun Cai; Qixing Tang; Cancan Yang; Xiaojiang Ke; Jirui Wang; Lin He; Ping Zhang (Pesticide Biochemistry and Physiology, 2025)

Biogeochemical processes play a decisive role in determining the fate of marine PAHs: A case validation with field measuring and modelling in the Beibu Gulf, South China Sea - Jingwen Shi; Mengyang Liu; Lingxin Chen; Jiandong Ye; Wupeng Xiao; Jinyan Xie; Fajin Chen; Yi-Fan Li; Xuke Chen; Yan Lin; Lin Zhang; Mingjun Feng; et al. (Journal of Hazardous Materials, 2025)

A distinctive merocyanine-based fluorescent probes for the detection of phosgene and hydrazine - Wen-Ke Jiang; Xu Wang; Wei-Na Wu; Lin-Yan Bian; Yun-Chang Fan; Yuan Wang; Zhi-Hong Xu; Lintao Zeng (Journal of Hazardous Materials, 2025)

Oxygen vacancies in MnO2 as active sites for photothermal catalytic degradation of formaldehyde - Yu-Syuan Liou; Yu-Chun Liao; Yu Age; Masaaki Yoshida; Ke-Hsuan Wang; Van-Huy Nguyen; Kun-Yi Andrew Lin; Chechia Hu (Journal of Environmental Chemical Engineering, 2025)

Preventing molecular catalyst aggregation in Z-scheme photocatalyst for unassisted CO2 reduction - Sharafat Ali; Sajjad Ali; Mohammad Z. Rahman; Lin Xu; Min Liu; Chuan Ke; Ahmed Ismail; Syedul H. Bakhtiar; Sher Ali; Muneerah Alomar; Zhenghua Wu; Li Zhong; et al. (Journal of Environmental Chemical Engineering, 2025)

Headspace single drop microextraction based digital image colorimetry and ICP-MS for dual-mode analysis of sulfide in condiments and beverage samples - Xiaoxiang Zhou; Chunhui Wu; Yang Zuo; Nuo Chen; Xiaojie Lin; Yi Zhang; Ke Huang; Xiaoli Xiong; Huimin Yu (Food Chemistry, 2025)

CHI–GSE–Nano-ZnO coating delays grape postharvest deterioration by inhibiting excess ROS via MYB714-pSTS484-mediated resveratrol biosynthesis - Yun-Lu Song; Jia-Lin Xing; Charles Ampomah-Dwamena; Shuai-Hui Ma; Mao-Song Pei; Han-Li Liu; Rui-Ping Feng; Yong-Ke Wu; Tong-Lu Wei; Hai-Nan Liu; Da-Long Guo (Food Bioscience, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Long-term effects of the hydrophilic and electrophilic modified magnetic carriers on partial nitrification at low temperatures: Enhancing nitrite supply by stimulating major enzyme gene expression - Fang Man; Yi Xue; Yuexin Yu; Chengyu Gu; Sijia Ma; Yuan Lin; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

Fire performance and post-fire residual behavior of insulated CFRP shear-strengthened RC beams: An experimental and numerical study - Wan-Yang Gao; Jun-Cong Lin; Ke-Xu Hu; Jian Yang (Engineering Structures, 2025)

Covalently integrated COF-hydrogel with self-adaptive Janus interface for high-efficiency solar desalination - Zheng Lin; Jiajie Xu; Jiang Li; Yirong Deng; Linhua Jiang; Ke Xiao (Chemical Engineering Journal, 2025)

Synergistic modification of coal by coupled scCO2 and engineering chemical reagents: Effects on pore structure and micromechanical properties - Ke Li; Yuchen Liu; Chuanjie Zhu; Sheng Qian; Yongshuai Lai; Xuanye Fan; Baiquan Lin (Chemical Engineering Journal, 2025)

Enhancing polymorphic purity by inducing specific pre-assembled dimer and reducing template particle size - Ke Zhang; Huina Liu; Yan Miao; Zezhi Lin; Liqin Hu; Yingran Duan; Yuan Gao; Jianjun Zhang; Yuanfeng Wei; Shuai Qian (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Triple-pronged strategy: A theranostic hydrogel platform with near-infrared chemiluminescence imaging-guided sonodynamic therapy for bacterial-infected wound healing - Jiaxin Yang; Kaijia Lin; Ke Xu; Liping Zhang; Qian Zhang; Gelin Xu; Yachao Wang; Haixing Feng; Yayun Xu; Yanqin Fan; Ziwei Wang; Zihan Wu; et al. (Chemical Engineering Journal, 2025)

Photoactivation assisted efficient triplet exciton filling for daylight-visible ultra-bright long lived room temperature phosphorescence - Zhaorun Tang; Lin Ding; Jiyang Long; Zhihao Guan; Xianwen Ke; Ruyi Wei; Xinghai Liu (Chemical Engineering Journal, 2025)

Sacrificial bond-enabled mechanically robust, stretchable ionic hydrogels for high-performance wearable sensors - Sheng-Lin Qiao; Xiao-Chun Yang; Xiao-Xue Wang; Shou-Shan Yu; Xue-Gang Yu; Ke-Zheng Chen (Chemical Engineering Journal, 2025)

Reconciling volume- and mass-based hygroscopicity parameters: Insights from coupled H-TDMA–APM measurements - Ta-Chih Hsiao; Ke-Ching Chen; Jun-Fa Ye; Si-Chee Tsay; Neng-Huei Lin (Atmospheric Environment, 2025)

TAX1BP1 regulates the apoptosis of renal tubular epithelial cells in ischemia/reperfusion injury via the NF-kB/PMAIP1 signaling pathway - Zhifen Wu; Wei Tan; Chunxuan Wang; Lirong Lin; En Tian; Bengang Huo; Luquan Zheng; Xujia Yang; Ke Li; Jurong Yang (Inflammation Research, 2025)

Gut microbiome-targeted therapeutics for chronic kidney disease: comparative efficacy of probiotic and microbial preparations - Yi-Ke Li; Wen-Ru Li; Huan Ren; Chen-Lin Xiao; Zhen Guo; Jian-Quan Luo (Inflammopharmacology, 2025)

Aerococcus christensenii: an emerging pathogen associated with infections and bacteremia in pregnancy—genomic insights and pathogenicity evaluation - Yugui Lin; Jialin He; Qiaoliang Zhang; Yanfen Li; Jialong Ke; Chunxiu Lin; Bingyan Yao; Chilun Zhang; Nan Tan (Functional & Integrative Genomics, 2025)

Integrative analysis identifies FERMT3 as a key regulator of metabolic reprogramming in keloid scarring and metabolic syndrome - Qian Lin; Beichen Cai; Feng Dong; Ruonan Ke; Xiuying Shan; Xuejun Ni; Lu Chen; Chuanshu Cai; Biao Wang (Functional & Integrative Genomics, 2025)

Functional Analysis of the mstn1 Gene and Its Transcriptional Regulation by Mef2 Factors in Yellowfin Seabream, Acanthopagrus latus (Hottuyn, 1782) - Hong-Xi He; Ke-Cheng Zhu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Lin Xian; Teng-Fei Zhu; Dian-Chang Zhang; Min Yang (Fish Physiology and Biochemistry, 2025)

Modulation of growth, gut-liver axis, and antioxidant defense by Bacillus tequilensis (GCB-3) in grass carp (Ctenopharyngodon idella) under high-carbohydrate diet: Insights into health enhancement and oxidative stress mitigation - Xin Wang; Dongming Zhang; Xinping Zhang; Xinyu Lei; Dan Jiang; Lili Lin; Wenli Zhu; Sibu Wang; Quan Huang; Yuxin Li; Yu-ke Chen; Zhixin Guo (Animal Feed Science and Technology, 2025)

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

Simplified theoretical analyses of lagging Darcy flow and land subsidence in a groundwater pumping system of three horizontal layers: An elastic thin plate approach - Jun-Hong Lin; Chih-Yu Liu; Chien-Chung Ke; Ying-Fan Lin (Advances in Water Resources, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

Experimental Study on Seabed Stability Around an Offshore Pipeline Under Waves and Currents: Local Scour and Pore-Water Pressure - Mengxiao Li; Dong-Sheng Jeng; Lin Cui; Zuodong Liang; Zheng Wang; Dajun Liu; Dayu Chang; Ke Sun (Journal of Marine Science and Engineering, 2025)
Offshore pipelines are commonly used for the transportation of oil and gas from offshore to near-shore facilities in the oil and gas industry. In ocean environments, the wave- and current- induced pore-water pressure within the seabed, and the associated seabed liquefaction and local scour around pipelines, are widely recognised as among the key factors in the design of offshore pipelines. In this paper, a series of wave flume experiments were carried out on the three-dimensional (3D) scouring around a pipeline. In the experiment, in addition to the measurement of hydrodynamic characteristics and local scour, the pore-water pressure within a sandy seabed was measured. Both waves and currents were considered with different incident angles to the pipeline. This study focuses on the relationship between the variation in pore-water pressure and the development of the scouring process around the pipeline, as well as the evolution of the 3D scouring morphology near the pipeline. The experimental results show that the pore-water pressure exhibits significant changes (up to 12.5% of P0) in the beginning stage of the scouring process, especially in the area below the pipeline, where the influence of scouring on pore-water pressure is most obvious.

Low Genetic Diversity and Decreased Effective Population Sizes of Acropora hyacinthus Populations Inhabiting Inshore and Offshore Reefs in the South China Sea - Yijin Di; Lingyu Zheng; Jingzhao Ke; Yinyin Zhou; Shaoyang Mo; Xiangbo Liu; Jiquan Lin; Yuxiao Ren; Duanjie Huang; Rouwen Chen; Xiubao Li (Oceans, 2025)
Coral reefs, with their high biodiversity and ecological service functions, face significant threats due to climate change, overfishing, and pollution. The South China Sea (SCS) hosts rich coral biodiversity, particularly Acropora hyacinthus, a critical species for reef restoration. However, the region’s coral reefs are increasingly degraded, highlighting the urgent need for conservation efforts. In the present study, the genetic diversity and population structure of A. hyacinthus were examined based on two types of data: double-digest restriction-site-associated DNA (ddRAD) sequencing data and mitochondrial putative control region DNA (mtCR) sequences. Coral tissue samples were collected from 74 colonies inhabiting two inshore reefs (Sanya) and three offshore reefs (Xisha islands), and 748 single nucleotide polymorphisms (SNPs) and 74 mtCR sequences were obtained and utilized for downstream analysis. The results were consistent in analyses and did not cluster into two geographical groups for the inshore and offshore sites. Phylogenetic analysis showed that individuals of A. hyacinthus inhabiting the five detected sites were likely cryptic species HyaD. Furthermore, AMOVA and pairwise FST estimations based on both data types revealed no differentiation among five populations and between inshore and offshore reefs, which could be due to the reproductive mode of broadcast spawning for this species. However, a prevalent low level of genetic diversity was observed when compared with nearby Taiwan regions and Japan, and the geographic history results showed that the effective population size (Ne) had been decreasing for the past 300 years. Thus, we speculated that the populations of A. hyacinthus inhabiting the SCS lack the potential to cope with future climate change adequately, and multiple conservation measures should be implemented based on considering genetic diversity.

One-year observation of cloud condensation nuclei concentration in a coastal city in eastern China: Seasonal variations, wet deposition, and regional transport - Zihan Wang; Yishu Bian; Qing Duan; Honglei Wang; Zihao Wu; Yue Ke; Tianliang Zhao; Wen Lin (Science of The Total Environment, 2025)

Multi-stage hybrid damper: Experimental validation and application in monopile offshore wind turbines - Huanyang Zhang; Ke Ke; Xuhong Zhou; Michael C.H. Yam; Junren Wang; Ye Lin (Ocean Engineering, 2025)

Light-emitting diode-derived blue light overexposure accelerates corneal endothelial cell aging by inducing abnormal ROS accumulation - Zhaolin Liu; Yiran Yang; Ke Yan; Jieli Wu; Xiang Lin; Liying Tang; Qingjian Li; Caihong Huang; Jiaoyue Hu; Zuguo Liu (Journal of Photochemistry and Photobiology B: Biology, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Optimization of coagulation process and its influence on membrane fouling for Anaerobic-Anoxic-Oxic-Anoxic Membrane Bioreactor (A2OA-MBR) - Xiaoping Tan; Ke Kuang; Jie Li; Caijing Lai; Zebin Chen; Ziyuan Wang; Wei Song; Yi Wu; Dachao Lin; Xing Du (Journal of Environmental Sciences, 2025)

Isolation of largemouth bass virus (LMBV) and dominant immunogenic epitope screening of the major capsid protein of LMBV - Jie Leng; Ling-Yun Lin; Yun-Yao Tu; Cheng-Ke Zhu; Qun Lu; Ming-Ji Lv; Tao He; Jian-Yong Hu; Zhao-Fang Han; Song Zhu (Fish & Shellfish Immunology, 2025)

Insights into fate and mechanism of polychlorinated dibenzo-p-dioxins/furans (PCDD/Fs) during sequential washing-thermal treatment of incineration fly ash - Kailun Chen; Li Lin; Jinglin Li; Endian Hu; Jingwen Chang; Weikai Qin; Yuchen Gao; Ke Liu; Jianguo Jiang (Environmental Research, 2025)

Topography-engineered cobalt-based microparticles for biofilm-eradicating medical device disinfection: Overcoming antibacterial resistance through mechano-bactericidal action - Ke Cheng; Shan Sun; Wenhao Zheng; Heng Zhang; Henggang Wang; Shang Gao; Si Li; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Targeting cuproptosis by FDX1 in acetaminophen-induced liver injury - Yan Liu; Ying Yang; Baizhao Peng; Zhongyue Ou; Anna Zuo; Zihao Jiang; Chuanghai Wu; Hiu Yee Kwan; Ke Ma; Lin Yu; Xiaoshan Zhao (Chemico-Biological Interactions, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

Paenibacillus wuxiensis sp. nov., a Novel Bacterium Capable of Producing Indole-3-Acetic Acid (IAA) and Inhibiting Rhizoctonia solani Kühn Isolated from Agricultural Soil - Cansheng Yuan; Luyao Ruan; Ying Yang; Lin Wang; Zhuang Ke; Jian He (Current Microbiology, 2025)

Site-selective hydroxyl functionalization: A dual-functional strategy for fabricating porous cellulose molecularly imprinted fiber for in vivo piperacillin sodium analysis - Deng Li; Min Wang; Zhou Li; Jia Zeng; Yingxi Zhu; Jiahao Lin; Zuojin Ao; Famin Ke; Kailian Zhang; Die Gao; Dandan Wang (Analytica Chimica Acta, 2025)

Comparative analysis of feed efficiency in Pacific abalone and its hybrid under varied environmental conditions - Wenchao Yu; Ziheng Yin; Yuehan Yan; Lin Cong; Miaoqin Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture International, 2025)

Dynamic in situ counting of farmed Holothurians based on improved YOLOv8s-ByteTrack - Ke-Xin Liu; Fang Wang; Sheng-Cheng Hong; Jun-Yi Wang; Xin-Yu Zheng; Yuan-Shan Lin (Aquaculture International, 2025)

Vitamin E alleviates ammonia‑nitrogen and hypoxia co-exposure-induced intestinal damage in grass carp (Ctenopharyngodon idella) by modulating mitochondrial function, cellular autophagy and apoptosis - Rui Su; Ke Yao; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Pei Wu (Aquaculture, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Quaternary paleogeographic reconstruction of the Qaidam Basin, northern Tibetan Plateau - Xue Ke; Zongyan Zhang; Taizhong Song; Wenjun Yang; Jing Li; Feng Chen; Jinming Zhang; Xiaojin Zhang; Bowen Song; Qixiang Lin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Impact of agricultural machinery purchase subsidies on the sustainable and intensive utilization of cultivated land: A perspective on agricultural machinery socialization services - Yajuan Zhou; Lijie He; Xinli Ke; Ershen Zhang; Jinwei Zhu; Aiwen Lin (Journal of Rural Studies, 2025)

Synthesis of novel thiol-functionalized halloysite nanotube/ organophyllosilicate composite for efficient removal of aqueous U(VI) - Edward Opong Acheampong; Ke Wang; Haoming Tang; Sen Lin; Shiyong Sun (Journal of Environmental Chemical Engineering, 2025)

Process and mechanism of low-temperature molten salt roasting conversion of beryl ore: Towards low-energy-consumption beryllium smelting - Lin Yu; Xiaobo Min; Hui Xu; Yunyan Wang; Yulin Zhou; Zhou Liao; Yun Li; Zhiyan Zeng; Yibin Xie; Cong Peng; Yong Ke (Journal of Environmental Chemical Engineering, 2025)

Insight into the adsorption of low-concentration ammonium nitrogen on zinc-modified montmorillonite: Performance, modelling and mechanisms - Lin Wei; Jianyu Kong; Tianqiu Hong; Yuefei Zhou; Qiang Zhang; Junjie Ji; Xiaoke Ding; Endi Wang; Ke Xu (Journal of Environmental Chemical Engineering, 2025)

Tropical circulation shifts and regional climate impacts: Comparing mid-Piacenzian warmth and future warming (SSP2–4.5) - Ke Zhang; Yong Sun; Yuheng Jiang; Huiwen Guo; Jiayi Lin; Jie Chen; Xin Wang (Global and Planetary Change, 2025)

Fermentation kinetics, physicochemical properties, and antioxidant activity of Fuji apple cider fermented with different yeast strains - Xinyan Peng; Yunying Li; Nan Li; Qian Liu; Lin Zhou; Ke Zhao (Food Research International, 2025)

Sensitive detection of phthalates in Chinese Baijiu by online in-tube SPME-HPLC-DAD based on carbonized COF-coated carbon fibers - Yaming Sun; Baoen Su; Ke Zhang; Yuhong Lin; Bing Wang; Min Sun (Food Chemistry, 2025)

Designation of multi-color and durable antimicrobial lyocell fiber by constructing various structural silver nanoparticles - Xiaofeng Wang; Wanjin Hu; Yonghao Zhou; Mengyao Cai; Xuelin Wang; Ke Lin; Chunhua Zhang; Sijie Zhou; Heng Pan; Lixin Du; Liangjun Xia (Chemical Engineering Journal, 2025)

All-in-one photothermal hydrogel: Graphene@CuS with microchannels for fast evaporation, water purification, and heat reuse - Lin Lin; Jin Yang; Danyi Li; Siyi Xu; Fangzheng Wang; Xiaoshan Zhou; Yongan Ke; Linfan Li; Jihao Li (Chemical Engineering Journal, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Mechanical robust and recyclable PLA-based polyurethane elastomers for flexible electronics - Chen-Yu Wang; Ke Ma; Xiao-Xue Wang; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2025)

Microbial succession dynamics drive mesh-structured microfibers transformation in estuarine wetlands: Metagenomic and metabolomic evidence of oxidative stress adaptation - Yiming Lei; Lujian Lin; Yue Ke; Xiaoting Zhang; Hanyi Li; Guanglong Zhang; Jingchun Liu; Haoliang Lu; Chongling Yan; Hualong Hong (Chemical Engineering Journal, 2025)

Hedgehog-nanovesicles redox probe based “explosive” signal amplification biosensing platform for Alzheimer's disease early diagnosis - Yuanzhe Li; Wenchen Gu; Yaling Li; Zheng Zhao; Ting Liu; Peifeng Ke; Haibiao Lin; Qiqin Wang; Xianzhang Huang; Qiaoxuan Zhang (Chemical Engineering Journal, 2025)

Synergistic band structure tailoring and texturing enhance cooling-power generation Bifunctionality in Bi0.4Sb1.6Te3 - Lin Liao; Jingjing Cui; Keke Liu; Xili Wen; Xingyan Dong; Ming Liu; Ding Luo; Yu-Ke Zhu; Xianli Su; Jiehe Sui; Jinsong Wu; Xinfeng Tang (Chemical Engineering Journal, 2025)

A 3D-printed chitosan-based pH-responsive dual functional scaffold for osteomyelitis: synergistic antibacterial and osteogenic treatment - Mingyue Lin; Yijing Stehle; Li Chen; Mao Yang; Ke Zeng; Chenxin Wang; Rui Zhang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Yubao Li; et al. (Carbohydrate Polymers, 2025)

Organotins as inhibitors targeting human and rat steroid 5α-reductase 1: structure-activity relationship and docking analysis - Shufang Qi; Rong Cui; Wanyu Li; Jin Yang; Ke Zheng; Shaowei Wang; Ren-Shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2025)

Low-intensity pulsed ultrasound enhances delivery of 30 nm Q10 for improving mental and memory disorder in APP/PS1 mice - Qi Luo; Xuanjie Ye; Jinan Xu; Zihui Sun; Panpan Wang; Haishu Chen; Tingting Gao; Qiangfeng Deng; Ziwen Wang; Qin Wang; Xiaoxiao Chen; Zhuowen Zhao; et al. (Drug Delivery and Translational Research, 2025)

Optimizing cropland management to mitigate climate-induced nitrogen leakage risk in Chinese ecosystems - Di Zhao; Weijie Lin; Ke Yu; Zelin Huang; Chaopu Ti; Xiaoyuan Yan; Yongqiu Xia (Agricultural Systems, 2025)

Fixed‐period strategy for maintaining the absolute configuration of large‐scale LEO constellations - Xiaoyu Zuo; Ke Li; Lin Chen; Xingji He; Ming Xu (Advances in Space Research, 2025)

Antimony induces mitochondria-dependent and ER stress-triggered apoptosis via the oxidative stress-activated JNK signaling pathway in pancreatic islet β-cells - Ken-An Lin; Chin-Chuan Su; Shing-Hwa Liu; Kuan-I. Lee; Kai-Min Fang; Chih-Hsin Tang; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Chun-Fa Huang; Ya-Wen Chen; Ching-Yao Yang (Toxicology, 2025)

Empirical analysis of two core questions on urban street vitality formation mechanism using energy efficiency metrics within the dissipative theory framework - Shiping Lin; Jilong Li; Niuniu Kong; Yilin Ke; Jiacheng Chen; Jie Zeng; Jiawen Wang; Ke Ai (Sustainable Cities and Society, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Seven previously undescribed steroidal alkaloids from the fruit of Solanum nigrum L. and their biological activities - Liang-Yu Liu; Qing Peng; Yu-Ke Yang; Tong Wu; Li-Xian Chen; Li Lin (Phytochemistry, 2025)

FTUVE based global fast terminal backstepping sliding mode control for dynamic positioning ships - Lin Li; Chen Wang; Ke Lu; Zhengkang Wu; Fang Deng (Ocean Engineering, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Microglia-derived extracellular vesicles mediate fine particulate matter-induced Alzheimer's disease-like behaviors through the miR-34a-5p/DUSP10/p-p38 MAPK pathway - Ling Wang; Yi Lin; Ziyi Yang; Ke Zhang; Hongyang Gong; Yaopeng Zheng; Binquan Wang; Xiaoyan Zhang; Mingkuan Sun (Journal of Hazardous Materials, 2025)

Metabolomic profiling unveils biochemical dynamics in spontaneously fermented grape leaf by-products: towards sustainable agricultural waste valorization - Jia-Lin Xing; Yun-Lu Song; Yan-Ge Li; Lu Yang; Ke-Ying Duan; Ding-Ding Zuo; Jing Zhang; Hai-Nan Liu; Tong-Lu Wei; Mao-Song Pei; Da-Long Guo (Food Bioscience, 2025)

Constructing a synthetic microbial community by analyzing the microorganisms responsible for the core flavor substances of Zhenjiang aromatic vinegar and their interaction - Yongjian Yu; Jiaxin Liu; Yuanyuan Zhu; Ke Wang; Yuqin Wang; Dong Han; Zhen Yu; Siyuan Cheng; Nan Zhang; Shuaiwei Dou; Shiyuan Lin; Ziyi Kang (Food Bioscience, 2025)

Algae biofilm produces less microbe-derived dissolved organic nitrogen under higher C/N ratio conditions - Yuexin Yu; Yuan Lin; Chengyu Gu; Fang Man; Sijia Ma; Yi Xue; Hongqiang Ren; Ke Xu (Environmental Research, 2025)

Wear theory and shear strength calculation method of cold-formed steel stud-to-oriented-strand-board fasteners - Wang Xingxing; Wang Wei; Zhang Yaozhao; Lin Xiaodong; Sun Ke (Engineering Structures, 2025)

Particle size distribution (PSD) of mine waste dump via unmanned aerial vehicle (UAV) image recognition and sieving - Han Ke; Zi Han Lin; Xiao Fei Wei; Bing Zhou; Tian Shou Hu; Shuai Zhang; Jie Hu; Chen Sheng Zhang (Engineering Geology, 2025)

Portable miRNA profiling of sepsis-associated exosomes via a novel DNA molecular lock-mediated nanobiosensor - Wei Xie; Shu Jia; Rongjun Yu; Jianjiang Xue; Shulian Bai; Chenxing Wang; Gang Tian; Qiongyuan Zhang; Xiao Gui; Lilin Wang; Silin Chen; Ke Lin; et al. (Chemical Engineering Journal, 2025)

Synergistic enhancement of wetland purification performance by introducing intermittent aeration and zero-valent iron under chilling stress - Lin-Yuan Wu; Bing-Xu Guo; Ke-Jia Zhang; Jun-Yu Ai; Wei-Yi Shi; Qing-Yuan Tian; Wen-Huai Wang; Jun-Feng Li (Chemical Engineering Journal, 2025)

Ceramifiable flame-retardant silicone rubber foam for long-term fire resistance and thermal insulating - Tao Lin; Ke Shang; Gui-De Lin; Jun-Sheng Wang; Jin-Jun Yang (Chemical Engineering Journal, 2025)

Linkage site regulation on photocatalytic hydrogen evolution performance of naphthalene-based conjugated polymers - Xufeng Ji; Nan Chen; Jinlian Yuan; Ao Sun; Lin Zhou; Xing Ding; Yi Yang; Bo Chai; Deng Ding; Xiaohu Zhang; Ke Dai; Hao Chen (Chemical Engineering Journal, 2025)

Complete nitrogen removal via novel nitrite-absent anodic anammox process with granular sludge in titanium anode microbial electrolysis cells - Liang Zhu; Jingwei Ma; Zhanhang Wang; Ying Han; Long Chen; Hui Sun; Qiulai He; Lin Deng; Zhou Shi; Shuizhou Ke (Chemical Engineering Journal, 2025)

An approach and mechanistic insights of coating-type binders for 4.6 V-LiCoO2 cathode of lithium-ion battery - Li Deng; Yu-Xi Luo; Zhen Wang; Jin-Xia Lin; Jun-Ke Liu; Kun-Gui Zheng; Gao-Yang Bai; Zu-Wei Yin; Yao Zhou; Jun-Tao Li (Chemical Engineering Journal, 2025)

Combined space cooling/heating and domestic hot water supply driven by data center waste heat: Complementary energy conservation, economic capacity optimization and generic analysis framework - Jun Bai; Xiaohui Wu; Xiaoyuan Chen; Zhiying Zhang; Lin Fu; Chunxiao Zhao; Ke Qing; Qiaoyu Luo; Shirong Gong; Boyang Shen (Building and Environment, 2025)

Bio-organic fertilizer mitigates Orobanche cumana parasitism by regulating sunflower transcriptomes and rhizosphere microbial community - Tengqi Xu; Jiao Xi; Yufan Wang; Yiqiong Zhang; Jihong Ke; Xiaomin Wei; Yanbing Lin (Plant and Soil, 2025)

Aurantibrevibacter litoralis gen. nov. sp. nov. a Novel Member in the Family Flavobacteriaceae Isolated from Sediment of Tidal Flat Located in Ningbo, China - Yun-Fei Cao; Dong-Yan He; Yu-Ruo Wang; Ke Cao; Yang Li; Jia-Wei Gao; Xing-Cheng Wang; Lin Xu; Cong Sun; Xiao-Yun Yu (Current Microbiology, 2025)

Morphological and Transcriptomic Response Mediated by Heat Stress in Pleurotus Pulmonarius - Zhenghui Lu; Binrong Ke; Hongyi Lin; Bin Yuan; Lina Ke; Meiyuan Chen; Yuanping Lu (Current Microbiology, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Transcriptomic and Metabolomic Analyses Provide Insights into Cryptocaryon irritans Resistance in Golden Pompano (Trachinotus ovatus) - Bo Liu; Bao-Suo Liu; Jing-Wen Yang; Hua-Yang Guo; Nan Zhang; Teng-Fei Zhu; Lin Xian; Ke-Cheng Zhu; Dian-Chang Zhang (Fishes, 2025)
Golden pompano (Trachinotus ovatus) is an economically important fish species along China’s southern coast. However, infections by Cryptocaryon irritans severely constrain the healthy and sustainable development of the aquaculture industry. To investigate the genetic basis of resistance to this parasite in golden pompano, this study employed transcriptomic and metabolomic analyses to compare differences between susceptible (ES) and resistant (RS) groups following C. irritans challenge. Transcriptome analysis identified 2031 differentially expressed genes (DEGs) between EST and RST groups, comprising 1004 up-regulated and 1027 down-regulated genes. Gene Ontology (GO) functional annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment revealed that these DEGs were primarily enriched in lipid metabolism and amino acid metabolism pathways. Untargeted metabolomics detected 461 significantly differentially abundant metabolites (295 up-regulated, 166 down-regulated), confirming pronounced metabolic differences between ES and RS groups, particularly in lipid and amino acid metabolism. Further, KEGG enrichment highlighted steroid hormone biosynthesis, α-linolenic acid metabolism, and arachidonic acid metabolism as the most significantly altered pathways upon infection. This integrated transcriptomic and metabolomic study reveals substantial differences in gene expression and metabolite profiles between susceptible and resistant golden pompano in response to C. irritans. These changes predominantly involve lipid metabolism and amino acid metabolism, suggesting that these processes are critical in determining host resistance/susceptibility.

Seismic scattered wave direct imaging in shallow underground space with undulating surface - Ke Shi; Feng Xu; Zong-ling Yan; He-jun Chai; Xue-ming Jia; Xing-lin Lu; Xian-xin Liu; You-ping Mao (Applied Geophysics, 2025)

Emergence and traceability of Salmonella enterica serotype Mbandaka harboring blaOXA-10 from chickens in China - Ke Wu; Jian Yang; Tiejun Zhang; Jing Zuo; Heng Lin; Juan Wang; Anyun Zhang; Changwei Lei; Hongning Wang (Veterinary Microbiology, 2025)

Weather effects on highway travel volume: Electric vs. Fuel vehicles - Qinyu Cui; Chaoshuo Huang; Kaihan Zhang; Chao Gao; Tianshun Gu; Entong Ke; Peiqun Lin (Transportation Research Part D: Transport and Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Large-scale optimized deployment of bioenergy with carbon capture and storage in China - Wenhao Lin; Lei Gao; Zhaoxia Guo; Yucheng Dong; Yinfeng Xu; Enayat A. Moallemi; Gang Kou; Meiqian Chen; Ke Li; Weijun Xu; Raymundo Marcos-Martinez; Brett A. Bryan (Science Bulletin, 2025)

Systemic assessment of fenpropathrin and 3-phenoxybenzoic acid in soil: adsorption, desorption, and effects on soil enzyme and microbial community - Ping Zhang; Xiaojiang Ke; Mengting Zhang; Cancan Yang; Yiyun Cai; Lin He (Pesticide Biochemistry and Physiology, 2025)

Evolutionary dynamics and codon bias analysis of canine circovirus: Insights into global spread and host adaptability - Gen Li; Rongqi Liu; Yongyi Chen; Huixian Liang; Yinyi Liang; Xin Li; Yankun Ke; Bowen Lin; Jianfeng Zhong; Xiaofeng Guo; Jun Che; Jun Luo (Molecular Phylogenetics and Evolution, 2025)

A critical need to control thallium contamination in aquatic ecosystem for the age of low carbon - Juan Liu; Wenhuan Yuan; Yu Shi; Yanyi Liu; Pei Li; Wanpeng Chen; Xuan Zeng; Ying Li; Ke Lin; Yinyin Lu; Haiyao Hu; Jin Wang (Journal of Hazardous Materials, 2025)

ε-MnO2 with oxygen defect Engineering: Modulating local electron density to enhance superoxide radical generation via peroxymonosulfate activation - Xiaoxi Guo; Zhuoyan Liu; Hongyang Wu; Chang Liu; Lin Shen; Ke Xu; Ji Wu; Yijun Cao (Journal of Cleaner Production, 2025)

Efficient three-dimensional electrochemical degradation of alizarin red by CeO2−MnO2/NF particle electrode synergized with ozone - Ke Hu; Fangyuan Zhao; Faqin Dong; Xingyu Zhang; Lin Zhou; Ming Guo (Journal of Environmental Sciences, 2025)

Antimicrobial properties and preservation potential of Allium sativum L-derived extracellular vesicle-like particles for food applications - Chenqi Zhu; Xiaoxiao Ke; Yi Gu; Chunmeng Wang; Shangyang Lin; Yijie Qian; Jiale Cheng; Yan Chen; Liu Xu; Zhipeng Chen (Food Chemistry, 2025)

Air classification efficiency evaluation of landfilled municipal solid waste using experiments and a probabilistic method - Lin Feng Yu; Yu Qi Jin; Miao Xin Yuan; Fei Zhang; Jie Hu; Ji Wu Lan; Yu Fan Wei; Yun Min Chen; Han Ke (Waste Management, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Fire ant-inspired bone repair breakthrough: Self-assembly strategy of microspheres driven by physical hydrogen bonding and hydrophobic interactions - Rui Zhang; Yijing Stehle; Li Chen; Ke Zeng; Mingyue Lin; Chenxin Wang; Huanshuo Zhang; Jiehui Yang; Denglang Hu; Min Huang; Mao Yang; Yubao Li; et al. (Chemical Engineering Journal, 2025)

Suppressing the progression of bladder cancer using cyclovirobuxine D based on network pharmacology and bioinformatics approaches - Ke Gao; Hanbing Jiang; Chao Zhang; Lin Li; Yuhong Qi; Nan Yang; Xiaoshun Li; Yongshun Wang; Bin Wu; Qiuju Shao; Guojun Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploring exhaled volatile organic compounds as potential biomarkers in anti-MDA5 antibody-positive interstitial lung disease - Yuxuan Wang; Xuewen Wang; Luqin Yang; Ke Wang; Fengqin Zhang; Huihui Yue; Junqi Wang; Minhua Peng; Pengnan Fan; Xiangcheng Qiu; Han Zhang; Wei Lin; et al. (Molecular and Cellular Biochemistry, 2025)

Recent advances in 3D cell culture models in cancer drug development - Yae Sol Cha; Alvin Michaels; Janney Z. Wang; Yihe Niu; Yipeng Lin; Ling Zhu; Xue Zhu; Ke Wang; Michael Murray; Fanfan Zhou (Journal of Pharmaceutical Investigation, 2025)
Background In vitro cell culture models are widely used in cancer drug development. However, traditional two-dimensional (2D) models do not replicate the complex characteristics of the tumour microenvironment. Three-dimensional (3D) culture models have been used to prepare cell spheroids that are increasingly used in drug screening and evaluation due to their greater capacity to mimic tumour properties. Area covered This review discusses the methods used to generate 3D cell systems and their applications in cancer research. There are several methods used in the generation of 3D culture models, including forced floating and matrix-based methods. However, bioprinting technologies have emerged more recently as novel approaches to generate 3D culture models that can better mimic tumour physiology. 3D models are used to evaluate the activities of drugs in a wide variety of cancer types, although they have not yet been widely applied in the case of rarer cancers. Expert opinion 3D culture models have a number of desirable features that are advantageous in anti-cancer drug development. However, some methods of spheroid production have issues of inherent non-reproducibility and inconsistency, while bioprinting technology generally has more favourable features. Thus, newer optimised technologies will improve the physiochemical properties of spheroids, which may promote their application in cancer drug development.

Behavioral Responses of Migratory Fish to Environmental Cues: Evidence from the Heishui River - Jiawei Xu; Yilin Jiao; Shan-e-hyder Soomro; Xiaozhang Hu; Dongqing Li; Jianping Wang; Bingjun Liu; Chenyu Lin; Senfan Ke; Yujiao Wu; Xiaotao Shi (Fishes, 2025)
Hydropower infrastructure has profoundly altered riverine connectivity, posing challenges to the migratory behavior of aquatic species. This study examined the post-passage migration efficiency of Schizothorax wangchiachii in a regulated river system, focusing on upstream and downstream reaches of the Songxin Hydropower Station on the Heishui River, a tributary of the Jinsha River. We used radio-frequency identification (RFID) tagging to track individuals after fishway passage and coupled this with environmental monitoring data. A Cox proportional hazards model was applied to identify key abiotic drivers of migration success and to develop a predictive framework. The upstream success rate was notably low (15.6%), with a mean passage time of 438 h, while downstream success reached 81.1%, with an average of 142 h. Fish exhibited distinct diel migration patterns; upstream movements were largely nocturnal, whereas downstream migration mainly occurred during daylight. Water temperature (HR = 0.535, p = 0.028), discharge (HR = 0.801, p = 0.050), water level (HR = 0.922, p = 0.040), and diel timing (HR = 0.445, p = 0.088) emerged as significant factors shaping the upstream movement. Our findings highlight that fishways alone may not ensure functional connectivity restoration. Instead, coordinated habitat interventions in upstream tributaries, alongside improved passage infrastructure, are crucial. A combined telemetry and modeling approach offers valuable insights for river management in fragmented systems.

Genetic Diversity in Three Sinipercine Fishes Based on Mitochondrial D-Loop and COX1 Sequences - Minghui Lin; Xu-Fang Liang; Ke Lu; Ming Zeng; Junjie Gao; Yaqi Dou; Yulan Kuang; Qiwei Zhang (Fishes, 2025)
Mandarin fish (Siniperca chuatsi), golden mandarin fish (Siniperca scherzeri), and Coreoperca whiteheadi are three important aquaculture species in China facing several threats to their production. Genetic diversity was assessed by sequencing the mitochondrial D-loop and cox1 regions in 207 individuals across nine populations. The genetic diversity analysis, based on the concatenated sequences, revealed that the total haplotype diversity was high across all sinipercine fish populations. Population differentiation analysis revealed that most genetic variation was within populations: 74.5% in S. chuatsi (p

Robust titanium suboxide anodes doped by sintering enhance PFOS degradation in water - Yufei Sui; Xi Zhu; Lei Li; Yaye Wang; Gengyang Li; Shuping Dong; Yifei Wang; Hui Lin; Ke Li; Qingguo Huang (Chemosphere, 2025)

Stratified biofilm structure of MABR enabling efficient ammonia removal from aquaculture medicated bath wastewater - Bincheng Lin; Tanqiu Hu; Zhihao Xu; Youqing Ke; Lei Zhang; Junjian Zheng; Jinxing Ma (Water Research, 2025)

Whole-genome sequences revealed genomic diversity and selection signatures of Dermacentor silvarum in Shaanxi, China - Yi-yao Mou; Meng-ke Lin; Yu-ying Yang; Yu-kun Kang; Ya-qing Li; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Terpene and lignan glycosides from the leaves of Cyclocarya paliurus and their anti-inflammatory activity - Si-Yang Fang; Jia Liu; Chang-Jian Wu; Xing-Gui Zhang; Hui-Lin Dong; Dong-Jian Zhang; Can Hu; Jian Zhang; Ke Pan; Zhi-Qi Yin; Yan-Hua Qin; Lei Wang (Phytochemistry, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Unveiling in situ methylmercury production and degradation in aquaculture sediments: Transformation rates, functional genes and microbial methylators - Songzhang Li; Yanbin Li; Xiuqin Xie; Zhaohong Li; Ke Yuan; Xin Chen; Zhijia Ci; Li Lin; Ligang Hu; Yongguang Yin; Jianbo Shi; Tiangang Luan; et al. (Journal of Hazardous Materials, 2025)

Insight into carbonyl source based on improved source apportionment method: Alkene regulate secondary formation - Yulong Yan; Yueyuan Niu; Xiaolin Duan; Ke Yue; Jiaqi Dong; Chao Yang; Dongmei Hu; Yuhang Wang; Junjie Li; Lin Peng (Journal of Hazardous Materials, 2025)

Letter to the editor: Comments on “Microplastic polyethylene induced inner ear dysfunction in murine model” - Haonan Lin; Liming Shang; Lexin Wang; Ke Xu (Journal of Hazardous Materials, 2025)

Enhanced adsorption of neonicotinoids by MnCl₂ and H₃PO₄ co-modified corn stover biochar: Performance and mechanism analysis - Jun Tu; Qiuru Chen; Siyu Ke; Xiaohui Yi; Yiquan Qiu; Ziyi Lin; Shuxiang Yang; Xinzhi Wang; Xiaotong Bai; Mingzhi Huang (Journal of Environmental Chemical Engineering, 2025)

Maillard reaction products derived from xylose-phosphatidylethanolamine: Potential anti-oxidative substances from hot-pressed flaxseed oil - Yi-kang Zhang; Ke-yao Li; Yue Du; Lin Wang; Qian Xiong; Ning Zhang; Xin Yue; Jia-zi Chen; Martin J.T. Reaney; Yong Wang; Zi-zhe Cai (Food Chemistry, 2025)

Crack regulating by multi-level sensory structure towards personalized heath monitoring, human motion tracking, and robotic arm control - Huinan Wang; Huijuan Lin; Zhiyuan Zhang; Ke Chen; Yan Yan; Naidi Yang; Kun Rui; Jingwen Sun; Jixin Zhu (Chemical Engineering Journal, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Evolved size-specific dose estimates for patient-specific organ doses from chest CT scans based on hybrid patient size vectors - Wencheng Shao; Ke Yang; Lizhi Lou; Xin Lin; Liangyong Qu; Weihai Zhuo; Haikuan Liu (Physical and Engineering Sciences in Medicine, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Mechanical properties and failure modes of discontinuous jointed considering water softening effects - Siyu Chen; Hang Lin; Ke Ou; Xing Zhang; Chaoyi Yang (Earth Science Informatics, 2025)

Associated effects of blood metal(loid) exposure and impaired glucose metabolism in patients with gastric precancerous lesions or gastric cancer - Yuting Zhu; Xiao Lin; Tingting Wang; Sheng Wang; Wuqi Wang; Mengran Ke; Yan Zhu; Bowen Zhang; Princess Ofosuhemaa; Yalei Wang; Mingjun Hu; Wanshui Yang; et al. (BioMetals, 2025)

Volatile organic compounds emission characteristics and factors from stage-dependent combustion in typical biomass stoves in northern China: Field measurements and environmental implications - Ke Yue; Yulong Yan; Zhen Li; Yueyuan Niu; Jiaqi Dong; Yongqian Zhou; Junjie Li; Lin Peng (Environmental Pollution, 2025)

Deciphering the role of extracellular polymeric substances in the adsorption of perfluorooctanoic acid during sludge alkaline fermentation: Experimental study and molecular dynamics simulation - Chengyu Gu; Sijia Ma; Fang Man; Yuexin Yu; Yuan Lin; Yi Xue; Yanru Wang; Hongqiang Ren; Ke Xu (Chemical Engineering Journal, 2025)

CTCs driven metal ions@DNA-functional nanomachines switch enable one-pot liquid biopsy of lung cancer - Yue Wang; Chengyong Wu; Ziqiang Fan; Ke Huang; Zeliang Wei; Feng Lin; Yi Xie; Piaopiao Chen (Chemical Engineering Journal, 2025)

Further understanding the unique structure derived from interaction of soy proteins with acylated starch of various chain-length short-chain fatty acids - Sheng Ke; Anqi Wang; Peng Yu; Xuanyu Wang; Guandi Chen; Yanhong Lin; Chris Blanchard; Zhongkai Zhou; Guohua Zhao (Carbohydrate Polymers, 2025)

Regional differences and formation mechanisms of watershed territorial space patterns evolution: A case study of the critical areas in the Pearl River Basin - Shugao Lin; Pengcheng Wang; Peixin Zhu; Ke Huang; Rucheng Lu (Journal of Geographical Sciences, 2025)

Minor protopanaxadiol type sapogenins from the alkali hydrolysate of stems-leaves of Panax notoginseng - Cong-Cong Jing; Jing-Min Wang; Pei Wang; Lin Guo; Shu-Min Zhang; Ke Liu; Zhen-Yuan Li; Hua-Ying Fan; Ze-Ping Xie (Natural Product Research, 2025)

Disinfection efficacy of peroxyacetic acid against bacterial spores - Le Yuan; Weishi Lin; Yue Cao; Junping Lv; Siqi Chao; Yulei Liu; Jun Ma; Jinpeng Guo; Yuehua Ke; Lu Wang; Jinfeng Tie (Journal of Hazardous Materials, 2025)

Structural controls on the magma emplacement and distribution of sulfide orebodies in the Kalatongke Cu-Ni sulfide district, NW China - Xue-Hai Wang; Ke-Zhang Qin; Xing-Wang Xu; Dong-Mei Tang; Ya-Jing Mao; Lei Zhang; Min-Qiang Zhang; Fang-Lin Yuan; Yi Li (Journal of Asian Earth Sciences, 2025)

An electron delocalization with n-π∗ transitions of graphitic carbon nitride photocatalyst for visible-light-driven water decontamination - Yan Ke; Mingzhu Yuan; Xinglong Li; Yuan Liu; Yangyang Li; Yuanxu Liu; Xiangang Lin; Qinghua Liu; Yupeng Yuan (Environmental Research, 2025)

A formula of quantile of extreme wind pressure coefficient to estimate wind load with various mean recurrence intervals - Lin Da; Qingshan Yang; Min Liu; Ke Zhou; Chuang Li (Engineering Structures, 2025)

Interpretable data-driven urban building energy modeling considering inter-building effect - Deqing Lin; Xiaodong Xu; Ke Liu; Tingjin Wu; Xi Wang; Ran Zhang (Building and Environment, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Differences in Pathogenetic Mechanism Between Tibetan and Han High-Altitude Polycythemia Based on a Whole Genome-Wide Association Study - Zhuoma Basang; Shixuan Zhang; Xianwei Ke; Zhuoma Duoji; La Yang; Danzeng Qiangba; Yang De; Deji Gesang; Zixin Hu; Yanyun Ma; Meng Hao; Ruidong Fan; et al. (Phenomics, 2025)

Terpenoids with Antiangiogenic Activity from Formosan Soft Coral Caementabunda hypotentaculata - Hsin Huang; Chen-Yu Yang; Shih-Wei Wang; Limbadri Salendra; Shu-Rong Chen; Tzi-Yi Ke; Yu-Liang Yang; Yu-Chi Lin; Yuan-Bin Cheng (Marine Biotechnology, 2025)

Changes in fertility and microbial communities of red soil and their contribution to crop yield following long-term different fertilization - Haoran Mao; Ke Leng; Xinyi Chen; Jie Zhang; Kailou Liu; Yongxin Lin; Xingjia Xiang; Jia Liu (Journal of Soils and Sediments, 2025)

Molecular characterization of a novel mycovirus from Curvularia lunata in China - Bin Ke; Xiaohan Mo; Mengting Wu; Lin Wang; Ru Peng; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Fei Yan; Hongying Zheng (Archives of Virology, 2025)

Gut microbiome composition likely affects the growth of Trachinotus ovatus by influencing the host's metabolism - Chen-Xu Wu; Bao-Suo Liu; Hua-Yang Guo; Teng-Fei Zhu; Lin Xian; Nan Zhang; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture International, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

Extensive cytonuclear discordance revealed by phylogenomic analyses suggests complex evolutionary history in the holly genus Ilex (Aquifoliaceae) - Ke-Wang Xu; Yi Yang; Hong Chen; Chen-Xue Lin; Lei Jiang; Zhong-Long Guo; Meng Li; Ming-Zhuo Hao; Kai-Kai Meng (Molecular Phylogenetics and Evolution, 2025)

New insights into quercetin's attenuation of TBBPA-induced injury to MCEC cells: Involvement of the p38/NF-κB pathway and pyroptosis - Ke Li; Kun Wang; Tong Xu; Chencong Lyu; Xuejiao Yang; Hongjin Lin; Shiwen Xu (Journal of Environmental Management, 2025)

Evaluating complementaries among urban water, energy, infrastructure, and social Sustainable Development Goals in China - Ke Yu; Yifan Song; Jin Lin; Shen Qu (Journal of Environmental Sciences, 2025)

Synergistic inactivation effect of ultrasound and nano-emulsified basil essential oil on the metabolic responses of Salmonella on sprouts - Zifei Liu; Peiwen Sun; Xichen He; Dingsong Lin; Lijing Ke; Chao Shi; Hongshun Yang; Lingchi Deng; Zejia Lin; Lin Chen (International Journal of Food Microbiology, 2025)

Mercury (II) adsorption and gaseous mercury re-emission inhibition from seawater flue gas desulfurization (SFGD) wastewater by Fe-Cu bimetallic modified activated carbon - Lushi Sun; Gan Wan; Ke Tang; Linlin Xu; Li Lin (Fuel, 2025)

Integrating ICP-MS and Chemometrics for Profiling Inorganic Elements in Lianhua Qingwen Capsules and Evaluating Health Risk - Shuya Li; Ke Yin; Yiwu Wang; Lihong Tan; Jianing Zhao; Shuxiang Pan; Lin Yang; Dan He (Biological Trace Element Research, 2025)

Detecting monogenic disorders in utero non-invasively based on fetal nucleated red blood cells highly-purified by multi-functional magnetic nanoparticles - Lin Cheng; Chun Feng; Ke Wu; Zixiang Wang; Wentao Zhu; Ting Geng; Naiqi Li; Jiawei Kang; Jie Duan; Jin Li; Yuqi Shao; Saisai Yang; et al. (Analytica Chimica Acta, 2025)

Social conditions alter the growth, metabolic rate, behavioral traits, and food-shelter preferences in the juvenile qingbo Spinibarbus sinensis - Yu-Lin Zhang; Wen-Qian Zhou; Shi-Jian Fu; Lauren E. Nadler; Shaun S. Killen; Ke-Ying Zhou; Shi-Long Zheng; Cheng Fu (Behavioral Ecology and Sociobiology, 2025)

Proteomic analysis of global protein acetylation in response to WSSV infection in a crustacean Cherax quadricarinatus - Ling-Ke Liu; Lu-Lu Yang; Qi Jiang; Wen-Lin Wu; Hai-Peng Liu (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Synergistic atmospheric influence on the co-pyrolysis of antibiotic sludge and waste bicycle tires: Optimal drivers, products, and pathways - Dajie Jia; Tao Chen; Liangzhon Li; Jingyong Liu; Zhibin Chen; Sen Lin; Guopeng Ke; Fatih Evrendilek; Wuming Xie; Wenxiao Huang; Chenyu Yang (Journal of Hazardous Materials, 2025)

Dynamic evolution and differential enrichment of deep coalbed methane: A case study in Qinshui Basin - Xiongxiong Yang; Shuheng Tang; Zhaodong Xi; Songhang Zhang; Qian Zhang; Ke Zhang; Donglin Lin; Jing Wang (International Journal of Coal Geology, 2025)

A comprehensive safety assessment of a novel starter Weissella confusa M1 combining with whole-genome sequencing - Meng Tian; Hailing Wang; Yue Li; Jialin Wang; Dayong Ren; Ke Lin (Food Research International, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

A comprehensive analysis-based study of Di-(2-ethylhexyl) phthalate (DEHP)—Environmental explanation of bladder cancer progression - Fei Lin; Wen-Cai Zheng; Zhi-Bin Ke; Dong-Ning Chen; Yu-Ting Xue; Yun-Zhi Lin; Xiao-Dong Li; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Ning Xu (Environmental Pollution, 2025)

Grid shielding of interphase hybrids via spatial charge separation for regulating interfacial Zn redox kinetics - Ke Chen; Kun Rui; Wenhao Si; Huinan Wang; Cong Zhao; Yan Yan; Huijuan Lin; Jixin Zhu (Chemical Engineering Journal, 2025)

Mineral, molecular composition and ecosystem type jointly determine the stability of soil organic carbon on the Qinghai-Tibetan Plateau - Jun Gu; Dongxue Li; Fei Yang; Xiao-Dong Song; Ke-Yang Gong; Gan-Lin Zhang (CATENA, 2025)

Three-dimensional Finite-Element Forward Modeling and Response Characteristic Analysis of Multifrequency Electromagnetic - Jun Zhou; Ke He; Zhi-yan Liu; Shuai Ruan; Hong-lin Ran (Applied Geophysics, 2025)

Neutrophil Membrane Nanovesicles Alleviate the Renal Function Indicators in Acute Kidney Injury Caused by Septic Rats - Junhao Pan; Feifei Shao; Xiaorong Xiao; Xin Ke; Zhihui Guan; Hui Lin; Qingqing Yan; Xinyao Xiang; Jinming Luo (Cell Biochemistry and Biophysics, 2025)

Deciphering Trachinotus ovatus resistance to Streptococcus agalactiae:GWAS identification of key SNPs and candidate genes - Yi-Yao Sun; Jie Gao; Bao-Suo Liu; Nan Zhang; Hua-Yang Guo; Ke-Cheng Zhu; Lin Xian; Dian-Chang Zhang (Aquaculture, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

A new insight into beryllium extraction mechanism from beryllium-containing sludge through key host phase reconstruction and binding energy regulation - Li Li; Huiqin Gao; Jie Li; Weizhen Liu; Yin Li; Zhiyan Zeng; Peng Lin; Changyong Yu; Yong Ke; Xiaoqin Li; Zhang Lin; Liyuan Chai (Journal of Cleaner Production, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

Local contributions and climate change effects on organochlorine pesticide levels in soil and sediments in Svalbard - Yan Lin; Geir Wing Gabrielsen; Zhibo Lu; Qinghui Huang; Peng Huang; Hongwei ke; Minggang Cai (Environmental Pollution, 2025)

Experimental investigation of GFRP bar bonding in geopolymer concrete using hinged beam tests - Yong-Chang Guo; Yong-Jian Cai; Zhi-Hong Xie; Shu-Hua Xiao; Ke-Xian Zhuo; Pei-De Cai; Jia-Xiang Lin (Engineering Structures, 2025)

Poly[nitrilo(diphenoxyphosphoranylidyne)] passivated MAPbI3 film achieves 21.36% efficiency and superior multivariate stability for air-processed perovskite solar cells - Pengyun Zhang; Xiang Mi; Qi-Lin Lu; Xiangshun Li; Yonggui Li; Huizhen Ke; Jie Xiong (Chemical Engineering Journal, 2025)

Avoidance behavior of grass carp (Ctenopharyngodon idella) shoals to low-frequency sound stimulation - Yujiao Wu; Guoyong Liu; Ji Yang; Jiawei Xu; Senfan Ke; Dongqing Li; Xiaolong Chen; Xiaotao Shi; Chenyu Lin (Aquatic Sciences, 2025)

SNPs in the Galectin-8 gene of Acanthopagrus latus have been found to be associated with resistance trait to Streptococcus iniae - Jin-Min Pan; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Teng-Fei Zhu; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture International, 2025)

Experimental Study of Submarine Pipeline with Geotextile and Stone Cover Protection Under the Superposition of Waves and Currents - Wenqi Si; Mingqing Wang; Yaru Gao; Ke Sun; Bing Chen; Risheng Wang; Lin Cui; Dong-Sheng Jeng; Hongyi Zhao (Journal of Marine Science and Engineering, 2024)
Submarine pipelines are the main transport carriers of marine resources. In order to protect these pipelines, geotextile and stone covering measures are adopted in this paper and the protective effect is studied. A sequence of physical model tests was conducted to carry out the research. The hydrodynamic characteristics and seabed oscillation response of the seabed surrounding the pipeline were analyzed with or without geotextile and stone cover protection, and it was found that they were affected by waves (and currents). The experimental results show the following: (1) comparing the regular wave and current with the regular wave alone, it is found that forward current promotes wave propagation and reverse current inhibits wave propagation; (2) the protective effect of geotextile and stone covering measures on different positions of the pipeline (the front, the bottom, and the back of the pipe) is basically same; (3) in the case of waves with large wave heights and long wave periods superimposed with ocean currents, the protective effect of geotextile and stone coverings on the hydrodynamic and seabed pore pressure around the pipeline is more significant.

Characterization of the Galectin-3 gene and its association with Streptococcus iniae resistance traits in Acanthopagrus latus (Houttuyn, 1782) - Jin-Min Pan; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Teng-Fei Zhu; Ke-Cheng Zhu; Dian-Chang Zhang (Aquaculture, 2024)

Experimental study of liquid drop impact on granular medium: Drop spreading/splashing and particle ejection - Shangtuo Qian; Han Ye; David Z. Zhu; Junqiang Lin; Ke Hu; Jiangang Feng (Water Research, 2024)

Sulforaphane acts through the NFE2L2/AMPK signaling pathway to protect boar spermatozoa from cryoinjury by activating antioxidant defenses - Guangzhi Zhang; Fei Wen; Yu Li; Pingyu Sun; Yang Li; Zhangtao Hu; Hui Wang; Yunhui Ma; Guodong Liang; Lin Chen; Ke Yang; Jianhong Hu (Theriogenology, 2024)

Community prevention and standardized clinical treatment jointly improve cancer outcome: Real-world evidence from an esophageal cancer patient cohort study - Ji Ke; Fangfang Liu; Wei Yang; Ruiping Xu; Lei Chen; Wenlei Yang; Yu He; Zhen Liu; Bolin Hou; Liqun Zhang; Miaoping Lin; Lixin Zhang; et al. (Science Bulletin, 2024)

Western diet induces GSDME-mediated epithelial pyroptosis through the DCA-S1PR2 pathway to disrupt the intestinal epithelial barrier - Ke Liu; Mengyao Song; Xueqin Huang; Yanqiang Shi; Sheng Li; Fangqing Zhu; Teng Ben; Xinlong Lin; Bingxia Chen; Beibei Xu; Sicong Ma; Binhai Shen; et al. (Science Bulletin, 2024)

Mechanical modulation wave energy harvesting for self-powered marine environment monitoring - Hong-Xiang Zou; Wen-Zhuo Zhou; Chang-Sheng Su; Ding-Hua Guo; Lin-Chuan Zhao; Qiu-Hua Gao; Ke-Xiang Wei (Ocean Engineering, 2024)

Integration of multiple observations for validation of mechanisms of earthquake-triggered groundwater level Anomalies: 2016 Taiwan Meinong earthquake - Shih-Jung Wang; Yan-Yao Lin; Ying-Han Chen; Chia-Lin Chung; Wen-Chi Lai; Chien-Chung Ke (Journal of Hydrology, 2024)

Application of seismically derived tilt signals to characterize groundwater flow regimes: An example from a constant-rate pumping test in Taiwan - Chu-Fang Yang; Wu-Cheng Chi; Chien-Chung Ke; Chin-Jen Lin (Journal of Hydrology, 2024)

Octopus-inspired flocculant for oily wastewater decontamination: Hydrophilic-hydrophobic convertibility and auto-separation characters - Wei Chen; Zhihan Zhao; Yuhan Du; Shuohao Ouyang; Mengyi Lin; Fengya Li; Hanwei Tang; Hongbing Luo; Ke Zhang; Huaili Zheng (Journal of Hazardous Materials, 2024)

Increased atmospheric thallium threats to populated areas: A mini review - Juan Liu; Yaole Huang; Yanyi Liu; Shunlong Jiang; Qiong Zhang; Pei Li; Ke Lin; Xuan Zeng; Haiyao Hu; Yang Cao; Xinni Xiong; Jin Wang (Journal of Hazardous Materials, 2024)

Emerging antibiotic and heavy metal resistance in spore-forming bacteria from pig manure, manure slurry and fertilized soil - Min Yan; Wen Wang; Lei Jin; Guoyou Deng; Xinfeng Han; Xiumei Yu; Junni Tang; Xiangan Han; Menggen Ma; Lin Ji; Ke Zhao; Likou Zou (Journal of Environmental Management, 2024)

Magnetic recyclable g-C3N4/CuFe2O4/MnO2 activated peroxymonosulfate process via dual Z-scheme heterojunction for photodegradation of ciprofloxacin - Jia Zeng; Tianzhen Gao; Zhou Li; Jing Lin; Yingxi Zhu; Deng Li; Famin Ke; Die Gao; Dandan Wang (Journal of Environmental Chemical Engineering, 2024)

Effects of thermal oxidation interaction via various polar lipid and myofibrillar proteins on the aroma formation in large yellow croaker - Tingting Zhang; Ke Zhang; Xinyi Qi; Sijia Lin; Lei Qin; Xuhui Huang (Food Bioscience, 2024)

The interaction of Lactiplantibacillus plantarum and Latilatilactobacillus sakei regulated the formation of characteristic quality attributes of low-salt fermented tilapia - Ke Zhang; Si-Jia Lin; Xin-Yi Qi; Bao-Cai Xu; Lei Qin; Xu-Hui Huang (Food Bioscience, 2024)

Microbial community succession and changes of volatile compounds in the fermentation process of bamboo shoots - Jinmei Wei; Zongjun Li; Jinyan Kuang; Zikang Yan; Li Wang; Ying Lin; Jin Du; Ke Li; Yuanliang Wang; Li Yang (Food Microbiology, 2024)

Metagenomic analysis manifesting intrinsic relatedness between antibiotic resistance genes and sulfate- and iron-reducing microbes in sediment cores of the Pearl River Estuary - Zhaohong Li; Lan Lin; Xiuqin Xie; Lili Ming; Songzhang Li; Lan Liu; Ke Yuan; Li Lin; Ligang Hu; Tiangang Luan; Baowei Chen (Environmental Pollution, 2024)

Tracing the stepwise warming trend in the tropical Indian Ocean through a 40-year record of oxygen isotope composition in Maldives corals - Ke Lin; Tao Han; Kyle Morgan; Paul S. Kench; Yue-Gau Chen; Xianfeng Wang (Earth and Planetary Science Letters, 2024)

Alpha-ketoglutarate supramolecular network accelerates diabetic wound healing through exudates management and neovascularization - Yimeng Cai; Pochun Lin; Yuhan Li; Linfeng Liu; Shuqin Cao; Bin Zhao; Yueying Wang; Wei Song; Qian Wang; Xinyan Gan; Ke Xu; Qingheng Wu; et al. (Chemical Engineering Journal, 2024)

Enhancing the electrochemical performance of Ni-rich cathode through an in-situ La-doping and La4NiLiO8-coating synergistic strategy - Wei Zeng; Sheng-Qi Su; Ying-Min Qin; Jing-Zhe Wu; Jiang-Nan Ke; Yong-Gang Sun; Xi-Jie Lin (Chemical Engineering Journal, 2024)

Aircraft observation of aerosol and mixed-phase cloud microphysical over the North China Plain, China: Vertical distribution, size distribution, and effects of cloud seeding in two-layered clouds - Zihan Wang; Honglei Wang; Xiaobo Dong; Yang Yang; Yue Ke; Sihan Liu; Yi Cui; Kun Cui; Zihao Wu; Wen Lin (Atmospheric Research, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Unlocking the potential: advancements and future horizons in ROR1-targeted cancer therapies - Lin Li; Weixue Huang; Xiaomei Ren; Zhen Wang; Ke Ding; Linxiang Zhao; Jinwei Zhang (Science China Life Sciences, 2024)

Simulated nitrogen deposition increased herbivore resistance and competitive ability of an invasive plant species over a native co-occurring congeneric species - Tiantian Lin; Zening Wang; Man Ke; Wanci He; Guoqing Zhu; Abdul Manan; Klaas Vrieling; Bo Li (Plant and Soil, 2024)

Polluticaenibacter yanchengensis gen. nov., sp. nov., A Novel Taxon Within the Family Chitinophagaceae Isolated from Activated Sludge - Zhuang Ke; Lin Wang; Ying Yang; Yingchun Du; Jian He; Cansheng Yuan (Current Microbiology, 2024)

Efficient genome engineering in Mycolicibacterium neoaurum using Cas9 from Streptococcus thermophilus - Gedan Xiang; Tao Liu; Lekai Li; Guihong Lin; Ke Liu; Fengqing Wang (Biotechnology Letters, 2024)

Effects of core soil microbial taxa on soil carbon source utilization under different long-term fertilization treatments in Ultisol - Haoran Mao; Guilong Li; Ke Leng; Luyuan Sun; Kailou Liu; Yongxin Lin; Jia Liu; Xingjia Xiang (Soil Ecology Letters, 2024)

Genome‑based classification of the family Natrialbaceae and description of four novel halophilic archaea from three saline lakes and a saline-alkaline land - Xin-Yue Dong; Ya-Ling Mao; Qing-Ke Zhang; Ling-Rui Zhu; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Litter quality regulates cover crop litter decay alongside altered microbial facets - Guilong Li; Ke Leng; Wenjing Qin; Xiaofen Chen; Yongxin Lin; Ming Liu; Meng Wu; Jianbo Fan; Xiaoyue Wang; Yuji Jiang; Jia Liu (Applied Soil Ecology, 2024)

Synthesis of Fe-ZSM-5 zeolite from high iron-containing palygorskite with peroxidase-like catalytic performance - Fengya Ran; Meng He; Shiyong Sun; Rui Lv; Sen Lin; Ke Wang; Yevgeny Aleksandrovich Golubev; Olga Borisovna Kotova; Elena Leonidovna Kotova (Applied Clay Science, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Lactobacillaceae-mediated eye-brain-gut axis regulates high myopia-related anxiety: from the perspective of predictive, preventive, and personalized medicine - Yuze Mi; Ke Chen; Shaokai Lin; Luyao Tong; Jiawei Zhou; Minghui Wan (EPMA Journal, 2024)

Transmission of carbapenem-resistant enterobacterales producing NDM-5 during the broiler breeding process in China - Ke Wu; Yuanyuan Zhang; Wei Xu; Xiaolong Lin; Cui Li; Juan Wang; Ruichao Li; Yizhi Tang; Changwei Lei; Hongning Wang (Veterinary Microbiology, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Impacts of February climate conditions in the Gobi Desert on March dust activities in the northern East Asia - Lin Liu; Dongping Bai; Zhili Wang; Deying Wang; Huizheng Che; Yadong Lei; Ke Gui; Junting Zhong; Xiaoye Zhang (Science of The Total Environment, 2024)

Comparative analysis of size-fractional eukaryotic microbes in subtropical riverine systems inferred from 18S rRNA gene V4 and V9 regions - Guanglong Zhang; Zhenli Guo; Yue Ke; Hanyi Li; Xilin Xiao; Da Lin; Lujian Lin; Yanhong Wang; Jingchun Liu; Haoliang Lu; Hualong Hong; Chongling Yan (Science of The Total Environment, 2024)

Unveiling the common laws of extracellular polymeric substances (EPS) properties on short-chain fatty acids production from sludge by EPS disintegration pretreatment - Xi-qi Li; Zhe Yu; Zhen Lin; Ying-ke Fang; Qi Sun; Kan Chen; Ai-jie Wang; Wen-zong Liu (Science of The Total Environment, 2024)

In-situ aircraft observations of aerosol and cloud microphysical characteristics of mixed-phase clouds over the North China Plain - Kun Cui; Honglei Wang; Yue Ke; Xiaobo Dong; Yang Yang; Zihao Wu; Sihan Liu; Zihan Wang; Wen Lin; Tianliang Zhao (Science of The Total Environment, 2024)

Multi-component optimization of composite pump-jet propulsor based on sensitivity analysis - Jianjie Lin; Qiang Xu; Yinglin Ke (Ocean Engineering, 2024)

Genomic and metabolomic insights into the selection and differentiation of bioactive compounds in citrus - Xiao Liang; Yue Wang; Wanxia Shen; Bin Liao; Xiaojuan Liu; Zimeng Yang; Jiebiao Chen; Chenning Zhao; Zhenkun Liao; Jinping Cao; Ping Wang; Peng Wang; et al. (Molecular Plant, 2024)

Cadmium contamination in sediments from a mangrove wetland: Insights from lead isotopes - Zhenghua Tao; Tianxiang Xia; Fengyuan Chen; Lina Zhang; Rongfei Wei; Shanshan Chen; Lin Jia; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2024)

Synthesis of hydrothermal carbonation carbon with tunable photocatalytic performance for trimethoprim degradation using an ethanol-water co-solvent strategy: Influence of ethanol concentration - Jiashuai Hu; Jie Chen; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; Wei Chen; et al. (Journal of Cleaner Production, 2024)

The carbon emission reduction benefits of the transformation of the intensive use of cultivated land in China - Yajuan Zhou; Ershen Zhang; Lijie He; Xinli Ke; Dan lu; Aiwen Lin; Xiaomin Lai (Journal of Environmental Management, 2024)

Insights into the critical roles of water-soluble organic matter and humic acid within kitchen compost in influencing cadmium bioavailability - Bing Kou; Lin Huo; Minyi Cao; Yuxin Ke; Lei Wang; Wenbing Tan; Ying Yuan; Xiaoli Zhu (Journal of Environmental Management, 2024)

Extraction, phytochemicals characterization, in vivo and in vitro anti-diabetic ability of non-extractable polyphenols from Undaria pinnatifida - Chun-yan Peng; Quan-yuan Xie; Xing Xie; Lin-yi Tang; Tian-xin Ma; Dai-wei Ke; Zong-cai Tu; Lu Zhang (Food Research International, 2024)

Microplastics-biofilm interactions in biofilm-based wastewater treatment processes: A review - Yaning Huang; Tanqiu Hu; Bincheng Lin; Youqing Ke; Jibin Li; Jinxing Ma (Environmental Pollution, 2024)

Acrolein exposure affects ovarian function by interfering with glycolysis and mitochondrial energy metabolism in mouse - Yan-Zhu Chen; Wen-Ke Wang; Yi-Fan Yang; Si-Yao Cheng; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Yu Liu (Environmental Pollution, 2024)

Observations of avalanche–substrate interactions in the Iymek rock avalanche deposit: A possible causative mechanism - Anwen Shi; Yufeng Wang; Qiangong Cheng; Qiwen Lin; Zhiyi Feng; Ke He; Fujun Niu; Zhang Song (Engineering Geology, 2024)

Janus-Adhesive ionogels for wearable Real-Time monitoring and prevention of infantile meningitis - Xiao-Chun Yang; Xiao-Xue Wang; Chen-Yu Wang; Meng Yin; Ke Ma; Yan Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

TEMDI: A Temporal Enhanced Multisource Data Integration model for accurate PM2.5 concentration forecasting - Ke Ren; Kangxu Chen; Chengyao Jin; Xiang Li; Yangxin Yu; Yiming Lin (Atmospheric Pollution Research, 2024)

Assessment of the seismic failure of reinforced concrete structures considering the directional effects of ground motions - Si-Qi Li; Ke Du; Yong-Sheng Chen; Peng-Fei Qin; Gabriele Milani; Antonio Formisano; Peng-Chi Chen; Lin-Lin Zheng; Can Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Environmental explanation of prostate cancer progression based on the comprehensive analysis of polychlorinated biphenyls - Wen-Cai Zheng; Fei Lin; Qian-Ren-Shun Qiu; Yu-Peng Wu; Zhi-Bin Ke; Shao-Hao Chen; Dong-Ning Chen; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Ning Xu (Science of The Total Environment, 2024)

Thallium isotopic fractionation in soils from a historic Hg Tl mining area: New insights on thallium geochemistry - Wenhuan Yuan; Jingye She; Jingfen Lin; Ke Lin; Qiaohui Zhong; Xinni Xiong; Huimin Cao; Xuan Zeng; Jin Wang; Juan Liu (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evidence for sustainably reducing secondary pollutants in a typical industrial city in China: Co-benefit from controlling sources with high reduction potential beyond industrial process - Yueyuan Niu; Yulong Yan; Jiaqi Dong; Ke Yue; Xiaolin Duan; Dongmei Hu; Junjie Li; Lin Peng (Journal of Hazardous Materials, 2024)

Hydroxyl radical mediated extracellular degradation of tetracycline under aerobic and anaerobic conditions stimulated by bio-FeS nanoparticles - Huixia Lan; Ke Li; Qiliang Cao; Qiaochu Liang; Yecheng Lin; Veeriah Jegatheesan; Binghua Yan; Heng Zhang; Yang Zhang (Journal of Hazardous Materials, 2024)

Comparison of in vivo glycolipid metabolism regulation pathway of lotus leaf polysaccharide and its combination with flavonoids and alkaloids: Effectiveness of high-pressure homogenization-assisted dual enzyme extraction - Yaxin Song; Yu Ke; Lianzhu Lin; Mouming Zhao (Food Bioscience, 2024)

Molecular characterization of histone gene in golden pompano (Trachinotus ovatus) and antimicrobial activity of its derived peptides - Yu Liang; Jin-Min Pan; Ke-Cheng Zhu; Lin Xian; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Teng-Fei Zhu; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Personal exposure to airborne organic pollutants and lung function changes among healthy older adults - Xiaojie Guo; Huimin Ren; Peijie Sun; Enmin Ding; Jianlong Fang; Ke Fang; Xiao Ma; Chenfeng Li; Chenlong Li; Yibo Xu; Kangning Cao; Elizabeth.Z. Lin; et al. (Environmental Research, 2024)

Enhanced electrochemical cyclability of composite sodium metal anode with inorganic-rich solid electrolyte interphase - Changqun Cen; Xiaoxue Yang; Xiancheng Wang; Lin Fu; Yuanjian Li; Ke Lu; Liqing He; Yongming Sun (Chemical Engineering Journal, 2024)

Map-based cloning of LPD, a major gene positively regulates leaf prickle development in eggplant - Changjiao Ke; Wenxiang Guan; Jialong Jiang; Likun Huang; Hui Li; Wenjing Li; Yanyu Lin; Lihui Lin; Xiaofang Xie; Weiren Wu; Wenxia Gao; Yan Zheng (Theoretical and Applied Genetics, 2024)

Main Controlling Factors and Prediction Model of Fracture Scale in Tight Sandstone: Insights from Dynamic Reservoir Data and Geomechanical Model Analysis - Jingshou Liu; Yuanhong Lu; Ke Xu; Yang Luo; Haimeng Yang; Lin Lu (Rock Mechanics and Rock Engineering, 2024)

First wetland mapping at 10-m spatial resolution in South America using multi-source and multi-feature remote sensing data - Weiwei Sun; Gang Yang; Yuling Huang; Dehua Mao; Ke Huang; Lin Zhu; Xiangchao Meng; Tian Feng; Chao Chen; Yong Ge (Science China Earth Sciences, 2024)

Atractylenolide II regulates the proliferation, ferroptosis, and immune escape of hepatocellular carcinoma cells by inactivating the TRAF6/NF-κB pathway - Yujie Lin; Ke Chen; Min Zhu; Wei Song; Guiyun Wu; Aizhen Pan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Myricetin alleviates pancreatic microcirculation and inflammation in rats with severe acute pancreatitis through FOXO1 and NF-κB pathways - Ke Ren; Jinfeng Lin; Yadong Wang; Xiaoyan Ji (Molecular & Cellular Toxicology, 2024)

Experimental Study of the Random Wave-Induced Hydrodynamics and Soil Response in a Porous Seabed Around Double Piles - Mingqing Wang; Wenqi Si; Yaru Gao; Lin Cui; Dong-Sheng Jeng; Ke Sun; Bing Chen; Hongyi Zhao (Journal of Marine Science and Engineering, 2024)
The evaluation of the wave-induced pore pressures around the offshore piles has attracted great attentions among coastal engineers, because they have been commonly used as foundations of numerous marine infrastructures. This paper presents comparative studies of the random wave-induced transient seabed response around single and double piles in a sandy seabed through a series of wave flume experiments. The influences of relative spacing ratios, wave incidence angles, and front pile diameters under different random wave parameters on oscillatory pore pressures in the vicinity of double piles are examined. In addition, variations in wave profiles and dynamic wave pressures surrounding single and double piles are quantitatively analyzed. Based on the experimental results, the following conclusions can be drawn: (1) under the influence of random waves, the wave profiles around the double piles exhibit obvious irregularity and nonlinearity; (2) the shielding effect existing in the tandem piles results in lower dynamic wave pressures around the rear pile compared to the front pile; (3) the pore pressures on the front surface of the double piles decrease with increasing soil depth, with a decreasing attenuation rate at each layer; (4) when the relative spacing ratio G/D2=3, the group-pile effect weakens, leading to an increase in the pore pressures around the rear pile, approaching the results of a single pile under conditions of lower significant wave heights or periods; (5) the intense disturbance effect caused by large wave incidence angles exacerbates the pore pressure response around the double piles; (6) when the diameter of the front pile in the tandem piles increases, it enhances the shielding effect, thus suppressing the seabed response around the rear pile. In contrast, it causes an increase in the wave surface around the double piles, exacerbating the pore pressure response in the seabed. The latter effect becomes more pronounced when the significant wave height is larger.

Healthy lifestyles ameliorate an increased risk of periodontitis associated with polycyclic aromatic hydrocarbons - An Li; Yuntao Chen; Mi Du; Ke Deng; Xin Cui; Chunhua Lin; Geerten-Has E. Tjakkes; Xiaodong Zhuang; Shixian Hu (Chemosphere, 2024)

Simultaneous efficient removal of tetracycline and mitigation of antibiotic resistance genes enrichment by a modified activated sludge process with static magnetic field - Yuan-Mo Zhu; Yongsheng Chen; Hewei Lu; Kai Jin; Yuan Lin; Hongqiang Ren; Ke Xu (Water Research, 2024)

Weak magnetic field promotes denitrification by stimulating ferromagnetic ion-containing metalloprotein expression - Yuan Lin; Yanting Chen; Haiyue Wang; Yuexin Yu; Yanru Wang; Sijia Ma; Laichun Wang; Hongqiang Ren; Ke Xu (Water Research, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Divergent rainfall infiltration patterns on the Chinese Loess Plateau between growing and non-growing seasons after long-term revegetation - Ruoxuan Li; Bihang Fan; Zhao Jin; Mingkui Hao; Hu Liu; Yaling Zhang; Yanjia Jiang; Hongyu Yao; Ke Lin; Li Guo (Journal of Hydrology, 2024)

A hyperstable, low-salt adapted protease from halophilic archaeon with potential applications in salt-fermented foods - Jing Hou; Qing-Ke Zhang; Ruo-Yao Zhang; Si-Ya Li; Yuan-Yiyi Liu; Heng-Lin Cui (Food Research International, 2024)

On the modification of plant proteins: Traditional methods and the Hofmeister effect - Ziming Wang; Tiantong Lan; Jing Jiang; Tingyu Song; Jingsheng Liu; Hao Zhang; Ke Lin (Food Chemistry, 2024)

Tailored buried layer passivation toward high-efficiency carbon based all-inorganic CsPbBr3 perovskite solar cell - Long Zhou; Mengjia Sui; Jiaojiao Zhang; Ke Cao; Hongqiang Wang; Haidong Yuan; Zhenhua Lin; Jincheng Zhang; Peixian Li; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Corrigendum to ““One stone, five birds”: Ultrabright and multifaceted carbon dots for precise cell imaging and glutathione detection” [Chem. Eng. J. 457 (2023) 140997] - Zihao Wang; Ke-Fei Xu; Gang Wang; Samran Durrani; Fengming Lin; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Ocean acidification in the tropical Indian Ocean over the past 37 years: Insights from δ11B and B/Ca records in a Maldives coral - Yi-Wei Liu; Ke Lin; Kyle Morgan; Xianfeng Wang (Chemical Geology, 2024)

The Suppression of Flow-Induced Vibrations for a Single and Two Tandem-Arrangement Cylinders Using Three Splitter Plates - Zhongming Hu; Jiasong Wang; Yuankun Sun; Ke Lin (Journal of Marine Science and Engineering, 2024)
Some very useful methods for suppressing the flow-induced vibration (FIV) of a single cylinder are known to potentially have a limited efficiency for tandem-arrangement cylinders. In this paper, three splitter plates uniformly attached around a cylinder with an angle of 120° are proposed to suppress the FIVs of both a single cylinder and two tandem-arrangement cylinders in a wind tunnel at Re = 4000–45,200. The splitter plates’ length to diameter ratios, L/Ds (where L is the length of the splitter plate and D is the cylinder diameter), are set from 0.1 to 0.8. The results show that the proposed method not only effectively suppresses the vortex-induced vibration (VIV) for a single cylinder, but also successfully mitigates the wake-induced galloping (WIG) for two tandem-arrangement cylinders. The vibrations of the single cylinders are effectively suppressed, consistently achieving suppression efficiencies over 95% for L/Ds = 0.2–0.8, with a notable peak efficiency of 98.4% at L/D = 0.2. For the two tandem-arrangement cylinders at S/D = 4.0 (where S is the center-to-center spacing between the two cylinders), the suppression efficiencies of the upstream cylinder exceed 96% for L/D = 0.2–0.8, with an optimal efficiency of 97.4% at L/D = 0.6. The downstream cylinder exhibits vibration only at L/Ds = 0.1, 0.2, and 0.4, resulting in suppression efficiencies of 80.3%, 67.1%, and 91.0%. The vibrations remain fully suppressed throughout the entire reduced velocity range for L/Ds = 0.6–0.8, reaching an optimal efficiency of 98.7% at L/D = 0.6. Three regimes of fs/fn characteristics can be classified for the single cylinder, and the wake structures show that shear layers develop along the front plate before attaching on the cylinder and are then offset to either side of the cylinder by the two rear splitter plates, contributing to the absence of periodic vortex shedding.

Study on the configuration causal factors of electric power generation safety incidents based on grounded theory and fsQCA - Lin Zhu; Ke Xiong; Min Pang (Environmental Science and Pollution Research, 2024)

Hepatitis B virus core protein as a Rab-GAP suppressor driving liver disease progression - Yu Su; Fan Bu; Yuanfei Zhu; Le Yang; Qiong Wu; Yuan Zheng; Jianjin Zhao; Lin Yu; Nan Jiang; Yongxiang Wang; Jian Wu; Youhua Xie; et al. (Science Bulletin, 2024)

Enrichment mechanism of organic matter and silicon in lower Cambrian shale of the Yangtze Platform - Donglin Lin; Zhaodong Xi; Shuheng Tang; Gary G. Lash; Jin Li; Qiyang Gou; Ke Zhang; Xiaofan Mei; Kaifeng Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Microplastics emerge as a hotspot for dibutyl phthalate sources in rivers and oceans: Leaching behavior and potential risks - Lujian Lin; Bo Yuan; Huiling Liu; Yue Ke; Weifeng Zhang; Hanyi Li; Haoliang Lu; Jingchun Liu; Hualong Hong; Chongling Yan (Journal of Hazardous Materials, 2024)

Distribution and migration of rare earth elements in sediment profile near a decommissioned uranium hydrometallurgical site in South China: Environmental implications - Mengqing Sun; Juan Liu; Ke Lin; Wenhuan Yuan; Xiaoliang Liang; Hanyu Wu; Ying Zhang; Qunwei Dai; Xiao Yang; Gang Song; Jin Wang (Journal of Environmental Management, 2024)

Amphichdiral enhancement on singlet oxygen generation and stable thallium immobilization using iron-driven copper oxide - Zhujun Liu; Xinning Dai; Jun He; Mengyi Lin; Hongbing Luo; Liangqian Fan; Ke Zhang; Dandan Ma; Jun Wang; Wei Chen (Journal of Environmental Management, 2024)

Experimental investigation into coal wettability changes caused by reactions with scCO2-H2O - Ke Li; Chuanjie Zhu; Jiamin Wan; Tetsu K. Tokunaga; Na Liu; Cong Ma; Baiquan Lin (Gas Science and Engineering, 2024)

Dynamic changes of key metabolites in Longjing green tea during processing revealed by widely targeted metabolomic profiling and sensory experiments - Lin Zeng; Yan-Qing Fu; Ying Gao; Fang Wang; Shuang Liang; Jun-Feng Yin; Marie-Laure Fauconnier; Lijing Ke; Yong-Quan Xu (Food Chemistry, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Redistribution and activation of inert N-configuration in metallic electron donor towards boosted oxygen reaction kinetics for zinc-air batteries - Yiyao Cao; Yakai Chen; Ke Chen; Lingling Sun; Wenhao Si; Yan Yan; Huijuan Lin; Jixin Zhu; Peilei He; Yan Lu; Haijiao Xie; Kun Rui (Chemical Engineering Journal, 2024)

Genomic structures of insulin-like growth factor from golden pompano (Trachinotus ovatus) and their expression responses to the feed types - Bo Liu; Yin-Yin Liang; Hua-Yang Guo; Bao-Suo Liu; Jing-Wen Yang; Nan Zhang; Lin Xian; Ke-Cheng Zhu; Dian-Chang Zhang (Fish Physiology and Biochemistry, 2024)

Genome-based classification of the family Haloferacaceae and description of five novel species of Halobaculum - Shun Tan; Ling-Rui Zhu; Qing-Ke Zhang; Xin-Yue Dong; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Characteristics of Clay Minerals in Sediments of Xinghua Bay and Nanri Channel in Fujian Province and Their Paleoenvironmental Significance - Xin Li; Jinrong Wang; Ke Yin; Qin Chen; Wei Liu; Yanna Huang; Yongchao Wang; Zhishan Wu; Jiansui Lin (Journal of Marine Science and Engineering, 2024)
Under the background of global climate change, the evolution of climate in the future is the focus of geoscience. The Nanri Channel is an important passage connecting the Xinghua Bay and the Taiwan Strait, in China, and the study of its provenance and paleoenvironmental alternation is of great significance to the climate evolution in the eastern coast of China. The grain size and X-ray diffraction analyses of sediments from ZK1 in Nanri Channel and ZK5 in Xinghua Bay, were used to study the variation of grain size and clay mineral characteristics and to analyze the changes in hydrodynamic characteristics, provenance, and paleoenvironmental evolution in the regions since the Last Glacial Maximum. The results show that the sedimentary environment of ZK1 varies from the nearshore tidal flat facies with strong hydrodynamic conditions and the neighboring rivers as the main provenance, to the littoral facies with weak hydrodynamic conditions and the Yangtze River-like type sediments as the main provenance. The sedimentary environment of ZK5 is from the nearshore tidal flat facies with strong hydrodynamic conditions to the littoral facies with weak hydrodynamic conditions, and the provenance of both facies is mainly Yangtze River-like type sediments. The clay mineral characteristics of ZK1 show that the climate in the Nanri Channel has experienced a change from cool and wet, to mild and dry, to mild and wet since the Last Glacial Maximum, while the climate in the Xinghua Bay has experienced a change from warm and humid, to moderate and dry, to warm and humid since the early-middle Holocene, which provides scientific theoretical support for the provenance and paleoenvironment of sediments in the study area and neighboring areas.

Correction: Indoor air pollution by solid fuel usages for cooking is longitudinally associated with possible sarcopenia in middle-aged Chinese population - Guo Ming Su; Ke Xin Jia; Jun Yi Liu; Xu Chen; Yi Lin Shen; Jia Jing Cai; Qi Wei Guo; Jia Lin; Ding Zhi Fang (Journal of Environmental Health Science and Engineering, 2024)

Buried interface modification and light outcoupling strategy for efficient blue perovskite light-emitting diodes - Shuxin Wang; Zhiqiu Yu; Jiajun Qin; Guoyi Chen; Yongjie Liu; Shuaiwei Fan; Chao Ma; Fang Yao; Hongsen Cui; Shun Zhou; Kailian Dong; Qianqian Lin; et al. (Science Bulletin, 2024)

Emerging global reservoirs in the new millennium: Abundance, hotspots, and total water storage - Chenyu Fan; Chunqiao Song; Jida Wang; Yongwei Sheng; Yaling Lin; Chunyu Yuan; Md Safat Sikder; Jean-François Crétaux; Kai Liu; Tan Chen; Fanxuan Zeng; Linghong Ke (Science Bulletin, 2024)

Pb isotopic fingerprinting of uranium pollution: New insight on uranium transport in stream-river sediments - Jin Wang; Haiyao Hu; Ke Lin; Xudong Wei; Jingzi Beiyuan; Xinni Xiong; Yuebing Wan; Pengyuan Deng; Hanyu Wu; Mingliang Kang; Juan Liu; Xuhui Dong (Journal of Hazardous Materials, 2024)

Review on toxicology and activity of tomato glycoalkaloids in immature tomatoes - Li-hao Wang; De-hong Tan; Xue-song Zhong; Mei-qi Jia; Xue Ke; Yu-mei Zhang; Tong Cui; Lin Shi (Food Chemistry, 2024)

Effect of vegetable oils on the thermal gel properties of PSE-like chicken breast meat protein isolate-based emulsion gels - Ke Li; Lin-Meng Wang; Bing-Bing Cui; Bo Chen; Dian-Bo Zhao; Yan-Hong Bai (Food Chemistry, 2024)

Immobilization mechanisms of Sr(II), Ni(II), and Cd(II) on glomalin-related soil protein in mangrove sediments at the microscopic scale - Bo Yuan; Lujian Lin; Hanyi Li; Yue Ke; Le He; Haoliang Lu; Jingchun Liu; Hualong Hong; Chongling Yan (Environmental Research, 2024)

A conductive and anti-freezing gelatin-PAA-based organic hydrogel (PC-OH) with high adhesion and self-healing activities for wearable electronics - Zhenglin Chen; Jiaqi Yang; Zhicheng Du; Jiansong Ji; Likun Zhang; Haifei Guan; Zhengyang Lei; Xiaopeng Zhang; Canhui Yang; Ying Zhu; Qianhui Sun; Lulu Xu; et al. (Chemical Engineering Journal, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Cardiac toxicity of brentuximab vedotin: a real-word disproportionality analysis of the FDA Adverse Event Reporting System (FAERS) database - Chengjie Ke; Maohua Chen; Yaping Huang; Yan Chen; Cuihong Lin; Pinfang Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

CircTrim37 Ameliorates Intracerebral Hemorrhage Outcomes by Modulating Microglial Polarization via the miR-30c-5p/SOCS3 Axis - Benshuai Wang; Lin Tian; Zhen Zhang; Zhiyi Liu; Ke Li; Qianqian Zhang; Yuejia Song; Jiping Qi (Molecular Neurobiology, 2024)

Composting of invasive plants in urban watercourses and its application in riverbanks: mechanisms and compost quality assessment - Peiyin Wang; Guiping Fu; Zhipeng Guo; Lin Zhao; Weicheng Pang; Chao Pan; Ke Wang; Qiqi Wu; Yurou Chen (Journal of Soils and Sediments, 2024)

Elevational patterns and assembly processes of multifaceted bird diversity in a subtropical mountain system - Haoxian Lin; Xiaoyi Wang; Maojun Zhong; Ke Tang; Yuanbao Du; Haigen Xu; Jianfeng Yi; Wei Liu; Junhua Hu (Journal of Biogeography, 2024)
Aim Mountain systems harbour disproportionate biodiversity on Earth. However, the mechanism underlying community assembly along elevational gradients remains unclear due to the complexity of environmental constraints and biotic interactions. Birds play a crucial role in mountain system and are sensitive to environmental changes, making them an ideal taxon for exploring diversity patterns and the underlying assembly processes. We aimed to identify the elevational patterns of multifaceted bird diversity and explore how different ecological processes drive community assembly. Location A 2600 m elevational gradient on the eastern margin of the Qinghai–Tibetan Plateau. Methods We identified the elevational patterns and assembly processes of alpha‐ and beta‐diversity in the taxonomic, phylogenetic, and functional dimensions. We compared the multidimensional beta‐diversity components and assessed the response of beta‐diversity to variations in elevational and environmental distances. Finally, we examined the roles of spatial and environmental factors in structuring the diversity patterns. Results We observed bimodal elevational patterns across species richness, phylogenetic diversity, and functional diversity but distinct community structures in terms of mean pairwise phylogenetic, and functional diversity. We detected a linear decline in phylogenetic and functional diversity with increasing elevation after controlling for the confounding effect of species richness. We documented relatively high taxonomic and phylogenetic total beta‐diversity, but low functional total beta‐diversity. Turnover dissimilarity contributed much more to total beta‐diversity than nestedness‐resultant dissimilarity. The elevational patterns of standardised measures indicated that competition exclusion and environmental filtering jointly shaped the community assembly process. In general, mean annual temperature, annual precipitation, and area significantly influenced the majority of diversity measures. Conclusions Our results revealed incongruent community structures across phylogenetic and functional diversity. Additionally, our results indicated that species with similar ecological performances or distinct lineages may exhibit convergent adaptations to cold and dry environments. These findings provide insights into the mechanistic understanding of the community assembly process and assist in conservation planning in mountain systems by integrating multifaceted diversity across different dimensions.

Indoor air pollution by solid fuel usages for cooking is longitudinally associated with possible sarcopenia in middle-aged Chinese population - Guo Ming Su; Ke Xin Jia; Jun Yi Liu; Xu Chen; Yi Lin Shen; Jia Jing Cai; Qi Wei Guo; Jia Lin; Ding Zhi Fang (Journal of Environmental Health Science and Engineering, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

First record of the late Famennian conodonts in Qamdo, Tibet and their biostratigraphic implications - Yu-Ze Huang; Wen Guo; Wei Lin; Ping-Cuo Zhaxi; Le Yao; Ke-Yi Hu; Qiu-Lai Wang; Yu-Ping Qi (Palaeoworld, 2024)

CO2-induced micro-mechanical alterations of mudstone Caprock: Examples from the Mercia Mudstone Group, East Irish Sea Basin - Ke Wang; Kevin G. Taylor; Lin Ma (International Journal of Greenhouse Gas Control, 2024)

Can drinking tea become an effective way to alleviate the extraintestinal manifestations of inflammatory bowel disease: A comprehensive review - Yong Lin; Siling Xie; Lizheng Xiao; Zhenyun Liu; Wanping Ke; Jian-an Huang; Zhonghua Liu; Wei Quan (Food Bioscience, 2024)

Density and volume of adsorbed methane in key applications for in-situ gas content: Insights from molecular simulation - TengFei Jia; Songhang Zhang; Shuheng Tang; Di Xin; Shouren Zhang; Bingjie Wang; Qian Zhang; Ke Zhang; Donglin Lin; Wenfu Yang (Chemical Engineering Journal, 2024)

Tail states suppression via surface-modification of wide-bandgap perovskites for high-efficiency all-perovskite photovoltaic tandems - Xuzhi Hu; Fang Yao; Chen Wang; Hongsen Cui; Peng Jia; Shengjie Du; Shun Zhou; Hongling Guan; Qianqian Lin; Weijun Ke; Chen Tao; Guojia Fang (Chemical Engineering Journal, 2024)

Climate factors influencing springtime dust activities over Northern East Asia in 2021 and 2023 - Lin Liu; Zhili Wang; Huizheng Che; Deying Wang; Ke Gui; Bo Liu; Kangjie Ma; Xiaoye Zhang (Atmospheric Research, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Tumor necrosis factor receptor-associated factor 5 protects against intimal hyperplasia by regulation of macrophage polarization via directly targeting PPARγ - Wen-Lin Cheng; Sheng-ping Chao; Fang Zhao; Huan-Huan Cai; Ziyue Zeng; Jian-Lei Cao; Zhili Jin; Ke-Qiong Deng; Xiaorong Hu; Hairong Wang; Zhibing Lu (Inflammation Research, 2024)

Sub-Seasonal Predictability of the Northeast China Cold Vortex in BCC and ECMWF S2S Model Forecasts for 2006–2021 - Yiqiu Yu; Jie Wu; Yihe Fang; Chunyu Zhao; Zongjian Ke; Yitong Lin (Journal of Meteorological Research, 2024)

Spatial identification and evaluation of rural vitality from a function-element-flow perspective: Evidence of Lin’an district in Hangzhou, China - Jing Zhang; Chenyue Guan; Lin Zhang; Zhoulu Yu; Chengxuan Ye; Congmou Zhu; Sinan Li; Ke Wang; Muye Gan (Journal of Geographical Sciences, 2024)

Systemic evaluation of novel acaricide hexythiazox for bioactivity improvement and risk reduction at the enantiomer level - Ping Zhang; Furong Yang; Lulu Ran; Cancan Yang; Can Tang; Xiaojiang Ke; Juanni Chen; Wei Xiao; Lin He; Zhifeng Xu (Science of The Total Environment, 2024)

Association between per- and polyfluoroalkyl substances exposure and prevalence of chronic obstructive pulmonary disease: The mediating role of serum albumin - Yan Wang; Jingwen Zhang; Jiaxian Zhang; Miao Hou; Lingkun Kong; Xiong Lin; Jinxin Xu; Chun Yan; Fan Lin; Sunkui Ke (Science of The Total Environment, 2024)

Recent advances in biofilm technologies for breeding wastewater treatment: Fundamentals, performance and impacts of antibiotics - Bincheng Lin; Yangyu Lai; Youqing Ke; Yaning Huang; Yewen Tao; Xiaomeng Han; Jinxing Ma (Journal of Water Process Engineering, 2024)

Aging behavior and leaching characteristics of microfibers in landfill leachate: Important role of surface mesh structure - Yue Ke; Lujian Lin; Guanglong Zhang; Hualong Hong; Chongling Yan (Journal of Hazardous Materials, 2024)

Hypoxia leads to gill endoplasmic reticulum stress and disruption of mitochondrial homeostasis in grass carp (Ctenopharyngodon idella): Mitigation effect of thiamine - Ke-Jing Huang; Lin Feng; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Xiao-Qiu Zhou; Wei-Dan Jiang (Journal of Hazardous Materials, 2024)

Comparative analysis of characteristics of antibiotic resistomes between Arctic soils and representative contaminated samples using metagenomic approaches - Xiuqin Xie; Baoying Chen; Siqi Zhu; Ruiqiang Yang; Ke Yuan; Ying Yang; Ruohong Chen; Lan Lin; Baowei Chen (Journal of Hazardous Materials, 2024)

Comprehensive insight into mercury contamination in atmospheric, terrestrial and aquatic ecosystems surrounding a typical antimony-coal mining district - Lulu Mao; Wenbo Ren; Yang Tang; Xitao Liu; Mengchang He; Ke Sun; Bo-Tao Zhang; Chunye Lin; Wei Ouyang (Journal of Hazardous Materials, 2024)

Distinctive shear zones demonstrate pervasive laminar cataclastic flow throughout the gigantic Iymek rock avalanche - Anwen Shi; Yufeng Wang; Qiangong Cheng; Qiwen Lin; Tianhua Li; Zhiyi Feng; Ke He; Fujun Niu; Zhang Song (Geomorphology, 2024)

Regulating photoluminescence through single-crystal-to-single-crystal transformation of solvent-containing zero-dimensional hybrid metal halide isomers - Ying-Chen Peng; Jian-Ce Jin; Sheng-Hua Zhou; Hao-Wei Lin; Dan-Dan Huang; Zhong-Hua Deng; Yu Dong; Hao-Jie Xu; Ke-Zhao Du; Ze-Ping Wang; Xiao-Ying Huang (Chemical Engineering Journal, 2024)

Unique role of silica in MOF-Derived High-Loading Palladium-on-Ceria single atom catalysts with excellent efficiency and durability - Ke Tang; Yonghao Wang; Guofei Jiang; Xiaoyu Zhou; Jingjing Wei; Jiangbo Lu; Xiangyan Meng; Shengjie Lu; Lishun Wu; Feng Lin (Chemical Engineering Journal, 2024)

Customizable and scalable manufacture of aesthetic ionic conductive silk yarns for e-textile devices - Ke Wang; Xiao-Xue Wang; Chen-Yu Wang; Meng Yin; Shou-Shan Yu; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Carbon-chain length determines the binding affinity and inhibitory strength of per- and polyfluoroalkyl substances on human and rat steroid 5α-reductase 1 activity - Rong Cui; Lei Ye; Xinyi Qiao; Shaowei Wang; Ke Zheng; Jin Yang; Ren-shan Ge; Han Lin; Yiyan Wang (Chemico-Biological Interactions, 2024)

Behavioral and physiological responses of nocturnal marine shellfish to predation pressure - Qi Luo; Xiaolong Gao; Mo Zhang; Shihui Lin; Huiyang Huang; Miaoqin Huang; Caihuan Ke (Applied Animal Behaviour Science, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

A study on expression of GRP78 and CHOP in neutrophil endoplasmic reticulum and their relationship with neutrophil apoptosis in the development of sepsis - Jinchuan Zhao; Ping Yang; Li Lu; Tao Yi; Yunfeng Li; Wei Mao; Qin Zhou; Ke Lin (Journal of Biosciences, 2024)

Risk assessment and strontium isotopic tracing of potentially toxic metals in creek sediments around a uranium mine, China - Pengyuan Deng; Ke Lin; Wenhuan Yuan; Mario Alberto Gomez; Jingye She; Shan Yu; Mengqing Sun; Yanyi Liu; Jin Wang; Diyun Chen; Juan Liu (Chemosphere, 2024)

Analyzing ozone formation sensitivity in a typical industrial city in China: Implications for effective source control in the chemical transition regime - Yueyuan Niu; Yulong Yan; Yiran Xing; Xiaolin Duan; Ke Yue; Jiaqi Dong; Dongmei Hu; Yuhang Wang; Lin Peng (Science of The Total Environment, 2024)

Diagenetic alterations induced by lamina-scale mass transfer and the impacts on shale oil reservoir formation in carbonate-rich shale of the Permian Lucaogou Formation, Jimusar Sag - Ke Li; Kelai Xi; Yingchang Cao; Xiang Shan; Miruo Lin (Marine and Petroleum Geology, 2024)

Targeted degradation of Bisphenol A with peroxymonosulfate activated by nanoscale zero-valent iron supported on molecularly imprinted polymers - Xinlei Zhu; Juncheng Ke; Chunyan Hu; Tao Lin; Jianjun Liang (Chemical Engineering Journal, 2024)

Heterogeneous catalytic ozonation of atrazine with oxygen vacancy-rich cu-loaded and ce-loaded attapulgite: Efficiency, mechanism and environmental application - Tianxiang Wu; Xi Tang; Yuan Lin; Yanru Wang; Sijia Ma; Yi Xue; Hongqiang Ren; Ke Xu (Chemical Engineering Journal, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Quaternary integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Yong Wang; Mianping Zheng; Yuan Ling; Shuyuan Xiang; Zhaogang Shao; Kexin Zhang; Xue Ke; Xiao Lin; Fang Han; Jian’en Han (Science China Earth Sciences, 2024)

Sea Cucumber Viscera Contains Novel Non-Holostane-Type Glycoside Toxins that Possess a Putative Chemical Defense Function - Yanfang Liu; Zhen Lu; Zhi Yan; Ainuo Lin; Shaoshuai Han; Yaxi Li; Xiao Yang; Xiaodong Li; Xiuli Yin; Ranran Zhang; Ke Li (Journal of Chemical Ecology, 2024)

Ecotoxicity of perfluorooctanoic acid and perfluorooctane sulfonate on aquatic plant Vallisneria natans - Zhen Lin; Wei Zhou; Zhen Ke; Zhonghua Wu (Environmental Science and Pollution Research, 2024)

Organic nutrient availability and extracellular enzyme activities influence harmful algal bloom proliferation in a coastal aquaculture area - Lin-Jian Ou; Zhou Wang; Guang-Mao Ding; Feng-Xian Han; Jin-Yi Cen; Xin-Feng Dai; Ke-Qiang Li; Song-Hui Lu (Aquaculture, 2024)

Cryopreservation of Goldlined seabream Rhabdosargus sarba (Forsskål, 1775) sperm: CASA observation and enzyme activity evaluation - Jin-Min Pan; Ke-Cheng Zhu; Jun Liu; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Jin-Hui Sun; Dian-Chang Zhang (Aquaculture, 2024)

Effects of flow velocity on the muscle nutrient content and flesh quality of the Pacific abalone (Haliotis discus hannai) - Shihui Lin; Mo Zhang; Qi Luo; Miaoqin Huang; Caihuan Ke; Xiaolong Gao (Aquaculture, 2024)

Impacts of the aerosol mixing state and new particle formation on CCN in summer at the summit of Mount Tai (1534m) in Central East China - Zihao Wu; Honglei Wang; Yan Yin; Lijuan Shen; Kui Chen; Jinghua Chen; Zhongxiu Zhen; Yi Cui; Yue Ke; Sihan Liu; Tianliang Zhao; Wen Lin (Science of The Total Environment, 2024)

Biophysical mechanisms underlying tefluthrin-induced modulation of gating changes and resurgent current generation in the human Nav1.4 channel - Hsing-Jung Lai; Ming-Jen Lee; Hsin-Wei Yu; Kuan-Wen Chen; Ke-Li Tsai; Pi-Chen Lin; Chiung-Wei Huang (Pesticide Biochemistry and Physiology, 2024)

Visible light-driven Cl-g-C3N4 activated peroxydisulfate process for TMP efficient degradation in a wide pH range - Jie Chen; Jiashuai Hu; Yuanmao Lin; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; et al. (Journal of Water Process Engineering, 2024)

Investigating the antibiotic resistance genes and their potential risks in the megacity water environment: A case study of Shenzhen Bay Basin, China - Hebin Liang; Jin Huang; Yi Tao; Uli Klümper; Thomas U. Berendonk; Kai Zhou; Yu Xia; Ying Yang; Yang Yu; Ke Yu; Lin Lin; Xiaoyan Li; et al. (Journal of Hazardous Materials, 2024)

Flutter control optimization for a 5000 m suspension bridge with active aerodynamic flaps: a CFD-enabled strategy - Zilong Wang; Lin Zhao; Yiheng Fu; Genshen Fang; Wei Cui; Ke Li; Yaojun Ge (Engineering Structures, 2024)

Behaviour and design of duplex stainless steel bolted connections failing in block shear - Yuchen Song; Xue-Mei Lin; Michael C.H. Yam; Ke Ke; Jia Wang (Engineering Structures, 2024)

Unraveling metabolic fate of a veterinary antibiotic thiamphenicol via the multi-omic approach - Jiayu Zhang; Fangliang Guo; Hebin Liang; Ke Yu; Wan Cai; Lin Lin; Xiaoyan Li; Bing Li (Chemical Engineering Journal, 2024)

The Alasu rock avalanche in the Tianshan Mountains, China: fragmentation, landforms, and kinematics - Qi-wen Lin; Yu-feng Wang; Qian-gong Cheng; Jing Huang; Hao-ran Tian; Guo-xiang Liu; Ke He (Landslides, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Chemical Cues Released by Predators’ Consumption of Heterospecific Prey Alter the Embryogenesis of Zebrafish - Ainuo Lin; Yaxi Li; Zhi Yan; Huilin Zhang; Baozhen Jiang; Jingjing Chen; Derui Wang; Huan Wang; Xiaodong Li; Zhen Lu; Ke Li (Fishes, 2024)
Environmentally cued hatching is prevalent, diverse, and crucial to many animals’ survival. Fish embryos use a variety of chemical cues to initiate hatching to avoid potential predators, yet the function of chemical cues released from the predatory consumption of heterospecific prey is largely unknown. Zebra cichlids (Metriaclima estherae) are ferocious predators that can feed on medaka (Oryzias latipes), though it is impossible for this to occur in their natural habitat. Zebrafish (Danio rerio) embryos have been employed as experimental subjects due to their sensitivity to a variety of chemical signals. In this study, zebrafish embryos were subjected to three types of chemical signals: predator cues (PCs, released from cichlids), heterospecific cues (HCs, released from medaka), and heterospecific dietary cues (HDCs, released from cichlids that have ingested medaka). As a result, the hatching times of zebrafish embryos were accelerated by 6.8% and 12.6% by PCs and HDCs, respectively. PCs and HDCs cause significantly reduced morphology in zebrafish embryos, including regarding total length, eye length, dorsal fin length, trunk height, caudal fin height, and body cavity, and increase yolk sac height. The PCs and HDCs diminished the larvae’s motion at 120 and 144 h post fertilization (hpf), which could be attributed to non-developmental embryogenesis. Overall, the impacts of HDCs on embryonic hatching, developmental morphology, and locomotor were more pronounced in comparison with PCs. Our findings demonstrate that predators’ dietary cues, even those released after predation on heterospecific prey, can modify embryogenesis, highlighting the critical functions of chemical signals in predation risk assessment using embryos.

RETRACTED: Applying thallium isotopic compositions as novel and sensitive proxy for Tl(I)/Tl(III) transformation and source apportionment - Juan Liu; Lulu Wang; Jingfen Lin; Wenhuan Yuan; Liangzhong Li; Yung-Kang Peng; Xinni Xiong; Huimin Cao; Xudong Wei; Qi'en Ouyang; Holger Lippold; Jin Wang; et al. (Science of The Total Environment, 2024)

Fine-scale monitoring of lake ice phenology by synthesizing remote sensed and climatologic features based on high-resolution satellite constellation and modeling - Jie Tong; Yaling Lin; Chenyu Fan; Kai Liu; Tan Chen; Fanxuan Zeng; Pengfei Zhan; Linghong Ke; Yongnian Gao; Chunqiao Song (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Experimental and numerical analysis on the characteristics of flow field and precession moment in fluid momentum wheel with driven pump - Wen-hua Wang; Ke-dong Zhang; Ren-shi Zheng; Lin-lin Wang; Ya-zhen Du; Yi Huang (Ocean Engineering, 2024)

Construction of copper-manganese based aminoclays with significant laccase-like activity and its prominent degradation performance towards bisphenol A - Yifan Zeng; Shiyong Sun; Rui Lv; Ke Wang; Yevgeny Aleksandrovich Golubev; Sen Lin; Faqin Dong; Elena Leonidovna Kotova; Olga Borisovna Kotova (Journal of Environmental Chemical Engineering, 2024)

Potential for CO2 storage in shale basins in China - Jianpeng Wang; Ke Wang; Xuanlong Shan; Kevin G. Taylor; Lin Ma (International Journal of Greenhouse Gas Control, 2024)

Genome-wide identification of heat shock protein gene family and their responses to pathogen challenge in Trachinotus ovatus - Yi-Yao Sun; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Ke-Cheng Zhu; Lin Xian; Peng-Hai Zhao; Hui-Yuan Yang; Dian-Chang Zhang (Fish & Shellfish Immunology, 2024)

Optimizing waste molasses utilization to enhance electron transfer via micromagnetic carriers: Mechanisms and high-nitrate wastewater denitrification performance - Jiahui Chen; Yi Xue; Dongli Yang; Sijia Ma; Yuan Lin; Haiyue Wang; Yanru Wang; Hongqiang Ren; Ke Xu (Environmental Research, 2024)

Diversity and composition of microbial communities in Jinsha earthen site under different degree of deterioration - Jing Li; Yanqiu He; Changjie He; Lin Xiao; Ning Wang; Luman Jiang; Juncheng Chen; Ke Liu; Qiang Chen; Yunfu Gu; Menggen Ma; Xiumei Yu; et al. (Environmental Research, 2024)

Mechanical robust, adhesive, self-healable and biodegradable protein-based electronic skin sensors for smart elderly care - Ying-Ao Zhang; Chen-Yu Wang; Xiao-Xue Wang; Meng Yin; Ke Wang; Da-Wei Zhou; Hong-Long Zheng; Shou-Shan Yu; Shuang Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

Simultaneously enhancing sensitivity and operation range of flexible pressure sensor by constructing a magnetic-guided microstructure in laser-induced graphene composite - Linna Mao; Taisong Pan; Lin Lin; Yizhen Ke; Hengjie Su; Yue Li; Wen Huang; Ting Li; Yuan Lin (Chemical Engineering Journal, 2024)

Black phosphorus nanosheets inhibit glioblastoma cell migration and invasion through modulation of WNT/β-catenin and NOTCH signaling pathways - Yue Xiong; Chao He; Xun Lin; Ke Cheng; Fumei He; Jingxin Zhao; Mengjie Yang; Hong Gao; Fangjie He; Xiaopei Zhang; Zeqi Liu; Gan Liu; et al. (Chemical Engineering Journal, 2024)

Increased Expression of CD74 in Atherosclerosis Associated with Inflammatory Responses of Endothelial Cells and Macrophages - Kun Ke; Zhengzhong Wu; Junqing Lin; Longwang Lin; Ning Huang; Weizhu Yang (Biochemical Genetics, 2024)

Fatty acid metabolism-related molecular subtypes and a novel model for predicting prognosis in bladder cancer patients - Wen-Ting Su; Jia-Yin Chen; Jiang-Bo Sun; Qi Huang; Zhi-Bin Ke; Shao-Hao Chen; Yun-Zhi Lin; Xue-Yi Xue; Yong Wei; Ning Xu (Journal of Biosciences, 2024)

Fertilizer recovery from source-separated urine by evaporation with a combined process of dehumidification and the addition of absorbent resin supplement - Xiaojing Lin; Zhan Jin; Shunfeng Jiang; Zhiquan Wang; Suqing Wu; Ke Bei; Min Zhao; Xiangyong Zheng (Water Research, 2024)

The anti-cancer drug candidate CBL0137 induced necroptosis via forming left-handed Z-DNA and its binding protein ZBP1 in liver cells - Jun Li; Miao Tang; Ruo-Xian Ke; Pei-Lin Li; Zhi-Guo Sheng; Ben-Zhan Zhu (Toxicology and Applied Pharmacology, 2024)

Enhanced membrane fouling by microplastics during nanofiltration of secondary effluent considering secretion, interaction and deposition of extracellular polymeric substances - Dachao Lin; Caijing Lai; Xiaokai Wang; Zhihong Wang; Ke Kuang; Ziyuan Wang; Xing Du; Lifan Liu (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Peptides: Opening the door - Zongcheng Lin; Ke Jin; Noni Franklin-Tong (Molecular Plant, 2024)

Transient ground bulge derived from a dense broadband seismic array during an aquifer step-drawdown pumping test - Wu-Cheng Chi; Chu-Fang Yang; Sebastian Wege; Chin-Jen Lin; Chien-Chung Ke (Journal of Hydrology, 2024)

Investigation of bacterial diversity from hybrid water sources to multiple terminal sites on an isolated island in the south China sea - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Yi Wang; Shu-Jun Yang; Jie Kong; Ying-Li Zhou; Jun-Lin Hu; Ke Ding; Si Zhang (Journal of Cleaner Production, 2024)

Corrigendum to: “Bright green emitter of Mn-doped C4H12N2ZnX4 (X = Cl, Br) for X-ray radiography and WLEDs” [Chem. Eng. J. 468 (2023) 143818] - Yang-Peng Lin; Sanlue Hu; Jiahao Xu; Zhizhuan Zhang; Xinghui Qi; Xuexia Lu; Jiance Jin; Xiao-Ying Huang; Qiang Xu; Zhonghua Deng; Zewen Xiao; Ke-Zhao Du (Chemical Engineering Journal, 2024)

Organic hybrid tetranuclear clusteroluminogens: Blue-light-excitable LED with ultrahigh luminous efficacy - Yang-Peng Lin; Xuexia Lu; Zhizhuan Zhang; Xinghui Qi; Jiance Jin; Jielong Xu; Yancong Wu; Yanan Wu; Zhonghua Deng; Xiao-Ying Huang; Cuiping Han; Sanlue Hu; et al. (Chemical Engineering Journal, 2024)

Effects of Aegilops longissima chromosome 1Sl on wheat bread-making quality in two types of translocation lines - Yuliang Qiu; Zhiyang Han; Ningtao Liu; Mei Yu; Shuangxi Zhang; Haiqiang Chen; Huali Tang; Zhiyong Zhao; Ke Wang; Zhishan Lin; Fangpu Han; Xingguo Ye (Theoretical and Applied Genetics, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Linked mutations within the pathogenicity locus of Clostridioides difficile increase virulence - Qianyun Lin; Zitong Li; Haoran Ke; Jiaxi Fei; Ting Zhang; Pu Wang; Ye Chen (Infectious Diseases, 2023)

Ecological benefits of artificial light at night (ALAN): Accelerating the development and metamorphosis of marine shellfish larvae - Mo Zhang; Xiaolong Gao; Qi Luo; Shihui Lin; Mingxin Lyu; Xuan Luo; Caihuan Ke; Weiwei You (Science of The Total Environment, 2023)

Can water dating trace the transport history of HCHs in the ocean? - Weimin Wang; Haowen Zheng; Peng Huang; Jiandong Ye; Mengyang Liu; Yan Lin; Yifan Li; Mian Chen; Hongwei Ke; Minggang Cai (Science of The Total Environment, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Hierarchical Y zeolite with accessible intracrystalline mesopores and enhanced hydrocracking performances via sequential multi-carboxyl acid and fluoroborate post-treatments - Lin-Jiao Wei; Peng Peng; Ke Qiao; Guang-Nan Cheng; Ubong Jerome Etim; Zi-Feng Yan (Fuel, 2023)

Antibacterial food packaging capable of sustained and unidirectional release carvacrol/thymol nanoemulsions for pork preservation - Lin Wang; Mengyuan Yuan; Enze Sun; Jiang Wu; Anboyuan Lv; Xu Zhang; Jiaxiang Guo; Yu Zhu; Hongbo Guo; Xiaozhou Li; Ke Wang (Food Hydrocolloids, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Associations of 10 trace element levels in the whole blood with risk of three types of obesity in the elderly - Rui Zhan; Lin Liu; Maoyuan Yang; Yating Ren; Zhihao Ge; Jun Shi; Ke Zhou; Jiebao Zhang; Hongjuan Cao; Linsheng Yang; Kaiyong Liu; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Disentangling in-vivo microstructural changes of white and gray matter in mild cognitive impairment and Alzheimer’s disease: a systematic review and meta-analysis - Shuchang Zhong; Jingjing Lou; Ke Ma; Zhenyu Shu; Lin Chen; Chao Li; Qing Ye; Liang Zhou; Ye Shen; Xiangming Ye; Jie Zhang (Brain Imaging and Behavior, 2023)

Sedimentary Features and Paleogeographic Evolution of the Middle Permian Trough Basin in Zunyi, Guizhou, South China - Zhichen Liu; Qi Zhou; Ke Liu; Yang Wang; Deng Chen; Yunming Chen; Lin Xiao (Journal of Earth Science, 2023)

Macroevolution of avian T cell receptor C segments using genomic data - Chunhong Liang; Lin Sun; Ying Zhu; Ayong Zhao; Hongyi Liu; Ke He (Immunogenetics, 2023)

Intrinsic peroxidase-like clay mineral nanozyme-triggered cascade bioplatform with enhanced catalytic performance - Ke Wang; Shiyong Sun; Yevgeny Aleksandrovich Golubev; Sen Lin; Jin Liu; Faqin Dong; Elena Leonidovna Kotova; Olga Borisovna Kotova (Applied Clay Science, 2023)

Study on Vibration Attenuation Performance of Pump-Jet Propulsor Duct with an Axial Slot Structure - Lin Ke; Jinming Ye; Xiaoyu Zou (Journal of Marine Science and Engineering, 2023)
To reduce the structural vibration of the duct structure in pump-jet propulsors (PJPs) and lower the induced vibration noise, this study learned from the “processor box” in an aero-engine and set a certain number of axial slots in the PJP. First, using finite element analysis, both dry and wet modes of the PJP ducts with and without an axial slot structure were simulated for analysis. Next, with the two-way fluid–solid coupling calculation method, the vibration performances of the PJP ducts with and without axial slots were contrasted and studied. The differences in calculation results under different duct structures were compared from three aspects—the vibration displacement, velocity, and acceleration of the duct and mesh nodes. According to the present results, after the addition of axial slots, the vibration displacement, the vibration velocity, and the vibration acceleration can be significantly reduced, especially in the back segment of the duct. Meanwhile, it can be concluded that it is quite important to select vibration acceleration for structural analysis in evaluating the PJP vibration. This study can provide a reference for further designs of low-noise PJPs.

Predicting 1-, 3-, 5-, and 8-year all-cause mortality in a community-dwelling older adult cohort: relevance for predictive, preventive, and personalized medicine - Yequn Chen; Xiulian Deng; Dong Lin; Peixuan Yang; Shiwan Wu; Xidong Wang; Hui Zhou; Ximin Chen; Xiaochun Wang; Weichai Wu; Kaibing Ke; Wenjia Huang; et al. (EPMA Journal, 2023)
Background Population aging is a global public health issue involving increased prevalence of age-related diseases, and concomitant burden on medical resources and the economy. Ninety-two diseases have been identified as age-related, accounting for 51.3% of the global adult disease burden. The economic cost per capita for older people over 60 years is 10 times that of the younger population. From the aspects of predictive, preventive, and personalized medicine (PPPM), developing a risk-prediction model can help identify individuals at high risk for all-cause mortality and provide an opportunity for targeted prevention through personalized intervention at an early stage. However, there is still a lack of predictive models to help community-dwelling older adults do well in healthcare. Objectives This study aims to develop an accurate 1-, 3-, 5-, and 8-year all-cause mortality risk-prediction model by using clinical multidimensional variables, and investigate risk factors for 1-, 3-, 5-, and 8-year all-cause mortality in community-dwelling older adults to guide primary prevention. Methods This is a two-center cohort study. Inclusion criteria: (1) community-dwelling adult, (2) resided in the districts of Chaonan or Haojiang for more than 6 months in the past 12 months, and (3) completed a health examination. Exclusion criteria: (1) age less than 60 years, (2) more than 30 incomplete variables, (3) no signed informed consent. The primary outcome of the study was all-cause mortality obtained from face-to-face interviews, telephone interviews, and the medical death database from 2012 to 2021. Finally, we enrolled 5085 community-dwelling adults, 60 years and older, who underwent routine health screening in the Chaonan and Haojiang districts, southern China, from 2012 to 2021. Of them, 3091 participants from Chaonan were recruited as the primary training and internal validation study cohort, while 1994 participants from Haojiang were recruited as the external validation cohort. A total of 95 clinical multidimensional variables, including demographics, lifestyle behaviors, symptoms, medical history, family history, physical examination, laboratory tests, and electrocardiogram (ECG) data were collected to identify candidate risk factors and characteristics. Risk factors were identified using least absolute shrinkage and selection operator (LASSO) models and multivariable Cox proportional hazards regression analysis. A nomogram predictive model for 1-, 3-, 5- and 8-year all-cause mortality was constructed. The accuracy and calibration of the nomogram prediction model were assessed using the concordance index (C-index), integrated Brier score (IBS), receiver operating characteristic (ROC), and calibration curves. The clinical validity of the model was assessed using decision curve analysis (DCA). Results Nine independent risk factors for 1-, 3-, 5-, and 8-year all-cause mortality were identified, including increased age, male, alcohol status, higher daily liquor consumption, history of cancer, elevated fasting glucose, lower hemoglobin, higher heart rate, and the occurrence of heart block. The acquisition of risk factor criteria is low cost, easily obtained, convenient for clinical application, and provides new insights and targets for the development of personalized prevention and interventions for high-risk individuals. The areas under the curve (AUC) of the nomogram model were 0.767, 0.776, and 0.806, and the C-indexes were 0.765, 0.775, and 0.797, in the training, internal validation, and external validation sets, respectively. The IBS was less than 0.25, which indicates good calibration. Calibration and decision curves showed that the predicted probabilities were in good agreement with the actual probabilities and had good clinical predictive value for PPPM. Conclusion The personalized risk prediction model can identify individuals at high risk of all-cause mortality, help offer primary care to prevent all-cause mortality, and provide personalized medical treatment for these high-risk individuals from the PPPM perspective. Strict control of daily liquor consumption, lowering fasting glucose, raising hemoglobin, controlling heart rate, and treatment of heart block could be beneficial for improving survival in elderly populations.

Analysis of volatile organic compounds and potential odour compounds in food contact paperboard using headspace two-dimensional GC-QTOF-MS - Dan Li; Ying Zeng; Zhi-Kang Ye; Han-Ke Li; Yu-Zhe Li; Ben Dong; Qi-Zhi Su; Qin-Bao Lin; Jing Xiao; Huai-Ning Zhong (Food Additives & Contaminants: Part A, 2023)

Circadian feeding characteristics of different abalone species and construction of a gastrointestinal evacuation model - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Caihuan Ke (Aquaculture, 2023)

Spatial-temporal clogging development in leachate collection systems of landfills: Insight into chemical and biological clogging characteristics - Qian Wang; Qianming Miao; Ke Huang; Yeqi Lin; Tong Wang; Xinyue Bai; Qiyong Xu (Waste Management, 2023)

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

Extraction of triterpene acids from loquat leaves via a novel hydrophobic deep eutectic solvent screened by COSMO-SAC model - Lu Huang; Yingjie Guo; Tianqi Jin; Ke Yan; Xianglin Liu; Shuyang He; Lin Li; Ye Gong; Junyi Ma; Hang Yu; Zhoumin Lu; Yupeng Liu; et al. (Journal of Cleaner Production, 2023)

Headspace single drop microextraction based visual colorimetry for highly sensitive, selective and matrix interference-resistant determination of sulfur dioxide in food samples - Jie Zhou; Xiaojie Lin; Li Zhao; Ke Huang; Qing Yang; Huimin Yu; Xiaoli Xiong (Food Chemistry, 2023)

Salt tide affecting algae-laden micropolluted surface water treatment and membrane performance based on BDD electro-oxidation coupled with ceramic membrane process - Xing Du; Bingxuan Li; Zhongjian Zhuang; Ke Kuang; Wei Song; Dachao Lin; Caixia Fu; Zhihong Wang (Environmental Research, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Weak magnetic field enhances waste molasses-driven denitrification during wastewater treatment - Qingxin Wang; Yuan Lin; Ling Peng; Yanru Wang; Sijia Ma; Hongqiang Ren; Ke Xu (Bioresource Technology, 2023)

Progresses and prospects of impact crater studies - Zongyu Yue; Ke Shi; Kaichang Di; Yangting Lin; Sheng Gou (Science China Earth Sciences, 2023)

Correction to: Antioxidative effects of polypyrimidine tract-binding protein-associated splicing factor against pathological retinal angiogenesis through promotion of mitochondrial function - Lijie Dong; Tingting Lin; Wenbo Li; Yaru Hong; Xinjun Ren; YiFeng Ke; Xiaomin Zhang; Xiaorong Li (Journal of Molecular Medicine, 2023)

Smart enzyme-free amplification dual-mode self-powered platform designed on two-dimensional networked graphdiyne and DNA nanorods for ultra-sensitive detection of breast cancer biomarkers - Yunzhi Ma; Jinyue Shi; Yu Lin; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Complete genome sequence of a novel mitovirus detected in Colocasia esculenta - Mengting Wu; Chanchan Huang; Lin Wang; Bin Ke; Yuwen Lu; Jiejun Peng; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2023)

Experimental Study on the Flow Field, Force, and Moment Measurements of Submarines with Different Stern Control Surfaces - Lin Ke; Jinming Ye; Qiufeng Liang (Journal of Marine Science and Engineering, 2023)
Flow field performance tests of submarine models with cross-rudder and X-rudder stern control surfaces were conducted to study X-rudders’ performance in non-uniform flow fields. The tests compared performance parameters such as resistance, lateral steering force, yaw moment, stern velocity field, and flow field inhomogeneity coefficient under low- and high-speed conditions. The test results show that, at low speed, the resistance of the X-rudder submarine is smaller than that of the cross-rudder one at the same rudder angle. In contrast, at high speed, the resistance of the cross-rudder submarine is smaller than that of the X-rudder submarine. Under low- and high-speed conditions, the X-rudder’s lateral steering force and yaw moment are larger than those of the cross rudder at the same rudder angle. The superiority of the maneuverability of the X-rudder becomes more apparent with increasing rudder angle. At a rudder angle of 10°, the X-rudder’s lateral steering force and yaw moment are about two times larger than the cross rudder’s. In the small-radius area of the propeller plane, the inhomogeneity coefficient of the X-rudder is generally smaller than that of the cross rudder. This is probably because the cross-rudder stern control surfaces have fixed stabilizers with flaps, and the X-rudder stern control surfaces are all-moving, with a small fixed part next to the submarine. This test provides a reference for designing the stern control surface of low-noise submarines.

Two new triterpenoid saponins from Bupleurum marginatum Wall. ex DC - Ke Luo; Rong-Ji Dai; Zhi Wang; Yan-Bo Zeng; Yu-Lin Deng; Fang Lv (Natural Product Research, 2023)

Development of a trace quantitative method to investigate caffeine distribution in the Yellow and Bohai Seas, China, and assessment of its potential neurotoxic effect on fish larvae - Zhi Yan; Yaxi Li; Ainuo Lin; Xiao Yang; Zhen Lu; Huilin Zhang; Jianhui Tang; Jianmin Zhao; Donglei Niu; Tianyu Zhang; Xiaodong Zhao; Ke Li (Marine Pollution Bulletin, 2023)

Examination of the effects of blue light stress on monoamine oxidase-mediated immunomodulatory function in the Pacific abalone, Haliotis discus hannai - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Influence of luminance and luminance longitudinal uniformity of tunnel lighting on drivers' comprehensive visual performance - Cheng Kang; Guojun Lin; Lei Ye; Chi Zhang; Zhiyi Huang; Ke Wu (Tunnelling and Underground Space Technology, 2023)

Cryopreservation of black seabream (Acanthopagrus schlegelii) sperm - Jin-Min Pan; Ke-Cheng Zhu; Jun Liu; Hua-Yang Guo; Bao-Suo Liu; Nan Zhang; Lin Xian; Jin-Hui Sun; Dian-Chang Zhang (Theriogenology, 2023)

Heavy metals and Pb isotopes in sediment cores from the Bering and Chukchi seas: Implications for environmental changes and human activities over the past century - Yan Lin; Zhai Wu; Hongwei Ke; Huorong Chen; Ye Xu; Jin Lin; Yanguang Liu; Fangjian Xu; Dongren Huang; Yi Wang; Tianyao Li; Minggang Cai (Marine Environmental Research, 2023)

Three-dimensional porous adsorbent based on chitosan-alginate-cellulose sponge for selective and efficient removal of anionic dyes - Zeng Wen; Die Gao; Hong Niu; Jing Lin; Zhou Li; Jia Zeng; Famin Ke; Kailian Zhang; Zhining Xia; Dandan Wang (Journal of Environmental Chemical Engineering, 2023)

Lotus leaf polysaccharides prepared by alkaline water, deep eutectic solvent and high pressure homogenization-assisted dual enzyme extraction: A comparative study of structural features, prebiotic activities and functionalities - Yu Ke; Lianzhu Lin; Mouming Zhao (Food Hydrocolloids, 2023)

Hydrogen-based modified atmosphere packaging delays the deterioration of dried shrimp (Fenneropenaeus chinensis) during accelerated storage - Ke Jiang; Yingying Zhang; Chenxu Cai; Weiran Lin; Longna Li; Wenbiao Shen (Food Control, 2023)

Prevalence, distribution, accumulation, and risk of environmental corticosteroids and estrogens in biofilms from the Pearl River Delta - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Wei Tao; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang (Environmental Pollution, 2023)

Impact of COVID-19 pandemic on profiles of antibiotic-resistant genes and bacteria in hospital wastewater - Liang Zhao; Ziquan Lv; Liangqiang Lin; Xiaowei Li; Jian Xu; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Pollution, 2023)

Biodegradable micro-nanofiber medical tape with antibacterial and unidirectional moisture permeability - Ning Zhou; Yu-Fei Gao; Ying Huo; Kai Zhang; Jian Zhu; Ming-Yi Chen; Ling Zhu; Yi-Hang Dong; Hong-Guo Gao; Ick Soo Kim; Ke-Qin Zhang; Rou-Xi Chen; et al. (Chemical Engineering Journal, 2023)

Performance enhancement of proton exchange membrane fuel cells with bio-inspired gear-shaped flow channels - Yuzhi Ke; Baotong Zhang; Wei Yuan; Yafeng Bai; Yonghao Zhao; Zi'ang Liu; Zhenhe Lin; Xinze Li; Yangang Wang; Yong Tang (Chemical Engineering Journal, 2023)

Paleoclimate-induced wildfires in a paleomire in the Ordos Basin, Northern China during the Middle Jurassic greenhouse period - Cunliang Zhao; Ke Zhang; Lin Xiao; Dieter Uhl; Zhixiang Shi; Wenwu Zhao; Qiaojing Zhao; Yuzhuang Sun; Bangjun Liu (Chemical Geology, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Role of short-wave-sensitive 1 (sws1) in cone development and first feeding in larval zebrafish - Ke Lu; Xu-Fang Liang; Shu-Lin Tang; Jiaqi Wu; Lixin Zhang; Yuye Wang; Farui Chai (Fish Physiology and Biochemistry, 2023)

A highly sensitive self-powered sensing method designed on DNA circuit strategy and MoS2 hollow nanorods for detection of thalassemia - Jinyue Shi; Danyao Tang; Yu Lin; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Physiologically based pharmacokinetic model combined with reverse dose method to study the nephrotoxic tolerance dose of tacrolimus - Limin Cai; Meng Ke; Han Wang; Wanhong Wu; Rongfang Lin; Pinfang Huang; Cuihong Lin (Archives of Toxicology, 2023)

Heavy metal contamination collapses trophic interactions in the soil microbial food web via bottom-up regulation - Xuehua Wang; Zhongmin Dai; Jiahui Lin; Haochun Zhao; Haodan Yu; Bin Ma; Lingfei Hu; Jiachun Shi; Xiaoyun Chen; Manqiang Liu; Xin Ke; Yijun Yu; et al. (Soil Biology and Biochemistry, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

A clean and efficient innovative technology for refractory sulfide gold ore: In situ gold extraction via self-generated thiosulfate - Yang Ou; Yongbin Yang; Lin Wang; Ke Li; Wei Gao; Yan Zhang; Qian Li; Tao Jiang (Journal of Cleaner Production, 2023)

Improving sewage sludge dewaterability via heterogeneous activation of persulfate by Fe–Al layered double hydroxide: Role of generated SO4−• - Benyi Xiao; Xiangyu Chen; Ke Zhang; Tianlong Zheng; Chunlin Bian; Jianguo Liu; Lin Li; Junxin Liu (Journal of Environmental Management, 2023)

Retraction Note: Antioxidative effects of polypyrimidine tract-binding protein-associated splicing factor against pathological retinal angiogenesis through promotion of mitochondrial function - Lijie Dong; Tingting Lin; Wenbo Li; Yaru Hong; Xinjun Ren; YiFeng Ke; Xiaomin Zhang; Xiaorong Li (Journal of Molecular Medicine, 2023)

Interactive effects of polyethylene microplastics and cadmium on growth of Glycine max - Mandeep Kaur; Ke Yang; Lin Wang; Ming Xu (Environmental Science and Pollution Research, 2023)

Research on carbon footprint measurement and emissions reduction optimization of the beer supply chain in China - Jing Chen; Han Bao; Lin-Ke Pei (Environmental Science and Pollution Research, 2023)

PSME3 induces radioresistance and enhances aerobic glycolysis in cervical cancer by regulating PARP1 - Xing Wei; Ke Sun; Shubo Li; Cheng Lin; Zhongheng Wei (Tissue and Cell, 2023)

Mechanisms of lead uptake and accumulation in wheat grains based on atmospheric deposition-soil sources - Chuang Ma; Lin Lin; Junxing Yang; Fuyong Liu; Mario Berrettoni; Ke Zhang; Nan Liu; Hongzhong Zhang (Science of The Total Environment, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Association of long-term exposure to ambient PM2.5 and its constituents with gut microbiota: Evidence from a China cohort - Sicheng Li; Bing Guo; Ke Dong; Shourui Huang; Jialong Wu; Hanwen Zhou; Kunpeng Wu; Xinyu Han; Xian Liang; Xiaofang Pei; Haojiang Zuo; Hualiang Lin; et al. (Science of The Total Environment, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Simultaneous recovery of Fe2O3 and PbCl2 from hazardous jarosite residues via hydrothermal phase transformation with NaCl - Yejing Zeng; Wenchao Zhang; Jiahui Wu; Yangjin Wei; Yong Ke; Meiqing Shi; Xu Yan; Zhang Lin (Hydrometallurgy, 2023)

Novel cationic porous materials with open architectures for highly efficient palladium recovery: Integrated experimental studies and DFT simulations - Pengcheng Wu; Yongjie Jiang; Wenxia Lin; Ke Wang; Kexin Wang; Song Qin; Yimin Cai; Lihua Yuan; Wen Feng (Hydrometallurgy, 2023)

Detection of walnut oil adulterated with high-linoleic acid vegetable oils using triacylglycerol pseudotargeted method based on SFC-QTOF-MS - Jing-Jing Zhang; Yan Gao; Mei-Ling Zhao; Xiao Xu; Bo-Nan Xi; Li-Ke Lin; Jing-Yi Zheng; Bang Chen; Yu Shu; Cong Li; Yehua Shen (Food Chemistry, 2023)

Effects of winemaking techniques on the phenolics, organic acids, and volatile compounds of Muscat wines - Yan-lun Ju; Xue-lei Xu; Yi-ke Yu; Meng Liu; Wan-ni Wang; Jin-ren Wu; Bo-chen Liu; Yang Zhang; Yu-lin Fang (Food Bioscience, 2023)

Maternal exposure to fine particulate matter and congenital heart defects during preconception and pregnancy period: A cohort-based case-control study in the Taiwan maternal and child health database - Ya-Chu Chang; Yu-Ting Lin; Chau-Ren Jung; Ke-Wei Chen; Bing-Fang Hwang (Environmental Research, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

A novel CD8+ T cell-related gene signature for predicting the prognosis and immunotherapy efficacy in bladder cancer - Fei Lin; Zhi-Bin Ke; Yu-Ting Xue; Jia-Yin Chen; Hai Cai; Yun-Zhi Lin; Xiao-Dong Li; Yong Wei; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Enhancing biosensing with fourfold amplification and self-powering capabilities: MoS2@C hollow nanorods-mediated DNA hexahedral framework architecture for amol-level liver cancer tumor marker detection - Jinyue Shi; Weiling Qin; Yu Lin; Mingxiang Li; Yeyu Wu; Hu Luo; Jun Yan; Ke-Jing Huang; Xuecai Tan (Analytica Chimica Acta, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Heterogeneity of the Ailaoshan–Song Ma ophiolitic mélange and its palaeogeographic implications for the evolution of Eastern Palaeo-Tethys - Fei Liu; Wei Lin; Yin Wang; Lingtong Meng; Michel Faure; Vuong Van Nguyen; Qinying Wu; Yang Chu; Wei Wei; Hoai Luong Thi Thu; Tich Van Vu; Qiuli Li; et al. (Tectonophysics, 2023)

Exploring distinct types of intertidal bars on either side of a small estuary using a multifaceted approach - Ke Luo; Yunwei Wang; Li Wang; Hangjie Lin; Jie Qin; Dongmei Xie; Burghard Flemming; Shu Gao; Qian Yu (Marine Geology, 2023)

Isopropanol and styrene removal from aqueous solutions and simultaneous power generation using microbial fuel cells with encapsulated deoxygenated anodes - Shu-Hui Liu; Jun-Ru Ke; Hwai Chyuan Ong; Chi-Wen Lin (Journal of Water Process Engineering, 2023)

Distribution of hydrogen isotope in the soil around the Qinshan Nuclear Power Plant - Jie Liang; Wen-yu Cheng; Jing-lin Li; Xiao-chong Xue; Ke Deng; Chao-fei Liang; Lin Du; Qin Zhang; Wei Liu (Journal of Environmental Radioactivity, 2023)

Variation in microbiological heterogeneity in Chinese strong-flavor Baijiu fermentation for four representative varieties of sorghum - Mao-Ke Liu; Yu-Ming Tang; Cheng-Yuan Liu; Xin-Hui Tian; Ji-Wei Zhang; Xiao-Li Fan; Kai-Feng Jiang; Xian-Lin Ni; Xin-Yu Zhang (International Journal of Food Microbiology, 2023)

Nano-scale synchrotron imaging of shale swelling in the presence of water - Ke Wang; Jianpeng Wang; Jingyue Hao; Chenzi Shi; Shouxu Pan; Shashidhara Marathe; Kevin G. Taylor; Lin Ma (Fuel, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Bright green emitter of Mn-doped C4H12N2ZnX4 (X = Cl, Br) for X-ray radiography and WLEDs - Yang-Peng Lin; Sanlue Hu; Jiahao Xu; Zhizhuang Zhang; Xinghui Qi; Xuexia Lu; Jiance Jin; Xiao-Ying Huang; Qiang Xu; Zhonghua Deng; Zewen Xiao; Ke-Zhao Du (Chemical Engineering Journal, 2023)

High-enthalpy biphasic phase change organogels with shape memory function based on hydrophobic association and H-bonding interaction - Chenxiao Yin; Zhi-Xiong Fei; Jingrui Sun; Lin Weng; Xu Wang; Ke-Ke Yang; Ling-Ying Shi (Chemical Engineering Journal, 2023)

Effects of successional sulfadiazine exposure on biofilm in moving bed biofilm reactor: Secretion of extracellular polymeric substances, community activity and functional gene expression - Liang Zhu; Jingwei Ma; Huizhou Yuan; Lin Deng; Zhou Shi; Qiulai He; Shuizhou Ke (Bioresource Technology, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Management‐induced changes in soil organic carbon and related crop yield dynamics in China's cropland - Bai‐Jian Lin; Ruo‐Chen Li; Ke‐Chun Liu; Olatunde Pelumi Oladele; Zhi‐Yu Xu; Rattan Lal; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2023)
Enhancing soil organic carbon (SOC) sequestration and food supply are vital for human survival when facing climate change. Site‐specific best management practices (BMPs) are being promoted for adoption globally as solutions. However, how SOC and crop yield are related to each other in responding to BMPs remains unknown. Here, path analysis based on meta‐analysis and machine learning was conducted to identify the effects and potential mechanisms of how the relationship between SOC and crop yield responds to site‐specific BMPs in China. The results showed that BMPs could significantly enhance SOC and maintain or increase crop yield. The maximum benefits in SOC (30.6%) and crop yield (79.8%) occurred in mineral fertilizer combined with organic inputs (MOF). Specifically, the optimal SOC and crop yield would be achieved when the areas were arid, soil pH was ≥7.3, initial SOC content was ≤10 g kg −1 , duration was >10 years, and the nitrogen (N) input level was 100–200 kg ha −1 . Further analysis revealed that the original SOC level and crop yield change showed an inverted V‐shaped structure. The association between the changes in SOC and crop yield might be linked to the positive role of the nutrient‐mediated effect. The results generally suggested that improving the SOC can strongly support better crop performance. Limitations in increasing crop yield still exist due to low original SOC level, and in regions where the excessive N inputs, inappropriate tillage or organic input is inadequate and could be diminished by optimizing BMPs in harmony with site‐specific conditions.

Functionalization of melamine sponge for the efficient recovery of Pt(IV) from acid leachates - Zhaojiang Wu; Zheng Lin; Shengye Wang; Bo Yang; Ke Xiao (Environmental Science and Pollution Research, 2023)

Characterization of a cadmium-resistant functional bacteria (Burkholderia sp. SRB-1) and mechanism analysis at physiochemical and genetic level - Huakang Liu; Huayan Huang; Ke Liang; Kangkai Lin; Yuxian Shangguan; Heng Xu (Environmental Science and Pollution Research, 2023)

Numerical study on unsteady propeller exciting characteristics considering shafting whirling vibration effect - Chang-Lin Meng; Zhi-Jun Shuai; Tao Yu; Ke-Xin Ren; Jie Jian; Xi Wang; Dong-Hua Wang; Wan-You Li; Chen-Xing Jiang (Ocean Engineering, 2023)

Calcium-dependent activation of CPK12 facilitates its cytoplasm-to-nucleus translocation to potentiate plant hypoxia sensing by phosphorylating ERF-VII transcription factors - Biao Fan; Ke Liao; Lin-Na Wang; Li-Li Shi; Yi Zhang; Ling-Jing Xu; Ying Zhou; Jian-Feng Li; Yue-Qin Chen; Qin-Fang Chen; Shi Xiao (Molecular Plant, 2023)

Succession and environmental response of sediment bacterial communities in the Liao River Estuary at the centenary scale - Zining Guo; Yan Li; Mengqi Shao; Tongxin Sun; Mengping Lin; Tie Zhang; Ke Hu; Hongchen Jiang; Xiangyu Guan (Marine Environmental Research, 2023)

Experimental study on coal combustion by using the ilmenite ore as active bed material in a 0.3 MWth circulating fluidized bed - Lin Li; Junhua Mao; Wu Tang; Guang Sun; Quanbin Gu; Xiaoyan Lu; Ke Shao; Yuqing Chen; Lunbo Duan (Fuel, 2023)

A comparative study on the taste quality of Mytilus coruscus under different shucking treatments - Shichen Zhu; Lin Zhu; Zhigang Ke; Hui Chen; Yadan Zheng; Peng Yang; Xingwei Xiang; Xiaomin Zhou; Youding Jin; Shanggui Deng; Xuxia Zhou; Yuting Ding; et al. (Food Chemistry, 2023)

Experimental and numerical study of micro-tubular direct carbon solid oxide fuel cell fueled by the oilseed rape straw-derived biochar - Tingting Han; Yujiao Xie; Lin Li; Ke Miao; Yu Mei; Jian Song; Jinjin Zhang; Xiuxia Meng; Ngie Hing Wong; Jaka Sunarso; Fangyong Yu; Naitao Yang (Chemical Engineering Journal, 2023)

Ecotoxicological risk assessment of 14 pesticides and corresponding metabolites to groundwater and soil organisms using China-PEARL model and RQ approach - Jiangong Jiang; Zhixin Liu; Beixing Li; Shankui Yuan; Ronghua Lin; Xin Yu; Xiao Liu; Xianxia Zhang; Ke Li; Dong Xiao; Shaoli Yu; Wei Mu (Environmental Geochemistry and Health, 2023)

Effects of phosphorus fertilizer application rate on transformation processes of phosphorus fractions in the purple alluvial soil of a riparian zone - Li-ping He; Kai-tao Jia; Dan Liu; Ke-hong Wang; Lin-Yan Duan; Jun-jie Lin (Journal of Mountain Science, 2023)

High-Intensity Ultraviolet-C Irradiation Efficiently Inactivates SARS-CoV-2 Under Typical Cold Chain Temperature - Peiru Li; Xianliang Ke; Dongmei Leng; Xian Lin; Wenling Yang; Hainan Zhang; Changqing Tian; Hongbo Xu; Quanjiao Chen (Food and Environmental Virology, 2023)

Characterization of lacustrine harmful algal blooms using multiple biomarkers: Historical processes, driving synergy, and ecological shifts - Qi Lin; Ke Zhang; Suzanne McGowan; Shixin Huang; Qingju Xue; Eric Capo; Can Zhang; Cheng Zhao; Ji Shen (Water Research, 2023)

Effects of conservation agriculture on carbon mineralization: A global meta-analysis - Cong He; Zhe Chen; Ke-Yi Qiu; Jin-Sai Chen; Yves N'Dri Bohoussou; Yash Pal Dang; Hai-Lin Zhang (Soil and Tillage Research, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Three unprecedented thioether-linked dimeric pyrimidines isolated from the medicinal-edible herb Ligusticum striatum DC - Bo Yang; Zhong-Duo Yang; Ke-Zhen Ma; Wen-Lin Guo; Tian-Hao Zhang; Tian-Kun Zhao (Phytochemistry, 2023)

Benzo(a)pyrene exposure in early life suppresses spermatogenesis in adult male zebrafish and association with the methylation of germ cell-specific genes - Ke Xu; Dongxu Gao; Jing Lin; Qinhua Dai; Qian Zhou; Ying Chen; Chonggang Wang (Aquatic Toxicology, 2023)

Cross-sectional rainfall observation on the central-western Tibetan Plateau in the warm season: System design and preliminary results - Kun Yang; Yingying Chen; Lazhu; Changhui Zhan; Xiaoyan Ling; Xu Zhou; Yaozhi Jiang; Xiangnan Yao; Hui Lu; Xiaogang Ma; Lin Ouyang; Weihao Pan; et al. (Science China Earth Sciences, 2023)

Complete nucleotide sequence of hackberry virus A, a tentative member of the genus Waikavirus - Jiajia Weng; Mengting Wu; Zhuangxin Ye; Lin Wang; Bin Ke; Chanchan Huang; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; et al. (Archives of Virology, 2023)

BCB1, a member of the acyl-coenzyme A synthetase family, regulates the morphogenesis and pathogenicity of Botrytis cinerea - Jiling Xiao; Ke Yang; Zhihuai Liang; Yi Zhang; Lin Wei (Archives of Microbiology, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

Physiological response and photosynthetic recovery to an extreme drought: Evidence from plants in a dry-hot valley savanna of Southwest China - Da Yang; Yang-Si-Ding Wang; Qin Wang; Yan Ke; Yun-Bing Zhang; Shi-Bao Zhang; Yong-Jiang Zhang; Nate G. McDowell; Jiao-Lin Zhang (Science of The Total Environment, 2023)

Prevalence and Subtype Distribution of Blastocystis in Tibetan Sheep in Qinghai Province, Northwestern China - Fan Yang; Jing-min Gou; Bing-ke Yang; Jia-yue Du; Hui-zhong Yao; Mei Ren; Qing Lin (Protist, 2023)

Mediated anaerobic system performance, co-metabolizing flora and electron transfer by graphene oxide supported zero-valent iron composite - Huixia Lan; Linyu Ji; Ke Li; Yecheng Lin; Xiangzhi Wang; Wudi Zhang; Qiaochu Liang; Yang Zhang (Journal of Environmental Chemical Engineering, 2023)

Novel Al-doped UiO-66-NH2 nanoadsorbent with excellent adsorption performance for tetracycline: Adsorption behavior, mechanism, and application potential - Liangqian Fan; Jiaxin Miao; Xianda Wang; Jie Cai; Jiawei Lin; Fenghui Chen; Wei Chen; Hongbing Luo; Lin Cheng; Xiaochan An; Xiaoxiao Zhang; Ke Zhang; et al. (Journal of Environmental Chemical Engineering, 2023)

Polystyrene microplastics arrest skeletal growth in puberty through accelerating osteoblast senescence - Chun Pan; Yin Wu; Sihan Hu; Ke Li; Xiangyu Liu; Yu Shi; Wenzheng Lin; Xinglong Wang; Yujie Shi; Zhuobin Xu; Huihui Wang; Hao Chen (Environmental Pollution, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

To what extent the traffic restriction policies can improve its air quality? An inspiration from COVID-19 - Si-qing Xu; Hong-di He; Ming-ke Yang; Cui-lin Wu; Xing-hang Zhu; Zhong-ren Peng; Yuya Sasaki; Kenji Doi; Shinji Shimojo (Stochastic Environmental Research and Risk Assessment, 2023)

Morroniside inhibits Beclin1-dependent autophagic death and Bax-dependent apoptosis in cardiomyocytes through repressing BCL2 phosphorylation - Xueping Ke; Shicheng Yu; Shubiao Situ; Zhenqian Lin; Yiqiang Yuan (In Vitro Cellular & Developmental Biology - Animal, 2023)

Changes in the Microbiota and their Roles in Patients with Type 2 Diabetes Mellitus - Qiao-ling He; Hui-chao Wang; Yu-ke Ma; Rui-lin Yang; Zhi-feng Dai; Jing-nan Yang; Yao Xu; Dan-dan Wei; Li-ping Zhu; Xu-hong Lin (Current Microbiology, 2023)

m6A writer WTAP targets NRF2 to accelerate bladder cancer malignancy via m6A-dependent ferroptosis regulation - Ke Wang; Gang Wang; Gang Li; Wei Zhang; Yarong Wang; Xiaofeng Lin; Chengxian Han; Hanxuan Chen; Liang Shi; Abudoula Reheman; Jingkai Li; Zhaomin Li; et al. (Apoptosis, 2023)

Hyperbaric Oxygen Therapy Attenuated the Motor Coordination and Cognitive Impairment of Polyglutamine Spinocerebellar Ataxia SCA17 Mice - Meng-Ke Chiang; Ta-Chun Lin; Keng-Hsuan Lin; Ya-Chin Chang; Hsiu Mei Hsieh-Li; Dar-Ming Lai (The Cerebellum, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

The mechanism of different cyanobacterial responses to glyphosate - Wei Lin; Zhenyan Zhang; Yiling Chen; Qi Zhang; Mingjing Ke; Tao Lu; Haifeng Qian (Journal of Environmental Sciences, 2023)

Thin-layer chromatography coupled with HPLC-DAD/UHPLC-HRMS for target and non-target determination of emerging halogenated organic contaminants in animal-derived foods - Ying Li; Ling Wang; Minggang Zheng; Yongfeng Lin; Hongyan Xu; Aifeng Liu; Yi Hua; Yuqing Jiang; Ke Ning; Shanmin Hu (Food Chemistry, 2023)

Differential diagnosis of prostate cancer and benign prostatic hyperplasia based on DCE-MRI using bi-directional CLSTM deep learning and radiomics - Yang Zhang; Weikang Li; Zhao Zhang; Yingnan Xue; Yan-Lin Liu; Ke Nie; Min-Ying Su; Qiong Ye (Medical & Biological Engineering & Computing, 2023)

Microbial response to antimony-arsenic distribution and geochemical factors at arable soil around an antimony mining site - Huayan Huang; Kangkai Lin; Ling Lei; Yongyun Li; Yipeng Li; Ke Liang; Yuxian Shangguan; Heng Xu (Environmental Science and Pollution Research, 2023)

A comprehensive review on mixotrophic denitrification processes for biological nitrogen removal - Jintao Zhang; Chunzhen Fan; Min Zhao; Zhiquan Wang; Shunfeng Jiang; Zhan Jin; Ke Bei; Xiangyong Zheng; Suqing Wu; Ping Lin; Huanyi Miu (Chemosphere, 2023)

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Policy impact on microplastic reduction in China: Observation and prediction using statistical model in an intensive mariculture bay - Kazi Belayet Hossain; Yan Lin; Kai Chen; Mingyu Zhang; Mengyang Liu; Wenlu Zhao; Hongwei Ke; Fengjiao Liu; Chunhui Wang; Minggang Cai (Science of The Total Environment, 2023)

Estimation of the soil arsenic concentration using a geographically weighted XGBoost model based on hyperspectral data - Miao Ye; Lin Zhu; Xiaojuan Li; Yinghai Ke; Yong Huang; Beibei Chen; Huilin Yu; Huan Li; Hui Feng (Science of The Total Environment, 2023)

Quantitative analysis of the structural evolution in Si anode via multi-scale image reconstruction - Chen Zhu; Shiming Chen; Ke Li; Zu-Wei Yin; Yinguo Xiao; Hai Lin; Feng Pan; Luyi Yang (Science Bulletin, 2023)

Pollutant removal performance and microbial responses of pure moving bed biofilm reactor to the successional sulfadiazine exposure - Liang Zhu; Huizhou Yuan; Jingwei Ma; Lin Deng; Zhou Shi; Qiulai He; Shuizhou Ke (Journal of Water Process Engineering, 2023)

Eco-friendly and low-energy innovative scheme of self-generated thiosulfate by atmospheric oxidation for green gold extraction - Yang Ou; Yongbin Yang; Ke Li; Wei Gao; Lin Wang; Qian Li; Tao Jiang (Journal of Cleaner Production, 2023)

Microstructure changes as a response to CO2 storage in sedimentary rocks: Recent developments and future challenges - Ke Wang; Lin Ma; Kevin G. Taylor (Fuel, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Effect of electric field and water on Pd-based catalyst for complete oxidation of methane: Study on promotion and deactivation - Xuteng Zhao; Ting Chen; Yinan Wang; Ke Li; Reggie Zhan; He Lin (Chemical Engineering Journal, 2023)

“One stone, five birds”: Ultrabright and multifaceted carbon dots for precise cell imaging and glutathione detection - Zihao Wang; Ke-Fei Xu; Gang Wang; Samran Durrani; Fengming Lin; Fu-Gen Wu (Chemical Engineering Journal, 2023)

100% N2O inhibition in photocatalytic NOx reduction by carbon particles over Bi2WO6/TiO2 Z-scheme heterojunctions - Ruting Yuan; Mingtao Wang; Lijun Liao; Wei Hu; Ziyu Liu; Zhaohui Liu; Liping Guo; Ke Li; Yuezhi Cui; Feng Lin; Furong Tao; Wei Zhou (Chemical Engineering Journal, 2023)

Discovery of inhibitors against SARS-CoV-2 main protease using fragment-based drug design - Hai Ping Shao; Tian Hua Wang; Hong Lin Zhai; Ke Xin Bi; Bing Qiang Zhao (Chemico-Biological Interactions, 2023)

Mito-TEMPO, a Mitochondria-Targeted Antioxidant, Improves Cognitive Dysfunction due to Hypoglycemia: an Association with Reduced Pericyte Loss and Blood-Brain Barrier Leakage - Lu Lin; Zhou Chen; Cuihua Huang; Yubin Wu; Lishan Huang; Lijing Wang; Sujie Ke; Libin Liu (Molecular Neurobiology, 2023)

Dexmedetomidine alleviates acute lung injury by promoting Tregs differentiation via activation of AMPK/SIRT1 pathway - Zheng-tao Zhang; Ke Xie; Ren-jie Luo; Dan-ying Zhang; Zhi-wei He; Ke-feng Li; Shi-hui Lin; Fang Xu (Inflammopharmacology, 2023)

Spatial distribution and driving factors of sediment net nitrogen mineralization in riparian zone of the Three Gorges Reservoir - Kai-tao Jia; Li-ping He; Ke-hong Wang; Zhi-guo Yu; Li-jiao Liang; Zhuo-lin Yu; Jun-jie Lin (Journal of Mountain Science, 2023)

Non-Dose-Dependent Relationship between Antipredator Behavior and Conspecific Alarm Substance in Zebrafish - Yaxi Li; Zhi Yan; Ainuo Lin; Xiaodong Li; Ke Li (Fishes, 2023)
A series of behavioral detection paradigms have been developed for zebrafish (Danio rerio) to examine anxiety-like behavioral responses. Among them, the novel tank diving test is rapidly gaining popularity in translational neuroscience and behavioral research for the investigation of psychopharmacological activity focusing on stress. Zebrafish respond to conspecific epidermal-released alarm substances with antipredator reactions. Although the alarm responses of zebrafish were well characterized in a novel tank diving experiment, the relationship between the intensity of the alarm behavior and the concentration of the alarm substance needed to be understood more adequately. In the current paper, we investigated the behavioral phenotypes and potencies of zebrafish elicited by the serial dilution of an alarm substance in the novel tank diving test. Using a video-tracking assisted behavioral quantification approach, we demonstrated no linear concentration-dependent relationship between antipredator behavior and skin extracts, suggesting that an optimal concentration induced each typical behavioral response. The results showed that the freezing duration (%) significantly increased when stimulated with 104-fold times dilutions of skin extract (equivalent 5 × 10−5 fish/L), while erratic movements (%), time in the bottom half (%), and latency to the upper half (s) significantly elevated when stimulated with 103-fold times dilutions (equivalent 5 × 10−4 fish/L). Therefore, the concentration threshold for an alarm substance that elicited innate fear behavior in zebrafish was presumed to be an equivalent concentration of approximately 5 × 10−4 fish/L. The conclusions may fill a knowledge gap between the innate fear response triggered by injured skin and a novel tank diving paradigm that provides insights into the characterization of alarm substance, behavioral responses, and physiological response mechanisms in zebrafish.

Within-species plant phylogeny drives ectomycorrhizal fungal community composition in tree roots along a timberline - Teng Yang; Luyao Song; Han-Yang Lin; Ke Dong; Xiao Fu; Gui-Feng Gao; Jonathan M. Adams; Haiyan Chu (Soil Biology and Biochemistry, 2023)

Mitochondrial alternative oxidase enhanced ABA-mediated drought tolerance in Solanum lycopersicum - Kang Qiao; Xiuhong Yao; Zuxu Zhou; Jiawei Xiong; Ke Fang; Jiayi Lan; Fei Xu; Xingguang Deng; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2023)

Degradation of poly(butylene adipate-co-terephthalate) films by Thermobifida fusca FXJ-1 isolated from compost - Xianbo Jia; Ke Zhao; Jie Zhao; Chenqiang Lin; Hui Zhang; Longjun Chen; Jichen Chen; Yu Fang (Journal of Hazardous Materials, 2023)

Environmental concentrations of benzophenone-3 disturbed lipid metabolism in the liver of clown anemonefish (Amphiprion ocellaris) - Yan-Kun Zhang; Huai-Yang Ke; Yong-Qiang Qin; Han-Ye Ju; Yu-Mei Chen; Fang Lin; Ji-Liang Zhang; Xiao-Ping Diao (Environmental Pollution, 2023)

Electricity consumption and load prediction method for Chinese rural residences based on the randomness and seasonality in electricity usage behavior - Pengli Yuan; Lin Duanmu; Zongshan Wang; Ke Gao; Xinyi Zhao; Xintong Liu; Weihong Kong (Energy and Buildings, 2023)

Phthalocyanine-mediated interfacial self-assembly of magnetic graphene nanocomposites toward low-frequency electromagnetic wave absorption - Chenchen Liu; Shuning Liu; Xiaofang Feng; Ke Zhu; Guo Lin; Zhongxiang Bai; Lingling Wang; Xiaobo Liu (Chemical Engineering Journal, 2023)

Osteomodulin protects dental pulp stem cells from cisplatin-induced apoptosis in vitro - Ting Dong; Wen-zhen Lin; Xiao-han Zhu; Ke-yong Yuan; Li-li Hou; Zheng-wei Huang (Stem Cell Reviews and Reports, 2023)

Identification of three wheat near isogenic lines originated from CB037 on tissue culture and transformation capacities - Huiyun Liu; Haili Ma; Wei Zhang; Wanqing Wang; Jiajie Wu; Ke Wang; Zhishan Lin; Xingguo Ye (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Carotenoid components and their biosynthesis in a bud mutant of Shiranui mandarin (Citrus reticulata Blanco) with citrine flavedo - Xun Wang; Jinqiu Huang; Zongyan Yin; Ke Xu; Dong Jiang; Lijin Lin; Xiaoai Zhang; Zhihui Wang (Journal of Zhejiang University-SCIENCE B, 2023)

Preoperative Acute Sleep Deprivation Causes Postoperative Pain Hypersensitivity and Abnormal Cerebral Function - Meimei Guo; Yuxiang Wu; Danhao Zheng; Lei Chen; Bingrui Xiong; Jinfeng Wu; Ke Li; Li Wang; Kangguang Lin; Zongze Zhang; Anne Manyande; Fuqiang Xu; et al. (Neuroscience Bulletin, 2022)

Rapid Determination in the Quality Control of Chinese Patent Medicine - Shao Hua Lu; Ming Cai Zhang; Hong Lin Zhai; Ke Xin Bi; Bing Qiang Zhao (Journal of Pharmaceutical Innovation, 2022)

Immunotherapies for the Effective Treatment of Primary Autoimmune Cerebellar Ataxia: a Case Series - Jiao Li; Bo Deng; Wenli Song; Keru Li; Jingwen Ai; Xiaoni Liu; Haocheng Zhang; Yi Zhang; Ke Lin; Guofu Shao; Chunfeng Liu; Wenhong Zhang; et al. (The Cerebellum, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Sex Difference is a Determinant of Gut Microbes and Their Metabolites SCFAs/MCFAs in High Fat Diet Fed Rats - Ying Shi; Lin Wei; Lin Xing; Shanyu Wu; Fangzhi Yue; Ke Xia; Dongmei Zhang (Current Microbiology, 2022)

Adsorption of di (2-ethylhexyl) phthalate (DEHP) to microplastics in seawater: a comparison between pristine and aged particles - Ke Pan; Ciara Chun Chen; Lin Lin; Huo Xu; Fengyuan Chen; Yanping Li; Xiaoshan Zhu; Jie Ma; Wenlu Lan (Bulletin of Environmental Contamination and Toxicology, 2022)

Study on aptamer based high throughput approach identifies natural ingredients against RGNNV - Hongling Wei; Mingzhu Liu; Ke Ke; Shuangyan Xiao; Lin Huang; Qiongyu He; Changping Mo; Hai Pang; Guozhu Xiao; Pengfei Li; Qing Yu (Journal of Fish Diseases, 2022)
Nervous necrosis virus (NNV) is one of the most destructive pathogens in marine fish aquaculture and is capable of infecting more than 50 fish species worldwide, which resulted in great economic losses. Effective drugs for managing NNV infection are urgently required. Medicinal plants have been known for thousands of years and benefit of medicinal plants against pathogens in aquaculture have emerged. Nowadays, the most commonly used method for detecting virus infection and assessing antiviral drugs efficacy is reverse transcription‐quantitative real‐time PCR. However, the application is limited on account of high reagent costs, complex time‐consuming operations and long detection time. Aptamers have been widely applied in application of pathogens or diseases diagnosis and treatments because of high specificity, strong affinity, good stability, easy synthesized and low costs. This study aimed to establish an aptamer (GBN34)‐based high‐throughput screening (GBN34‐AHTS) model for efficient selection and evaluation of natural ingredients against NNV infection. GBN34‐AHTS is an expeditious rapid method for selecting natural ingredients against NNV, which is characterized with high‐speed, dram, sensitive and accurate. AHTS strategy could reduce work intensity and experimental costs and shorten the whole screening cycle of effective ingredients. AHTS should be suitable for rapid selection of effective ingredients against other viruses, which is important for improving the prevention and controlling of aquatic diseases.

Feeding strategy trade-off and selection of marine nocturnal gastropods under predation risk - Shihui Lin; Xiaolong Gao; Mo Zhang; Mingxin Lyu; Caihuan Ke (Frontiers in Marine Science, 2022)
The circadian rhythm is one of the most crucial and universal biological rhythms in living organisms. As a typical nocturnal creature, the Pacific abalone ( Haliotis discus hannai ) exhibits rhythmic behaviors in terms of passively selecting whether to avoid predators or to forage, and active adaptation to light cycle changes is regulated by the biological clock. However, no basic data are available to help us to understand these rhythmic behaviors in the abalone species. In the present study, quantification of behavioral data for the abalone and its predator swimming crab Portunus trituberculatus in short-term (24 h) and long-term (40 days) polyculture scenarios suggests that the distance and duration of movement, percentage of feeding individuals, and cumulative duration of feeding of the abalone individuals were significantly lower under the short-term predation risk than the long-term predation risk. The concentrations of 5-hydroxytryptamine (5-HT), cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), and hexokinase (HK) in hemolymph, and expression levels of 5-HT1A receptor and 5-HT2 receptor in cerebral ganglion were significantly higher under the long-term predation risk than the short-term predation risk. The concentration of lactate dehydrogenase (LDH) and glycogen content in adductor muscle of the abalone was significantly higher under the short-term predation risk than the long-term predation risk, thereby implying their role in anaerobic metabolism and aerobic metabolism as primary energy sources under the short-term and long-term predation risk, respectively. The concentrations of 5-HT and cAMP, and the expression levels of Bmal1 and 5-HT2 receptor exhibited no significant signs of cosine rhythmicity under the short-term predation risk, but changes in the movement and feeding behaviors of the abalone still occurred at the night only. Correlation analysis shows that the expression levels of Bmal1 and Clock had significantly positive correlations with the circadian changes in the movement parameters of the abalone, thereby suggesting a dominant role in the rhythmic expression of endogenous circadian clock genes regulating the rhythmic behavior of the abalone. These findings provide new insights into the origin and evolution of biological rhythms in nocturnal marine animals and a reference for developing rational stock enhancement plans, and would improve protection for marine benthic biodiversity.

Revealing top-k dominant individuals in incomplete data based on spark environment - Ke Wang; Binge Cui; Jerry Chun-Wei Lin; Jimmy Ming-Tai Wu (Environment, Development and Sustainability, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Genome-Wide Association and Expression Analysis Revealed the Candidate Variants and Molecular Underpinnings of Cold-Stress Response in Large Yellow Croaker - Ning Suo; Yidi Wu; Zhixiong Zhou; Qian He; Huaqiang Bai; Huanling Lin; Qiaozhen Ke; Peng Xu (Marine Biotechnology, 2022)

How will Chinese cities reduce their carbon emissions? Evidence from spatial differences - Junna Yan; Zhonghua Zhang; Mingli Chen; Tao Lin; Ke Yuan (Environmental Science and Pollution Research, 2022)

Changes in plant anthocyanin levels in response to abiotic stresses: a meta-analysis - Wenjie Yan; Juanjuan Li; Xinyue Lin; Lina Wang; Xiaoxiao Yang; Xiangyu Xia; Yuxin Zhang; Shaoyu Yang; Hongbing Li; Xiping Deng; Qingbo Ke (Plant Biotechnology Reports, 2022)

Circular RNA circMTO1 suppressed the progression of renal cell carcinoma progression by sponging miR-211 and miR-204 - Ke Wang; Xiaofeng Lin (Mammalian Genome, 2022)

Intrauterine hyperglycemia impairs endometrial receptivity via up-regulating SGK1 in diabetes - Haiyan Xu; Jingyi Li; Luyang Jin; Dan Zhang; Bin Chen; Xinmei Liu; Xianhua Lin; Yiting Huang; Zhanghong Ke; Juan Liu; Lin Gao; Jianzhong Sheng; et al. (Science China Life Sciences, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Negative Poisson’s ratio and peripheral strain of an NPR anchor cable - Zhi-gang Tao; Hao-tian Xu; Shu-lin Ren; Long-ji Guo; Ke Qin; Yi-fei Zhu (Journal of Mountain Science, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Protein kinase Ime2 is associated with mycelial growth, conidiation, osmoregulation, and pathogenicity in Fusarium oxysporum - Jiling Xiao; Yi Zhang; Ke Yang; Yanying Tang; Lin Wei; Erming Liu; Zhihuai Liang (Archives of Microbiology, 2022)
Fusarium oxysporum f.sp. niveum is one of the most serious diseases impairing watermelon yield and quality. Inducer of meiosis 2 (Ime2) is the founding member of a family of serine/threonine protein kinases and plays important roles in yeasts and other filamentous fungi. In this study, we analyzed the functions of Fo Ime2, the ortholog of Saccharomyces cerevisiae Ime2 in F. oxysporum f.sp. niveum . The FoIme2 -deleted mutants exhibited obvious morphological abnormalities, including slower vegetative growth, more branches in the edge hyphae and a reduction in conidia production. Compared to the wild type, the mutants were hypersensitive to the osmotic stressor NaCl but were more insensitive to the membrane stressor SDS. The deletion of FoIme2 also caused a reduction in pathogenicity. Transcriptional analysis revealed that Fo Ime2 acts downstream of Fo Opy2 which is an upstream sensor of the MAPK kinase cascade. These results indicate that Fo Ime2 is important in the development and pathogenicity of F. oxysporum, and provide new insight for the analysis of the pathogenic mechanism of F. oxysporum.

Risk of aquaculture-derived microplastics in aquaculture areas: An overlooked issue or a non-issue? - Lin Lin; Ciara Chun Chen; Xiaoshan Zhu; Ke Pan; Xiangrong Xu (Frontiers in Marine Science, 2022)
Plastic equipment such as fishing nets and foam buoys has been widely used in aquaculture. This kind of equipment would gradually decompose while being subject to the long-term effects of physical, chemical, and biological degradation processes, leading to the release of large amounts of microplastics (MPs) into the local marine environment and the generation of aquaculture-derived MPs (AD-MPs). The rapid growth of aquaculture has resulted in an explosion of AD-MPs with various environmental consequences. The accumulation of MPs in aquatic products was found closely related to the abundance of environmental MPs, suggesting the importance of determining whether AD-MPs increase the risk of MP ingestion by aquatic products and thus endanger aquatic food safety. In this short communication, the ecological and health risks of AD-MPs were discussed and perspectives were proposed for future studies.

Meta-analysis of the effect of melatonin application on abiotic stress tolerance in plants - Xiaoxiao Yang; Jianhong Ren; Juanjuan Li; Xinyue Lin; Xiangyu Xia; Wenjie Yan; Yuxin Zhang; Xiping Deng; Qingbo Ke (Plant Biotechnology Reports, 2022)

Post-transcriptional control of bacterial nitrogen metabolism by regulatory noncoding RNAs - Yueyue Han; Chao Li; Yongliang Yan; Min Lin; Xiubin Ke; Yunhua Zhang; Yuhua Zhan (World Journal of Microbiology and Biotechnology, 2022)
Nitrogen metabolism is the most basic process of material and energy metabolism in living organisms, and processes involving the uptake and use of different nitrogen sources are usually tightly regulated at the transcriptional and post-transcriptional levels. Bacterial regulatory noncoding RNAs are novel post-transcriptional regulators that repress or activate the expression of target genes through complementarily pairing with target mRNAs; therefore, these noncoding RNAs play an important regulatory role in many physiological processes, such as bacterial substance metabolism and stress response. In recent years, a study found that noncoding RNAs play a vital role in the post-transcriptional regulation of nitrogen metabolism, which is currently a hot topic in the study of bacterial nitrogen metabolism regulation. In this review, we present an overview of recent advances that increase our understanding on the regulatory roles of bacterial noncoding RNAs and describe in detail how noncoding RNAs regulate biological nitrogen fixation and nitrogen metabolic engineering. Furthermore, our goal is to lay a theoretical foundation for better understanding the molecular mechanisms in bacteria that are involved in environmental adaptations and metabolically-engineered genetic modifications.

Diminished miR-374c-5p negatively regulates IL (interleukin)-6 in unexplained recurrent spontaneous abortion - Lin Zhao; Li Han; Guozhen Hei; Ran Wei; Zhen Zhang; Xiaoxiao Zhu; Qiang Guo; Chu Chu; Xiaoxiao Fu; Ke Xu; Xia Li (Journal of Molecular Medicine, 2022)

Construction and comprehensive analysis of a lncRNA–mRNA interactive network to reveal a potential lncRNA for hepatic encephalopathy development - Chihao Zhang; Wei Ni; Yiming Zhu; Jiayun Lin; Hongjie Li; Zhifeng Zhao; Ke Wang; Haizhong Huo; Meng Luo (Human Cell, 2022)

Testing the transfer functions for the Geonor T-200B and Chinese standard precipitation gauge in the central Qinghai—Tibet Plateau - Le-le Zhang; Li-ming Gao; Ji Chen; Lin Zhao; Ke-long Chen; Jing-yi Zhao; Guo-jun Liu; Ting-xi Song; Yan-kun Li (Journal of Mountain Science, 2022)

Probiotics Treatment of Leg Diseases in Broiler Chickens: a Review - Tingting Xu; Ke Yue; Chaodong Zhang; Xishuai Tong; Luxi Lin; Qinqin Cao; Shucheng Huang (Probiotics and Antimicrobial Proteins, 2022)

Molecular cloning, characterization and expression analysis of two 12-oxophytodienoate reductases (NtOPR1 and NtOPR2) from Nicotiana tabacum - Feiyan Huang; Farhat Abbas; Dylan O’Neill Rothenberg; Muhammad Imran; Sajid Fiaz; Naveed ur Rehman; Sikandar Amanullah; Afifa Younas; Yan Ding; Xianjie Cai; Xiaolong Chen; Lei Yu; et al. (Molecular Biology Reports, 2022)

Comparison of different inversion methods of D-T2 two-dimensional nuclear magnetic resonance logging and applicability analysis - Cheng-Lin Li; Mao-Jin Tan; Ke-Wen Wang; Feng Zhou; Ying-Ming Liu; Hai-Tao Zhang; Li-Zhi Xiao (Applied Geophysics, 2022)

Community Structure of Benthic Macrofauna and the Ecological Quality of Mangrove Wetlands in Hainan, China - Ping Li; Jingli Liu; Jiankun Bai; Yifan Tong; Yuchen Meng; Xiaoping Diao; Ke Pan; Xiaoshan Zhu; Guanghui Lin (Frontiers in Marine Science, 2022)
Few studies have systematically assessed the ecological status of mangrove wetlands following the stress of anthropogenic activities in China. This study investigated the spatial and seasonal distribution of benthic macroinvertebrate communities and assessed the ecological quality of mangrove habitats on an island scale in Hainan, China (containing the third largest mangrove area of China and the highest mangrove species richness). For the benthic macrofauna community structure, a total of 102 macrobenthic taxa belonging to 50 families were identified, with Crustaceans, Molluscs, Polychaetes, and Oligochaeta having relative abundances of 52.3%, 36.1%, 10.8%, and 0.8%, respectively. Decapoda and Gastropoda dominated the benthic community abundance. Non-metric multidimensional scaling and an analysis of similarities revealed significantly different macroinvertebrate assemblages among the regions during the two seasons. The South mangroves had the lowest macrofauna species numbers, biodiversity, richness, and abundance. The macrofaunal species richness, Shannon index, Margalef index, abundance, and biomass markedly affected by region and season. As indicated by the biotic indices AMBI (AZTI’s Marine Biotic Index) and M-AMBI, more than half of the mangrove habitats on Hainan Island were slightly to heavily disturbed and had poor to moderate ecological quality. Our results recommend long-term monitoring for evaluating the quality status of mangrove wetlands and avoiding extensive land-use conversion of mangroves. Holistic approaches considering ecological characteristics and combining information on both floral and faunal functionality would contribute to the effective management and conservation of mangroves in disturbed areas.

Metabolic tuning of a stable microbial community in the surface oligotrophic Indian Ocean revealed by integrated meta-omics - Zhang-Xian Xie; Ke-Qiang Yan; Ling-Fen Kong; Ying-Bao Gai; Tao Jin; Yan-Bin He; Ya-Yu Wang; Feng Chen; Lin Lin; Zhi-Long Lin; Hong-Kai Xu; Zong-Ze Shao; et al. (Marine Life Science & Technology, 2022)
Understanding the mechanisms, structuring microbial communities in oligotrophic ocean surface waters remains a major ecological endeavor. Functional redundancy and metabolic tuning are two mechanisms that have been proposed to shape microbial response to environmental forcing. However, little is known about their roles in the oligotrophic surface ocean due to less integrative characterization of community taxonomy and function. Here, we applied an integrated meta-omics-based approach, from genes to proteins, to investigate the microbial community of the oligotrophic northern Indian Ocean. Insignificant spatial variabilities of both genomic and proteomic compositions indicated a stable microbial community that was dominated by Prochlorococcus , Synechococcus , and SAR11. However, fine tuning of some metabolic functions that are mainly driven by salinity and temperature was observed. Intriguingly, a tuning divergence occurred between metabolic potential and activity in response to different environmental perturbations. Our results indicate that metabolic tuning is an important mechanism for sustaining the stability of microbial communities in oligotrophic oceans. In addition, integrated meta-omics provides a powerful tool to comprehensively understand microbial behavior and function in the ocean.

Shinella oryzae sp. nov., a novel zearalenone-resistant bacterium isolated from rice paddy soil - Ruyu Gao; Juan Zheng; Wei Lu; Xiubin Ke; Ming Chen; Min Lin; Wei Zhang; Zhengfu Zhou (Antonie van Leeuwenhoek, 2022)

EV-T synergizes with AZD5582 to overcome TRAIL resistance through concomitant suppression of cFLIP, MCL-1, and IAPs in hepatocarcinoma - Kui Su; Qian Yuan; Huan Hou; Changhong Ke; Chaohong Huang; Shuyi Li; Jianwu Sun; Xin Yuan; Yue Lin; Yiqing Chen; Huijuan Xin; Xiaoping Liang; et al. (Journal of Molecular Medicine, 2022)

The RNA-binding protein SND1 promotes the degradation of GPX4 by destabilizing the HSPA5 mRNA and suppressing HSPA5 expression, promoting ferroptosis in osteoarthritis chondrocytes - Min Lv; Yuanzhen Cai; Weikun Hou; Kan Peng; Ke Xu; Chao Lu; Wenxing Yu; Weisong Zhang; Lin Liu (Inflammation Research, 2022)

Genetic diversity and population structure of Curcuma alismatifolia Gagnep. accessions revealed by SSR markers - Hui-Wen Yu; Ling-Jun Ke; Yi-Lan Xiao; Si-Jia Chen; Yuan-Yuan Li; Qi-Lin Tian; Yun-He Li; Jin-Shui Lin; Luan-Mei Lu (Genetic Resources and Crop Evolution, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Highly selective monoclonal antibody-based lateral flow immunoassay for visual and sensitive determination of conazole fungicides propiconazole in vegetables - Ze-Ke Xu; Jing-Nan Meng; Yi Lei; Xing-Xing Yang; Yi-Yong Yan; Hai-Hong Liu; Hong-Tao Lei; Ting-Cai Wang; Xing Shen; Zhen-Lin Xu (Food Additives & Contaminants: Part A, 2022)

Lactoferrin promotes the autophagy activity during osteoblast formation via BCL2-Beclin1 signaling - Dianshan Ke; Xinwen Wang; Yinquan Lin; Shengwang Wei (Molecular Biology Reports, 2022)

Characteristics of fine particulate matter (PM2.5) at Jinsha Site Museum, Chengdu, China - Jialin Deng; Luman Jiang; Wenwen Miao; Junke Zhang; Guiming Dong; Ke Liu; Juncheng Chen; Tong Peng; Yao Fu; Yunpei Zhou; Xue Huang; Mengqian Hu; et al. (Environmental Science and Pollution Research, 2022)

Pilot study on the treatment of low carbon and nitrogen ratio municipal sewage by A1/O2/A3/A4/O5 sludge-membrane coupling process with multi-point inflow - De-Wei Zhang; Jun-Tian Zheng; Jun Zheng; Meng-Ke Zhao; Meng-Lin Wang; Shi-Hua Zhang (Environmental Science and Pollution Research, 2022)

The effects of immersive garden experience on the health care to elderly residents with mild-to-moderate cognitive impairment living in nursing homes after the COVID-19 pandemic - Chung-Heng Hsieh; Cheng-Min Chen; Ju-Yuan Yang; Yen-Ju Lin; Man-Li Liao; Ke-Hsin Chueh (Landscape and Ecological Engineering, 2022)

M1 macrophages-derived exosomes miR-34c-5p regulates interstitial cells of Cajal through targeting SCF - Su Xu; Jinhai Zhai; Ke Xu; Xingguo Zuo; Chenghua Wu; Tao Lin; Li Zeng (Journal of Biosciences, 2021)

The effects of extreme temperatures on emergency room visits—a population-based analysis by age, sex, and comorbidity - Yu-Kai Lin; Yasmin Zafirah; Meng-Ting Ke; Gerry Andhikaputra; Yu-Chun Wang (International Journal of Biometeorology, 2021)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Effects of Flow Velocity on the Growth and Survival of Haliotis discus hannai Larvae in the Recirculating Upflow System From the Point of Energy Metabolism - Mo Zhang; Xiaolong Gao; Mingxin Lyu; Shihui Lin; Ying Su; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
For the abalone Haliotis discus hannai , attachment and metamorphosis are crucial stages in the transition from planktonic to benthic life. Increasing the larval metamorphosis rate by artificially controlling the external environment and simulating natural seawater flow is vital to enhance the hatchery efficiency of H. discus hannai . Thus, in the current study, an upflow recirculating aquaculture unit was designed for the rearing of larval abalone, and the larval hatching rate, survival rate, mode of energy metabolism, and expression levels of metamorphosis-related genes at different flow velocities (0, 5, 10, 20, and 40 L/h) were compared and analyzed. At flow velocities less than 20 L/h, no significant differences occurred in larval hatching, survival, and metamorphosis rates, whereas significant differences were recorded at flow rates of 20 and 40 L/h. Differences were also observed in the activity of enzymes, such as hexokinase (HK), pyruvate kinase (PK), lactate dehydrogenase (LDH), succinate dehydrogenase (SDH), and malate dehydrogenase (MDH), as well as glycogen levels, at the higher flow rates. These results suggested that velocity in excess of a certain limit leads to a higher glycolysis rate and transition of energy utilization from aerobic to anaerobic metabolism for the abalone larvae. Compared with conventional still-water aquacultural systems, the flow velocity at 5–10 L/h could maintain the water environment stability, and avoid both fertilized eggs from being densely deposited before hatching and the consumption of energy needed to resist high flow velocities. Thus, these results are useful references to enhance the hatchery efficiency, and to conduct large-scale rearing, of abalone larvae.

Aquimarina algicola sp. nov., isolated from the surface of a marine red alga - Xun-Ke Sun; Yan-Lin Zhong; Xu-Yang Chen; Guan-Jun Chen; Zong-Jun Du (Archives of Microbiology, 2021)

Mapping coastal wetlands in the Yellow River Delta, China during 2008–2019: impacts of valid observations, harmonic regression, and critical months - Zhanpeng Wang; Yinghai Ke; Mengmeng Chen; Demin Zhou; Lin Zhu; Junhong Bai (International Journal of Remote Sensing, 2021)

Master regulator NtrC controls the utilization of alternative nitrogen sources in Pseudomonas stutzeri A1501 - Zhimin Yang; Qin Li; Yongliang Yan; Xiubin Ke; Yueyue Han; Shaoyu Wu; Fanyang Lv; Yahui Shao; Shanshan Jiang; Min Lin; Yunhua Zhang; Yuhua Zhan (World Journal of Microbiology and Biotechnology, 2021)
Pseudomonas stutzeri A1501 is a model strain used to study associative nitrogen fixation, and it possesses the nitrogen regulatory NtrC protein in the core genome. Nitrogen sources represent one of the important factors affecting the efficiency of biological nitrogen fixation in the natural environment. However, the regulation of NtrC during nitrogen metabolism in P. stutzeri A1501 has not been clarified. In this work, a phenotypic analysis of the ntrC mutant characterized the roles of NtrC in nitrogen metabolism and the oxidative stress response of P. stutzeri A1501. To systematically identify NtrC-controlled gene expression, RNA-seq was performed to further analyse the gene expression differences between the wild-type strain and the ∆ ntrC mutant under nitrogen fixation conditions. A total of 1431 genes were found to be significantly altered by ntrC deletion, among which 147 associative genes had NtrC-binding sites, and the pathways for nitrogen fixation regulation, nitrogenous compound acquisition and catabolism and nitrate assimilation were discussed. Furthermore, the oxidative stress-related gene ( katB ), which was upregulated by ntrC deletion, was suggested to be a potential target gene of NtrC, thus highlighting the importance of NtrC in nitrogenase protection against oxygen damage. Based on these findings, we propose that NtrC is a high-ranking element in the regulatory network of P. stutzeri A1501 that controls a variety of nitrogen metabolic and oxidative stress responsive traits required for adaptation to complex rhizosphere environments.

Patterns and trajectories of macrophyte change in East China’s shallow lakes over the past one century - Feifan Huang; Ke Zhang; Shixin Huang; Qi Lin (Science China Earth Sciences, 2021)

Comparative Study of the Feeding Characteristics and Digestion Physiology of Haliotis discus hannai and Haliotis gigantea - Mingxin Lyu; Xiaolong Gao; Mo Zhang; Shihui Lin; Xuan Luo; Weiwei You; Caihuan Ke (Frontiers in Marine Science, 2021)
Abalone ( Haliotis spp.) are typical nocturnal creatures but Haliotis discus hannai is bold and active in the nighttime whereas H. gigantea tends to be timid and inactive. In this study, we quantified and compared differences in movement, feeding, and digestive physiology between H. discus hannai and H. gigantea as well as the potential molecular mechanisms on the basis of video observations and expression levels of genes related to feeding regulation. The feeding behaviors of both species were characterized by significant circadian rhythms ( P < 0.05). However, the distance moved and the cumulative duration of movement were 2.61 and 1.94 times higher, respectively, in H. discus hannai than in H. gigantea over the 24-h cycle. The cumulative duration of feeding by H. discus hannai was only 1.15 times that by H. gigantea , but the feeding time as a percentage of the cumulative duration of movement (FTP) was up to 94.6% for H. gigantea and only 56.0% for H. discus hannai . The peaks for α-amylase activity and NPF expression levels in both species as well as the peak OX 2 R expression level in H. gigantea occurred during 20:00–00:00 h. By contrast, the peaks for alginate lyase activity and NPYR expression levels in H. discus hannai occurred at 16:00 h, when the FTP was significantly higher for H. discus hannai than for H. gigantea . These initial findings quantify specific behavior parameters and thus provide a reference for the selection of appropriate feeding strategies and the proliferation of abalone via bottom sowing.

Synergistic impacts of nutrient enrichment and climate change on long‐term water quality and ecological dynamics in contrasting shallow‐lake zones - Qi Lin; Ke Zhang; Suzanne McGowan; Eric Capo; Ji Shen (Limnology and Oceanography, 2021)
Anthropogenic and climatic stressors on freshwater ecosystems are of global concern. However, the interactions and effects of multiple stressors (e.g., nutrient enrichment, climate warming, altered wind and precipitation) acting over different spatial and temporal scales are often complex and remain controversial. Here, we reconstructed one‐century dynamics of eutrophication and primary producer communities in algal‐dominated and macrophyte‐dominated zones of a large shallow lake (Taihu, China), by integrating sedimentary photosynthetic pigments and geochemical records with water monitoring and historical archives. We aimed to explore the long‐term underlying mechanisms of the responses of water quality and lake biota to multiple environmental perturbations. We found that water quality degradation and algal community modification showed similar trends but distinct timings and trajectories in contrasting ecological zones. Onset and intensity of eutrophication in north Meiliang Bay (since the 1950s) exceeded far beyond that of macrophyte‐dominated Eastern Taihu (~1990s). Anthropogenic nutrients overtook past climatic control on production and composition of phototrophic assemblages. More importantly, lake phytoplankton responded markedly to climate warming, decreasing wind speed, and extreme weathers after cultural eutrophication. Synergistic interactions of nutrients and climate on lake ecosystems became increasingly significant in promoting harmful algal blooms (HABs) dominated by Microcystis , close to the hyper‐eutrophic north lake zones. The asynchronous limnological and ecological responses also indicated the modulating roles of lake ecological regime and catchment hydrogeomorphic characteristic. Collectively, our findings suggest that mitigation of eutrophication and HABs calls for a triple management strategy integrating anthropogenic nutrients, climate change, and lake‐catchment setting.

Epididymal initial segment-specific Cre recombinase activity in Lcn8-Cre knock-in mice - Qian-qian Gong; Zhi-lin Dou; Xiao Wang; Ke-yi Zhang; Hao Chen; Jian-gang Gao; Xiao-yang Sun (Molecular Biology Reports, 2021)

Mid-Level Riverine Outflow Matters: A Case of Microplastic Transport in the Jiulong River, China - Yifan Li; Siguang Liu; Mengyang Liu; Wei Huang; Kai Chen; Yongcheng Ding; Fangzhu Wu; Hongwei Ke; Linghao Lou; Yan Lin; Mingyu Zhang; Fengjiao Liu; et al. (Frontiers in Marine Science, 2021)
Riverine outflow is one of the major pathways for microplastic transportation to coastal environments. Research on the output of microplastics in small- or medium-sized rivers will help accurately understand the status of their marine loads. In this study, we used both trawling and pumping methods to collect microplastics of different sizes in the Jiulong River Estuary and Xiamen Bay. We found that the abundance of small microplastics (44 μm–5.0 mm) was at least 20 times higher than the large particles (0.33–5.0 mm). The abundance of the large particles ranges from 4.96 to 16.3 particles/m 3 , and that of the small particles ranged from 82.8 to 918 particles/m 3 . Granule was the dominant shape (>60%), and polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) were the most common components. The riverine flux of small microplastics (44 μm–5 mm, 472 ± 230 t/y) was at a medium level and was eight times greater than that of large particles (0.33–5.0 mm, 61.2 ± 2.6 t/y). The behavior of the large microplastics was relatively conservative, whose abundance had a significant correlation with salinity ( R 2 = 0.927) and was mainly influenced by physical factors. In contrast, results of statistical analysis revealed that more complicated factors influenced the small microplastics.

Identification of a delayed leaf greening gene from a mutation of pummelo - Hui-Wen Yu; Zhi-Hao Lu; Xia Wang; Dan Liu; Jia-Xian He; Xiao-Lin Jiang; Ling-Jun Ke; Wen-Wu Guo; Xiu-Xin Deng; Qiang Xu (Science China Life Sciences, 2021)

RETRACTED ARTICLE: Antioxidative effects of polypyrimidine tract-binding protein-associated splicing factor against pathological retinal angiogenesis through promotion of mitochondrial function - Lijie Dong; Tingting Lin; Wenbo Li; Yaru Hong; Xinjun Ren; YiFeng Ke; Xiaomin Zhang; Xiaorong Li (Journal of Molecular Medicine, 2021)

Application of physiologically based pharmacokinetic modeling to predict the pharmacokinetics of telavancin in obesity with renal impairment - Wanhong Wu; Meng Ke; Lingling Ye; Cuihong Lin (European Journal of Clinical Pharmacology, 2021)

Actirhodobacter atriluteus gen. nov., sp. nov., isolated from the surface water of the Yellow Sea - Hua-Peng Xue; Dao-Feng Zhang; Lin Xu; Xiang-Ning Wang; Ai-Hua Zhang; Jian-Ke Huang; Chuang Liu (Antonie van Leeuwenhoek, 2021)

Blocking the JAK2/STAT3 and ERK pathways suppresses the proliferation of gastrointestinal cancers by inducing apoptosis - Xi Wang; Chunyan Dai; Yifei Yin; Lin Wu; Weiyang Jin; Yufei Fu; Zhe Chen; Ke Hao; Bin Lu (Journal of Zhejiang University-SCIENCE B, 2021)

Detection of Human Sapoviruses in Sewage in China by Next Generation Sequencing - Ke Song; Xiaojuan Lin; Yao Liu; Feng Ji; Li Zhang; Peng Chen; Chenxu Zhao; Yanyan Song; Zexin Tao; Aiqiang Xu (Food and Environmental Virology, 2021)

Development and evaluation of a serological test for diagnosis of COVID-19 with selected recombinant spike proteins - Pingping Zhang; Qi Gao; Tang Wang; Yuehua Ke; Fei Mo; Ruizhong Jia; Wanbing Liu; Lei Liu; Shangen Zheng; Yuzhen Liu; Luping Li; Yao Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased resting state functional irregularity of T2DM brains with high HbA1c: sign for impaired verbal memory function? - Xin Zhang; Ying Yu; Zhe-Sheng Shi; Ke Xu; Jia-Hao Feng; Ze-Yang Li; Xiang-Nan Zhang; Shu-Ning Shen; Yang Yang; Lin-Feng Yan; Jin Zhang; Qian Sun; et al. (Brain Imaging and Behavior, 2021)

Genome-Wide Association Study Identifies Genomic Loci of Sex Determination and Gonadosomatic Index Traits in Large Yellow Croaker (Larimichthys crocea) - Huanling Lin; Zhixiong Zhou; Ji Zhao; Tao Zhou; Huaqiang Bai; Qiaozhen Ke; Fei Pu; Weiqiang Zheng; Peng Xu (Marine Biotechnology, 2021)

Identification of contaminants as members of the Bacillus pumilus group and analysis of contamination sources in the cultivation of Pleurotus geesteranus mushrooms - Na Lu; Wei-Dong Yuan; You-Liang Wu; Ji-Ling Song; Lin Ma; Wei-Ke Wang; Jing Yan; Zai-Ming Chen; Qing Chen (Journal of Plant Pathology, 2021)

ERP evidence for asymmetric orthographic transfer between traditional and simplified Chinese - Jiushu Xie; Yanli Huang; Ke Chen; Qian Lin; John X. Zhang; Lei Mo (Experimental Brain Research, 2021)

Community structure of bacterioplankton and its relationship with environmental factors in the upper reaches of the Heihe River in Qinghai Plateau - Zhang Qian‐Qian; Jian Sheng‐Long; Li Ke‐Mao; Wu Zhen‐Bing; Guan Hong‐Tao; Hao Jin‐Wen; Wang Shu‐Yi; Lin Yao‐Yao; Wang Guo‐Jie; Li Ai‐Hua (Environmental Microbiology, 2021)
Summary Planktonic microorganisms play a key role in the biogeochemical processes of the aquatic system, and they may be affected by many factors. High‐throughput sequencing technology was used in this study to investigate and study the bacterioplankton community of water bodies in the upper reaches of the Heihe River Basin in Qinghai Plateau. Results showed that Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria are the predominant phyla in this river section, while the main genera are Thiomonas , Acidibacillus , Acidocella , Rhodanobacter , Acidithiobacter and Gallionella , which are autochthonous in the acid‐mine drainage. Additionally, total nitrogen, total phosphorus, permanganate index and pH are significantly correlated with the bacterioplankton abundance and are the main limiting factors for the spatial distribution of the bacterioplankton. PICRUSt inferred that the mainstream microbial assemblages had a higher abundance of KOs belong to metabolism of terpenoids and polyketides, while the tributary had higher abundance of KOs belong to the immune system. The relationship between bacterioplankton community composition and environmental factors in the Heihe River basin was discussed for the first time in this study, which provides a theoretical basis for the healthy, orderly development of the water environment in the Heihe River Basin.

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Screening and functional characterization of candidate resistance genes to powdery mildew from Dasypyrum villosum#4 in a wheat line Pm97033 - Shijin Li; Zimiao Jia; Ke Wang; Lipu Du; Hongjie Li; Zhishan Lin; Xingguo Ye (Theoretical and Applied Genetics, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Genome-Wide Association Study of Body Shape-Related Traits in Large Yellow Croaker (Larimichthys crocea) - Shengnan Kong; Zhixiong Zhou; Tao Zhou; Ji Zhao; Lin Chen; Huanling Lin; Fei Pu; Qiaozhen Ke; Huaqiang Bai; Peng Xu (Marine Biotechnology, 2020)

Identification of Prognostic Signatures of Alternative Splicing in Glioma - Yu Zeng; Peidong Zhang; Xizhao Wang; Ke Wang; Mingfeng Zhou; Hao Long; Jie Lin; Zhiyong Wu; Liang Gao; Ye Song (Journal of Molecular Neuroscience, 2020)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Stable isotopes reveal effects of natural drivers and anthropogenic pressures on isotopic niches of invertebrate communities in a large subtropical river of China - Sai Wang; Lin-Hui Su; Bang-Ke Luo; Ying-Jun Qin; Simon D. Stewart; Jin-Peng Tang; Tuan-Tuan Wang; Yang Yang; Gong Cheng (Environmental Science and Pollution Research, 2020)

Evolution of Neolithic site distribution (9.0–4.0 ka BP) in Anhui, East China - Li Wu; Xiaoling Sun; Wei Sun; Cheng Zhu; Tongxin Zhu; Shuguang Lu; Hui Zhou; Qingchun Guo; Houchun Guan; Wei Xie; Rui Ke; Guiping Lin (Journal of Geographical Sciences, 2020)

Protective effect of apigenin on d-galactosamine/LPS-induced hepatocellular injury by increment of Nrf-2 nucleus translocation - Rui-Jun Zhou; Ying Zhao; Ke Fan; Mei-Lin Xie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Gut microbial diversity across a contact zone for California voles: Implications for lineage divergence of hosts and mitonuclear mismatch in the assembly of the mammalian gut microbiome - Dana Lin; Eileen A. Lacey; Bryan H. Bach; Ke Bi; Christopher J. Conroy; Anton Suvorov; Rauri C. K. Bowie (Molecular Ecology, 2020)
Gut microbial diversity is thought to reflect the co‐evolution of microbes and their hosts as well as current host‐specific attributes such as genetic background and environmental setting. To explore interactions among these parameters, we characterized variation in gut microbiome composition of California voles ( Microtus californicus ) across a contact zone between two recently diverged lineages of this species. Because this contact zone contains individuals with mismatched mitochondrial‐nuclear genomes (cybrids), it provides an important opportunity to explore how different components of the genotype contribute to gut microbial diversity. Analyses of bacterial 16S rRNA sequences and joint species distribution modelling revealed that host genotypes and genetic differentiation among host populations together explained more than 50% of microbial community variation across our sampling transect. The ranked importance (most to least) of factors contributing to gut microbial diversity in our study populations were: genome‐wide population differentiation, local environmental conditions, and host genotypes. However, differences in microbial communities among vole populations (β‐diversity) did not follow patterns of lineage divergence (i.e., phylosymbiosis). Instead, among‐population variation was best explained by the spatial distribution of hosts, as expected if the environment is a primary source of gut microbial diversity (i.e., dispersal limitation hypothesis). Across the contact zone, several bacterial taxa differed in relative abundance between the two parental lineages as well as among individuals with mismatched mitochondrial and nuclear genomes. Thus, genetic divergence among host lineages and mitonuclear genomic mismatches may also contribute to microbial diversity by altering interactions between host genomes and gut microbiota (i.e., hologenome speciation hypothesis).

Epitranscriptomic technologies and analyses - Xiaoyu Li; Qiao-Xia Liang; Jin-Ran Lin; Jinying Peng; Jian-Hua Yang; Chengqi Yi; Yang Yu; Qiangfeng Cliff Zhang; Ke-Ren Zhou (Science China Life Sciences, 2020)

Weakening Laws of Mechanical Properties of Sandstone Under the Effect of Chemical Corrosion - Yun Lin; Keping Zhou; Jielin Li; Bo Ke; Rugao Gao (Rock Mechanics and Rock Engineering, 2020)

Rock mass permeability classification schemes to facilitate groundwater availability assessment in mountainous areas: a case study in Jhuoshuei river basin of Taiwan - Shih-Meng Hsu; Jun-Pu Hsu; Chien-Chung Ke; Yen-Tsu Lin; Chi-Chao Huang (Geosciences Journal, 2020)

Optimization of the OCO-2 Cloud Screening Algorithm and Evaluation against MODIS and TCCON Measurements over Land Surfaces in Europe and Japan - Sijie Chen; Shuaibo Wang; Lin Su; Changzhe Dong; Ju Ke; Zhuofan Zheng; Chonghui Cheng; Bowen Tong; Dong Liu (Advances in Atmospheric Sciences, 2020)

Simulation of the Pharmacokinetics of Oseltamivir and Its Active Metabolite in Normal Populations and Patients with Hepatic Cirrhosis Using Physiologically Based Pharmacokinetic Modeling - Yong Chen; Meng Ke; Jianwen Xu; Cuihong Lin (AAPS PharmSciTech, 2020)

Chronic ketamine abuse is associated with orexin-A reduction and ACTH elevation - Ming-Chyi Huang; Chun-Hsin Chen; Lian-Yu Chen; Hu-Ming Chang; Chih-Ken Chen; Shih-Ku Lin; Ke Xu (Psychopharmacology, 2020)

Analyzing the action of evolutionarily conserved modules on HMW-GS 1Ax1 promoter activity - Luning Duan; Shichen Han; Ke Wang; Peihong Jiang; Yunsong Gu; Lin Chen; Junyi Mu; Xingguo Ye; Yaxuan Li; Yueming Yan; Xiaohui Li (Plant Molecular Biology, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Downregulation of LncRNA GAS5 promotes liver cancer proliferation and drug resistance by decreasing PTEN expression - Congren Wang; Shaoying Ke; Mingzhu Li; Conglin Lin; Xiaoyu Liu; Qunxiong Pan (Molecular Genetics and Genomics, 2020)

A multidecadal change analysis for irrigation ponds in Taoyuan, Taiwan, using multisource data - Yen-Ching Chen; Wei-Chun Lin; Lin-Hsuan Hsiao; Ke-Sheng Cheng (Paddy and Water Environment, 2020)

Predicting 3D heterogeneous in situ stress field of Gaoshangpu Oilfield northern area, Nanpu Sag, Bohai Bay Basin, China - Ke Xu; Junsheng Dai; Jianwei Feng; Bifeng Wang; Lin Shang; Lu Fang; Shuo Wang (Arabian Journal of Geosciences, 2020)

Bifidobacterium bifidum TMC3115 Can Characteristically Influence Glucose and Lipid Profile and Intestinal Microbiota in the Middle-Aged and Elderly - Ke Wang; Xiaohong Yu; Yi Li; Yun Guo; Lin Ge; Fangfang Pu; Xinying Ma; Wenjing Cui; Francesco Marrota; Fang He; Ming Li (Probiotics and Antimicrobial Proteins, 2019)

The Alterations of Copper and Zinc Homeostasis in Acute Appendicitis and the Clinical Significance - Wenhao Lin; Wei Han; Ke Wen; Sunhua Huang; Yao Tang; Zhexuan Lin; Ming Han (Biological Trace Element Research, 2019)

A Bregman adaptive sparse-spike deconvolution method in the frequency domain - Shu-Lin Pan; Ke Yan; Hai-Qiang Lan; Zi-Yu Qin (Applied Geophysics, 2019)

Investigating the Transport Mechanism of PM2.5 Pollution during January 2014 in Wuhan, Central China - Miaomiao Lu; Xiao Tang; Zifa Wang; Lin Wu; Xueshun Chen; Shengwen Liang; Hui Zhou; Huangjian Wu; Ke Hu; Longjiao Shen; Jia Yu; Jiang Zhu (Advances in Atmospheric Sciences, 2019)
Severe haze pollution that occurred in January 2014 in Wuhan was investigated. The factors leading to Wuhan’s PM 2.5 pollution and the characteristics and formation mechanism were found to be significantly different from other megacities, like Beijing. Both the growth rates and decline rates of PM 2.5 concentrations in Wuhan were lower than those in Beijing, but the monthly PM 2.5 value was approximately twice that in Beijing. Furthermore, the sharp increases of PM 2.5 concentrations were often accompanied by strong winds. A high-precision modeling system with an online source-tagged method was established to explore the formation mechanism of five haze episodes. The long-range transport of the polluted air masses from the North China Plain (NCP) was the main factor leading to the sharp increases of PM 2.5 concentrations in Wuhan, which contributed 53.4% of the monthly PM 2.5 concentrations and 38.5% of polluted days. Furthermore, the change in meteorological conditions such as weakened winds and stable weather conditions led to the accumulation of air pollutants in Wuhan after the long-range transport. The contribution from Wuhan and surrounding cities to the PM 2.5 concentrations was determined to be 67.4% during this period. Under the complex regional transport of pollutants from surrounding cities, the NCP, East China, and South China, the five episodes resulted in 30 haze days in Wuhan. The findings reveal important roles played by transregional and intercity transport in haze formation in Wuhan.

Resource (Light and Nitrogen) and Density-Dependence of Seaweed Growth - Xi Xiao; Susana Agusti; Fang Lin; Caicai Xu; Yan Yu; Yaoru Pan; Ke Li; Jiaping Wu; Carlos M. Duarte (Frontiers in Marine Science, 2019)

Different calcification responses of two hermatypic corals to CO2-driven ocean acidification - Xinqing Zheng; Fuwen Kuo; Ke Pan; Haining Huang; Rongcheng Lin (Environmental Science and Pollution Research, 2019)

Seasonal Dynamics of Gastrointestinal Nematode Infections of Goats and Emergence of Ivermectin Resistance in Haemonchus contortus in Hubei Province, China - Wei Yuan; Ke Lu; Hao Li; Jinming Liu; Chuanchuan He; Jintao Feng; Xin Zhang; Yudan Mao; Yang Hong; Yu Zhou; Jun Lu; Yamei Jin; et al. (Acta Parasitologica, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

Different intensity of autophagy regulate interleukin-33 to control the uncontrolled inflammation of acute lung injury - Ming Lei; Chuan-jiang Wang; Feng Yu; Ke Xie; Shi-hui Lin; Fang Xu (Inflammation Research, 2019)

Study on Properties of Grouting Materials and Reinforcement Effect in Coal Roadways Influenced by Dynamic Pressure - Zeng-qiang Yang; Chang Liu; Yun Dong; Lin-ming Dou; Jing-ke Wu (Geotechnical and Geological Engineering, 2019)

Recent advances in carbohydrate-based cancer vaccines - Ke-Tao Jin; Huan-Rong Lan; Xiao-Yi Chen; Shi-Bing Wang; Xiao-Jiang Ying; Yan Lin; Xiao-Zhou Mou (Biotechnology Letters, 2019)

Host genetic determinants of the gut microbiota of wild mice - Taichi A. Suzuki; Megan Phifer‐Rixey; Katya L. Mack; Michael J. Sheehan; Dana Lin; Ke Bi; Michael W. Nachman (Molecular Ecology, 2019)
Identifying a common set of genes that mediate host–microbial interactions across populations and species of mammals has broad relevance for human health and animal biology. However, the genetic basis of the gut microbial composition in natural populations remains largely unknown outside of humans. Here, we used wild house mouse populations as a model system to ask three major questions: (a) Does host genetic relatedness explain interindividual variation in gut microbial composition? (b) Do population differences in the microbiota persist in a common environment? (c) What are the host genes associated with microbial richness and the relative abundance of bacterial genera? We found that host genetic distance is a strong predictor of the gut microbial composition as characterized by 16S amplicon sequencing. Using a common garden approach, we then identified differences in microbial composition between populations that persisted in a shared laboratory environment. Finally, we used exome sequencing to associate host genetic variants with microbial diversity and relative abundance of microbial taxa in wild mice. We identified 20 genes that were associated with microbial diversity or abundance including a macrophage‐derived cytokine ( IL12a ) that contained three nonsynonymous mutations. Surprisingly, we found a significant overrepresentation of candidate genes that were previously associated with microbial measurements in humans. The homologous genes that overlapped between wild mice and humans included genes that have been associated with traits related to host immunity and obesity in humans. Gene–bacteria associations identified in both humans and wild mice suggest some commonality to the host genetic determinants of gut microbial composition across mammals.

Quantitative phosphoproteomic analyses provide evidence for extensive phosphorylation of regulatory proteins in the rhizobia–legume symbiosis - Zaibao Zhang; Danxia Ke; Menghui Hu; Chi Zhang; Lijun Deng; Yuting Li; Jiuli Li; Hai Zhao; Lin Cheng; Lei Wang; Hongyu Yuan (Plant Molecular Biology, 2019)

Role of mTOR complex in IGF-1 induced neural differentiation of DPSCs - Dan Huang; Shuling Shen; Ming Cai; Lin Jin; Jun Lu; Ke Xu; Jinlong Zhang; Guijuan Feng; Yingzi Hu; Ke Zheng; Xingmei Feng (Journal of Molecular Histology, 2019)

Constructing a High-Density Genetic Linkage Map for Large Yellow Croaker (Larimichthys crocea) and Mapping Resistance Trait Against Ciliate Parasite Cryptocaryon irritans - Shengnan Kong; Qiaozhen Ke; Lin Chen; Zhixiong Zhou; Fei Pu; Ji Zhao; Huaqiang Bai; Wenzhu Peng; Peng Xu (Marine Biotechnology, 2019)

The role of heterogeneous environment and docetaxel gradient in the emergence of polyploid, mesenchymal and resistant prostate cancer cells - Ke-Chih Lin; Gonzalo Torga; Yusha Sun; Robert Axelrod; Kenneth J. Pienta; James C. Sturm; Robert H. Austin (Clinical & Experimental Metastasis, 2019)

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Comparative transcriptomic analysis reveals adriamycin-induced apoptosis via p53 signaling pathway in retinal pigment epithelial cells - Yu-chen Lin; Ze-ren Shen; Xiao-hui Song; Xin Liu; Ke Yao (Journal of Zhejiang University-SCIENCE B, 2018)

Dopamine receptor D2 polymorphism is associated with alleviation of obesity after 8-year follow-up: a retrospective cohort study in obese Chinese children and adolescents - Jian-fang Zhu; Lian-hui Chen; Ke Yuan; Li Liang; Chun-lin Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Electrochemical oxidation of Microcystis aeruginosa using a Ti/RuO2 anode: contributions of electrochemically generated chlorines and hydrogen peroxide - Li Lin; Xiaoyang Meng; Qingyun Li; Zhuo Huang; Linling Wang; Ke Lin; Jin Chen; John Crittenden (Environmental Science and Pollution Research, 2018)

Neuroinflammation and Neuroimmunomodulation in Alzheimer’s Disease - Yin Hong; Jun Xu; Yue Hu; Lin Li; Zhen Dong; Ting-ke Zhu; Yan-qiu Wei (Current Pharmacology Reports, 2018)

Activation of histamine H4 receptor suppresses the proliferation and invasion of esophageal squamous cell carcinoma via both metabolism and non-metabolism signaling pathways - Gong-Hao He; Jia-Qi Ding; Xin Zhang; Wen-Mang Xu; Xiao-Qian Lin; Mei-Jin Huang; Ju Feng; Ping Wang; Wen-Ke Cai (Journal of Molecular Medicine, 2018)

Influence of anthropogenic activities on polycyclic aromatic hydrocarbons in sediments from mangrove wetland at Dongzhai Harbor, China: distribution, sources, probability risk, and temporal trend - Daolai Zhang; Dongyun Yan; Xuejun Jiang; Xuehui Lin; Na Liu; Ke Liu; Ping Yin (Wetlands Ecology and Management, 2018)

Cognitive profile of ketamine-dependent patients compared with methamphetamine-dependent patients and healthy controls - Liang-Jen Wang; Chih-Ken Chen; Shih-Ku Lin; Yi-Chih Chen; Ke Xu; Ming-Chyi Huang (Psychopharmacology, 2018)

Taraxasterol suppresses the growth of human liver cancer by upregulating Hint1 expression - Tianhao Bao; Yang Ke; Yifan Wang; Weiwei Wang; Yuehua Li; Yan Wang; Xiang Kui; Qixin Zhou; Han Zhou; Cheng Zhang; Dongming Zhou; Lin Wang; et al. (Journal of Molecular Medicine, 2018)

Induction of a high-titered antibody response using HIV gag-EV71 VP1-based virus-like particles with the capacity to protect newborn mice challenged with a lethal dose of enterovirus 71 - Xi Wang; Ke Dong; Min Long; Fang Lin; Zhaowei Gao; Lin Wang; Zhe Zhang; Xi Chen; Ying Dai; Huiping Wang; Huizhong Zhang (Archives of Virology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

Screening of seaweeds in the East China Sea as potential bio-monitors of heavy metals - Yaoru Pan; Thomas Wernberg; Thibaut de Bettignies; Marianne Holmer; Ke Li; Jiaping Wu; Fang Lin; Yan Yu; Jiang Xu; Chaosheng Zhou; Zhixing Huang; Xi Xiao (Environmental Science and Pollution Research, 2018)

Effect of UGT2B7 genotypes on plasma concentration of valproic acid: a meta-analysis - Ping Wang; Xiao-Qian Lin; Wen-Ke Cai; Gui-Li Xu; Meng-Di Zhou; Mei Yang; Gong-Hao He (European Journal of Clinical Pharmacology, 2018)

Enhanced Tumor Diagnostic and Therapeutic Effect of Mesoporous Silica Nanoparticle-Mediated Pre-targeted Strategy - Gaochao Lv; Ke Li; Ling Qiu; Ying Peng; Xueyu Zhao; Xi Li; Qingzhu Liu; Shanshan Wang; Jianguo Lin (Pharmaceutical Research, 2018)

Monitoring land deformation in Changzhou city (China) with multi-band InSAR data sets from 2006 to 2012 - Yanyan Lu; Chang-Qing Ke; Xiaobing Zhou; Manman Wang; Hui Lin; Deliang Chen; Houjun Jiang (International Journal of Remote Sensing, 2018)

MicroRNA expression, target genes, and signaling pathways in infants with a ventricular septal defect - Hui Chai; Zhaoyuan Yan; Ke Huang; Yuanqing Jiang; Lin Zhang (Molecular and Cellular Biochemistry, 2018)

Using circulating tumor cells to evaluate the efficacy of irreversible electroporation for unresectasble pancreatic cancer - Mao Lin; Mohammed Alnaggar; Shu-Zhen Liang; Jian Shi; Li-Zhi Niu; Ji-Bing Chen; Ke-Cheng Xu (Immunologic Research, 2018)

Development of a set of PCR markers specific to Aegilops longissima chromosome arms and application in breeding a translocation line - Kunyang Wang; Zhishan Lin; Long Wang; Ke Wang; Qinghua Shi; Lipu Du; Xingguo Ye (Theoretical and Applied Genetics, 2018)

Increased Src Family Kinase Activity Disrupts Excitatory Synaptic Transmission and Impairs Remote Fear Memory in Forebrain Shp2-Deficient Mice - Xunyi Yan; Bin Zhang; Wen Lu; Lin Peng; Qian Yang; Wei Cao; Shen Lin; Wenyue Yu; Xiaoming Li; Yuehai Ke; Shengtian Li; Wei Yang; et al. (Molecular Neurobiology, 2017)

A Cheap and Convenient Method of Liposome Preparation Using Glass Beads as a Source of Shear Force - Aoke Wang; Aftab Ahmad; Sadeeq Ullah; Li Cheng; Lin Ke; Qipeng Yuan (AAPS PharmSciTech, 2017)

Comparative and population genomic landscape of Phellinus noxius : A hypervariable fungus causing root rot in trees - Chia‐Lin Chung; Tracy J. Lee; Mitsuteru Akiba; Hsin‐Han Lee; Tzu‐Hao Kuo; Dang Liu; Huei‐Mien Ke; Toshiro Yokoi; Marylette B. Roa; Mei‐Yeh J. Lu; Ya‐Yun Chang; Pao‐Jen Ann; et al. (Molecular Ecology, 2017)
The order Hymenochaetales of white rot fungi contain some of the most aggressive wood decayers causing tree deaths around the world. Despite their ecological importance and the impact of diseases they cause, little is known about the evolution and transmission patterns of these pathogens. Here, we sequenced and undertook comparative genomic analyses of Hymenochaetales genomes using brown root rot fungus Phellinus noxius , wood‐decomposing fungus Phellinus lamaensis, laminated root rot fungus Phellinus sulphurascens and trunk pathogen Porodaedalea pini . Many gene families of lignin‐degrading enzymes were identified from these fungi, reflecting their ability as white rot fungi. Comparing against distant fungi highlighted the expansion of 1,3‐beta‐glucan synthases in P. noxius , which may account for its fast‐growing attribute. We identified 13 linkage groups conserved within Agaricomycetes, suggesting the evolution of stable karyotypes. We determined that P. noxius has a bipolar heterothallic mating system, with unusual highly expanded ~60 kb A locus as a result of accumulating gene transposition. We investigated the population genomics of 60 P. noxius isolates across multiple islands of the Asia Pacific region. Whole‐genome sequencing showed this multinucleate species contains abundant poly‐allelic single nucleotide polymorphisms with atypical allele frequencies. Different patterns of intra‐isolate polymorphism reflect mono‐/heterokaryotic states which are both prevalent in nature. We have shown two genetically separated lineages with one spanning across many islands despite the geographical barriers. Both populations possess extraordinary genetic diversity and show contrasting evolutionary scenarios. These results provide a framework to further investigate the genetic basis underlying the fitness and virulence of white rot fungi.

Acclimation of bloom‐forming and perennial seaweeds to elevated p CO 2 conserved across levels of environmental complexity - Dong Xu; Charlotte‐Elisa Schaum; Fan Lin; Ke Sun; James R. Munroe; Xiao W. Zhang; Xiao Fan; Lin H. Teng; Yi T. Wang; Zhi M. Zhuang; Naihao Ye (Global Change Biology, 2017)
Macroalgae contribute approximately 15% of the primary productivity in coastal marine ecosystems, fix up to 27.4 Tg of carbon per year, and provide important structural components for life in coastal waters. Despite this ecological and commercial importance, direct measurements and comparisons of the short‐term responses to elevated p CO 2 in seaweeds with different life‐history strategies are scarce. Here, we cultured several seaweed species (bloom forming/nonbloom forming/perennial/annual) in the laboratory, in tanks in an indoor mesocosm facility, and in coastal mesocosms under p CO 2 levels ranging from 400 to 2,000 μatm. We find that, across all scales of the experimental setup, ephemeral species of the genus Ulva increase their photosynthesis and growth rates in response to elevated p CO 2 the most, whereas longer‐lived perennial species show a smaller increase or a decrease. These differences in short‐term growth and photosynthesis rates are likely to give bloom‐forming green seaweeds a competitive advantage in mixed communities, and our results thus suggest that coastal seaweed assemblages in eutrophic waters may undergo an initial shift toward communities dominated by bloom‐forming, short‐lived seaweeds.

Development and comparative genomic mapping of Dasypyrum villosum 6V#4S-specific PCR markers using transcriptome data - Shijin Li; Zhishan Lin; Chang Liu; Ke Wang; Lipu Du; Xingguo Ye (Theoretical and Applied Genetics, 2017)

Comparison of the effectiveness of resistance training in women with chronic computer-related neck pain: a randomized controlled study - Xiao Li; Caina Lin; Cuicui Liu; Songjian Ke; Qing Wan; Haijie Luo; Zhuxi Huang; Wenjun Xin; Chao Ma; Shaoling Wu (International Archives of Occupational and Environmental Health, 2017)

Protective effects of paeonol on inflammatory response in IL-1β-induced human fibroblast-like synoviocytes and rheumatoid arthritis progression via modulating NF-κB pathway - Ke-feng Zhai; Hong Duan; Lin Luo; Wen-gen Cao; Fang-kai Han; Ling-ling Shan; Xue-mei Fang (Inflammopharmacology, 2017)

Evolution of landslide hotspots in Taiwan - S. C. Lin; M. C. Ke; C. M. Lo (Landslides, 2017)

Clinical efficacy of percutaneous cryoablation combined with allogenic NK cell immunotherapy for advanced non-small cell lung cancer - Mao Lin; Shu-Zhen Liang; Xiao-Hua Wang; Ying-Qing Liang; Ming-Jie Zhang; Li-Zhi Niu; Ji-Bing Chen; Hai-Bo Li; Ke-Cheng Xu (Immunologic Research, 2017)

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

Diversity and antimicrobial activity of culturable fungi from fishscale bamboo (Phyllostachys heteroclada) in China - Ying-Ke Zhou; Xiao-Ye Shen; Cheng-Lin Hou (World Journal of Microbiology and Biotechnology, 2017)

A new isoquinolone alkaloid from an endophytic fungus R22 of Nerium indicum - Yang-min Ma; Ke Qiao; Yang Kong; Meng-yun Li; Lin-xin Guo; Zhi Miao; Chao Fan (Natural Product Research, 2017)

Overexpression of a chrysanthemum transcription factor gene DgNAC1 improves the salinity tolerance in chrysanthemum - Ke Wang; Ming Zhong; Yin-huan Wu; Zhen-yu Bai; Qian-yu Liang; Qing-lin Liu; Yuan-zhi Pan; Lei Zhang; Bei-bei Jiang; Yin Jia; Guang-li Liu (Plant Cell Reports, 2017)

Elevated Serum and Cerebrospinal Fluid Free Fatty Acid Levels Are Associated with Unfavorable Functional Outcome in Subjects with Acute Ischemic Stroke - Xiao-Xia Duan; Guan-Peng Zhang; Xiao-Bin Wang; Hua Yu; Jia-Li Wu; Ke-Zhi Liu; Lin Wang; Xiang Long (Molecular Neurobiology, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Heme oxygenase-1 protects spinal cord neurons from hydrogen peroxide-induced apoptosis via suppression of Cdc42/MLK3/MKK7/JNK3 signaling - Siyuan Wang; Tao Zhang; Zhen Yang; Jianhua Lin; Bin Cai; Qingfeng Ke; Wenbin Lan; Jinxing Shi; Shiqiang Wu; Wenping Lin (Apoptosis, 2017)

Optimization of Groundwater Quality Monitoring Network Using Risk Assessment and Geostatistic Approach - Shih -Ching Wu; Kai-Yuan Ke; Hsien-Tsung Lin; Yih-Chi Tan (Water Resources Management, 2017)

Effects of the wheat UDP-glucosyltransferase gene TaUGT-B2 on Agrobacterium-mediated plant transformation - Xiaohong Zhou; Ke Wang; Lipu Du; Yongwei Liu; Zhishan Lin; Xingguo Ye (Acta Physiologiae Plantarum, 2017)

ER-localized adenine nucleotide transporter ER-ANT1: an integrator of energy and stress signaling in rice - Xiangqian Zhang; Xu Zheng; Shanwen Ke; Haitao Zhu; Fang Liu; Zemin Zhang; Xinxiang Peng; Lin Guo; Ruizhen Zeng; Pei Hou; Ziqiang Liu; Suowei Wu; et al. (Plant Molecular Biology, 2016)

Species-specific effects of leaf litter on seedling emergence and growth of the invasive Flaveria bidentis and its co-occurring native species: a common garden test - Ke-li Li; Hui-yan Li; Chao-he Huangfu; Dian-lin Yang; Hong-mei Liu; Hui Wang (Plant Ecology, 2016)

Modeling daily reference ET in the karst area of northwest Guangxi (China) using gene expression programming (GEP) and artificial neural network (ANN) - Sheng Wang; Zhi-yong Fu; Hong-song Chen; Yun-peng Nie; Ke-lin Wang (Theoretical and Applied Climatology, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Impact of Heat Shock Protein A 12B Overexpression on Spinal Astrocyte Survival Against Oxygen-Glucose-Serum Deprivation/Restoration in Primary Cultured Astrocytes - Xun Xia; Yuan Ma; Li-bin Yang; Jing-ming Cheng; Tao Yang; Ke-xia Fan; Yun-ming Li; En-yu Liu; Lin Cheng; Hai-dong Huang; Jian-wen Gu; Yong-qin Kuang (Journal of Molecular Neuroscience, 2016)

Illicit drugs and their metabolites in 36 rivers that drain into the Bohai Sea and north Yellow Sea, north China - De-Gao Wang; Qiu-Da Zheng; Xiao-Ping Wang; Juan Du; Chong-Guo Tian; Zhuang Wang; Lin-Ke Ge (Environmental Science and Pollution Research, 2016)

Population geography in China since the 1980s: Forging the links between population studies and human geography - Yu Zhu; Jinhong Ding; Guixin Wang; Jianfa Shen; Liyue Lin; Wenqian Ke (Journal of Geographical Sciences, 2016)

Anisotropic Drained Deformation Behavior and Shear Strength of Natural Soft Marine Clay - Yu-Ke Wang; Lin Guo; Yu-Feng Gao; Yue Qiu; Xiu-Qing Hu; Ying Zhang (Marine Georesources & Geotechnology, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

Transcriptomic analysis of the succulent xerophyte Zygophyllum xanthoxylum in response to salt treatment and osmotic stress - Qing Ma; Ai-Ke Bao; Wei-Wei Chai; Wen-Ying Wang; Jin-Lin Zhang; Yi-Xiao Li; Suo-Min Wang (Plant and Soil, 2016)

Inhibition of Autophagy by Estradiol Promotes Locomotor Recovery after Spinal Cord Injury in Rats - Chao-Wei Lin; Bi Chen; Ke-Lun Huang; Yu-Sen Dai; Hong-Lin Teng (Neuroscience Bulletin, 2016)

Mechanical Behavior of Brittle Rock-Like Specimens with Pre-existing Fissures Under Uniaxial Loading: Experimental Studies and Particle Mechanics Approach - Ri-hong Cao; Ping Cao; Hang Lin; Cheng-zhi Pu; Ke Ou (Rock Mechanics and Rock Engineering, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

A set of GFP-based organelle marker lines combined with DsRed-based gateway vectors for subcellular localization study in rice (Oryza sativa L.) - Tsung-Meng Wu; Ke-Chun Lin; Wei-Shiang Liau; Yun-Yang Chao; Ling-Hung Yang; Szu-Yun Chen; Chung-An Lu; Chwan-Yang Hong (Plant Molecular Biology, 2016)

Rat Liver Mitochondrial Dysfunction Induced by an Organic Arsenical Compound 4-(2-Nitrobenzaliminyl) Phenyl Arsenoxide - Yuan-Hong Jiao; Qian Zhang; Ling-Li Pan; Xin-You Chen; Ke-Lin Lei; Jie Zhao; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2015)

Hygromycin B-induced cell death is partly mediated by reactive oxygen species in rice (Oryza sativa L.) - Hui-Min Oung; Ke-Chun Lin; Tsung-Meng Wu; Nulu Naga Prafulla Chandrika; Chwan-Yang Hong (Plant Molecular Biology, 2015)

Age-dependent alterations in the inflammatory response to pulmonary challenge - Helena M. Linge; Kanta Ochani; Ke Lin; Ji Young Lee; Edmund J. Miller (Immunologic Research, 2015)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Two new eudesmane-type glucopyranosides from the fruits of Daucus carota L. - Jin-Ke Xu; Xiang-Hong Lu; Wei Zhu; Bing-Xian Yang; Lin Zhang; Jing-Kui Tian (Natural Product Research, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Eco-environmental vulnerability assessment for large drinking water resource: a case study of Qiandao Lake Area, China - Qing Gu; Jun Li; Jinsong Deng; Yi Lin; Ligang Ma; Chaofan Wu; Ke Wang; Yang Hong (Frontiers of Earth Science, 2015)

The Antibacterial Effects of an Antimicrobial Peptide Human β-Defensin 3 Fused with Carbohydrate-Binding Domain on Pseudomonas aeruginosa PA14 - Ping Lin; Yong Li; Ke Dong; Qingtian Li (Current Microbiology, 2015)

Quercetin induces mitochondrial-derived apoptosis via reactive oxygen species-mediated ERK activation in HL-60 leukemia cells and xenograft - Wei-Jiunn Lee; Michael Hsiao; Junn-Liang Chang; Shun-Fa Yang; Tsui-Hwa Tseng; Chao-Wen Cheng; Jyh-Ming Chow; Ke-Hsun Lin; Yung-Wei Lin; Chung-Chi Liu; Liang-Ming Lee; Ming-Hsien Chien (Archives of Toxicology, 2015)

Effectiveness of Lactobacillus reuteri in infantile colic and colicky induced maternal depression: a prospective single blind randomized trial - Guo-Lin Mi; Lei Zhao; Dong-Dong Qiao; Wen-Qing Kang; Mao-Qin Tang; Jin-Ke Xu (Antonie van Leeuwenhoek, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Rifampicin Loaded Mannosylated Cationic Nanostructured Lipid Carriers for Alveolar Macrophage-specific Delivery - Xu Song; Qing Lin; Ling Guo; Yao Fu; Jianfeng Han; Huan Ke; Xun Sun; Tao Gong; Zhirong Zhang (Pharmaceutical Research, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Network Analysis of Functional Brain Connectivity Driven by Gamma-Band Auditory Steady-State Response in Auditory Hallucinations - Jun Ying; Dan Zhou; Ke Lin; Xiaorong Gao (Journal of Medical and Biological Engineering, 2015)

A review of seasonal climate prediction research in China - Huijun Wang; Ke Fan; Jianqi Sun; Shuanglin Li; Zhaohui Lin; Guangqing Zhou; Lijuan Chen; Xianmei Lang; Fang Li; Yali Zhu; Hong Chen; Fei Zheng (Advances in Atmospheric Sciences, 2015)

Stress signaling in response to polycyclic aromatic hydrocarbon exposure in Arabidopsis thaliana involves a nucleoside diphosphate kinase, NDPK-3 - Hong Liu; David Weisman; Ling Tang; Long Tan; Wen-ke Zhang; Zong-hua Wang; Yan-he Huang; Wen-xiong Lin; Xuan-ming Liu; Adán Colón-Carmona (Planta, 2015)

Expression analysis of genes encoding mitogen-activated protein kinases in maize provides a key link between abiotic stress signaling and plant reproduction - Wei Sun; Hao Chen; Juan Wang; Hong Wei Sun; Shu Ke Yang; Ya Lin Sang; Xing Bo Lu; Xiao Hui Xu (Functional & Integrative Genomics, 2015)

A Brassica napus PHT1 phosphate transporter, BnPht1;4, promotes phosphate uptake and affects roots architecture of transgenic Arabidopsis - Feng Ren; Cai-Zhi Zhao; Chun-Sen Liu; Ke-Lin Huang; Qian-Qian Guo; Li-Li Chang; Huan Xiong; Xue-Bao Li (Plant Molecular Biology, 2014)

USP11 regulates p53 stability by deubiquitinating p53 - Jia-ying Ke; Cong-jie Dai; Wen-lin Wu; Jin-hua Gao; Ai-juan Xia; Guang-ping Liu; Kao-sheng Lv; Chun-lin Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Evaluation of Flow Velocity in Unilateral Middle Cerebral Artery Stenosis by Transcranial Doppler - Lin Wang; Yingqi Xing; Yang Li; Ke Han; Jiafeng Chen (Cell Biochemistry and Biophysics, 2014)

Rooting characteristics of two widely distributed woody plant species growing in different karst habitats of southwest China - Yun-peng Nie; Hong-song Chen; Ke-lin Wang; Ya-li Ding (Plant Ecology, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Two Frequent Mutations Associated with the Classic Form of Propionic Acidemia in Taiwan - Yen-Hui Chiu; Yu-Ning Liu; Wei-Ling Liao; Ying-Chen Chang; Shuan-Pei Lin; Chia-Chi Hsu; Pao-Chin Chiu; Dau-Ming Niu; Chung-Hsing Wang; Yu-Yuan Ke; Yin-Hsiu Chien; Kwang-Jen Hsiao; et al. (Biochemical Genetics, 2014)

Seasonal variations in leaf δ13C values: implications for different water-use strategies among species growing on continuous dolomite outcrops in subtropical China - Yun-peng Nie; Hong-song Chen; Ke-lin Wang; Ya-li Ding (Acta Physiologiae Plantarum, 2014)

Non-alcoholic fatty liver disease and risk of in-stent restenosis after bare metal stenting in native coronary arteries - Ke-Qing Shi; Fa-Ling Wu; Wen-Yue Liu; Chen-Chen Zhao; Chang-Xi Chen; Yao-Yao Xie; Sheng-Jie Wu; Xian-Feng Lin; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

Effects of organic solvents on two retinal pigment epithelial lipofuscin fluorophores, A2E and all-trans-retinal dimer - Qiu-xia Jin; Xin-ran Dong; Jing-meng Chen; Ke Yao; Ya-lin Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Evidences for B6C3-Tg (APPswe/PSEN1dE9) Double-Transgenic Mice Between 3 and 10 Months as an Age-Related Alzheimer’s Disease Model - Zhiyong Zhong; Lin Yang; Xiansheng Wu; Wei Huang; Jiarong Yan; Shenglai Liu; Xia Sun; Ke Liu; Huangquan Lin; Shaosong Kuang; Xiaojiang Tang (Journal of Molecular Neuroscience, 2014)

G Protein-Coupled Estrogen Receptor–Protein Kinase A–ERK–CREB Signaling Pathway is Involved in the Regulation of Mouse Gubernaculum Testis Cells by Diethylstilbestrol - Xuan Zhang; Jian-hong Li; Shou-xing Duan; Qing-Jun Lin; Song Ke; Lian Ma; Tian-hua Huang; Xue-wu Jiang (Archives of Environmental Contamination and Toxicology, 2014)

Increased risk of colorectal malignant neoplasm in patients with nonalcoholic fatty liver disease: a large study - Xian-Feng Lin; Ke-Qing Shi; Jie You; Wen-Yue Liu; Ying-Wan Luo; Fa-Ling Wu; Yong-Ping Chen; Danny Ka-Ho Wong; Man-Fung Yuen; Ming-Hua Zheng (Molecular Biology Reports, 2014)

Differential expression profile of membrane proteins in Aplysia pleural–pedal ganglia under the stress of methyl parathion - Ying-Ying Chen; Lin Huang; Yong Zhang; Cai-Huan Ke; He-Qing Huang (Environmental Science and Pollution Research, 2014)

Characterization of S-(+)-linalool synthase from several provenances of Cinnamomum osmophloeum - Yan-Liang Lin; Yi-Ru Lee; Wen-Ke Huang; Shang-Tzen Chang; Fang-Hua Chu (Tree Genetics & Genomes, 2014)

Identification and mapping of a novel dominant resistance gene, TuRB07 to Turnip mosaic virus in Brassica rapa - Mina Jin; Soo-Seong Lee; Lin Ke; Jung Sun Kim; Mi-Suk Seo; Seong-Han Sohn; Beom-Seok Park; Guusje Bonnema (Theoretical and Applied Genetics, 2014)

Functional Analysis of a Novel Chrysanthemum WRKY Transcription Factor Gene Involved in Salt Tolerance - Qing-Lin Liu; Ke-Dong Xu; Yuan-Zhi Pan; Bei-Bei Jiang; Guang-Li Liu; Yin Jia; Hai-Qing Zhang (Plant Molecular Biology Reporter, 2014)

Genome-wide analysis of the bHLH transcription factor family in Chinese cabbage (Brassica rapa ssp. pekinensis) - Xiao-Ming Song; Zhi-Nan Huang; Wei-Ke Duan; Jun Ren; Tong-Kun Liu; Ying Li; Xi-Lin Hou (Molecular Genetics and Genomics, 2014)

The bionomics, habitat requirements and population threats of the butterfly Bhutanitis thaidina in Taibai Mountain - Ke Gao; Xiu-shan Li; Zhen-ying Guo; Ya-lin Zhang (Journal of Insect Conservation, 2014)

Phylogeography of Hipposideros armiger (Chiroptera: Hipposideridae) in the Oriental Region: the contribution of multiple Pleistocene glacial refugia and intrinsic factors to contemporary population genetic structure - Ai‐Qing Lin; Gabor Csorba; Lin‐Feng Li; Ting‐Lei Jiang; Guan‐Jun Lu; Vu Dinh Thong; Pipat Soisook; Ke‐Ping Sun; Jiang Feng (Journal of Biogeography, 2014)
Aim The goals of our study were to assess the population history and genetic structure of the widespread bat H ipposideros armiger , and to evaluate the effect of palaeoclimatic changes and dispersal patterns on this species. Location S outh C hina, mainland S outheast A sia and the S outh H imalayas. Methods We amplified two mitochondrial DNA (mt DNA ) regions (cyt b and D ‐loop) and seven nuclear microsatellite loci (n SSR s) from 216 individuals of H . armiger . To examine the evolutionary history of this species, we constructed maximum likelihood and Bayesian phylogenetic trees based on the two mt DNA regions. From the mt DNA and/or n SSR data, we assessed population genetic structure using analysis of molecular variance ( AMOVA ) and median‐joining network and structure analyses. We also estimated demographic history and gene flow using a B ayesian skyline plot and the program I Ma 2. Results Phylogenetic and median‐joining network analyses revealed that H . armiger comprises two distinct mt DNA clades divided into seven subclades. The results of AMOVA suggested strong population genetic structure based on mt DNA , but weak structure based on n SSR s. structure analysis identified three population clusters and also showed weak genetic structure at the nuclear level. Demographic analyses revealed two population expansion events c . 0.62 Ma and c . 0.25 Ma. The basic phylogeographical structure of H . armiger was established by 0.24 Ma. I Ma 2 analysis demonstrated that substantial gene flow has occurred between different regions since then. Additionally, non‐significant population structure and significant gene flow were detected between T aiwan and H ainan island populations and those from mainland C hina. Main conclusions Our results suggest that divergence and population expansion of H . armiger occurred in association with P leistocene climatic changes and that multiple refugia may have existed for this species. Post‐glacial male‐biased dispersal was likely to be the primary contributor to the contemporary genetic structure of H . armiger populations. Gene flow may have contributed greatly to the genetic structure of insular populations and populations from mainland C hina.

ZxSOS1 is essential for long-distance transport and spatial distribution of Na+ and K+ in the xerophyte Zygophyllum xanthoxylum - Qing Ma; Yi-Xiao Li; Hui-Jun Yuan; Jing Hu; Li Wei; Ai-Ke Bao; Jin-Lin Zhang; Suo-Min Wang (Plant and Soil, 2014)

Tentative identification of sex-specific antibodies and their application for screening bovine sperm proteins for sex-specificity - Wu-Cai Yang; Lei Sang; Yao Xiao; Hua-Lin Zhang; Ke-Qiong Tang; Li-Guo Yang (Molecular Biology Reports, 2014)

Cochlear Inner Hair Cell Ribbon Synapse is the Primary Target of Ototoxic Aminoglycoside Stimuli - Ke Liu; Xuejun Jiang; Chuang Shi; Lei Shi; Bo Yang; Lin Shi; Yice Xu; Weiyan Yang; Shiming Yang (Molecular Neurobiology, 2013)

Occurrence and distribution of veterinary antibiotics and tetracycline resistance genes in farmland soils around swine feedlots in Fujian Province, China - Xu Huang; Chaoxiang Liu; Ke Li; Feng Liu; Derun Liao; Lin Liu; Gefu Zhu; Jie Liao (Environmental Science and Pollution Research, 2013)

Overexpression of a novel chrysanthemum Cys2/His2-type zinc finger protein gene DgZFP3 confers drought tolerance in tobacco - Qing-Lin Liu; Ke-Dong Xu; Ming Zhong; Yuan-Zhi Pan; Bei-Bei Jiang; Guang-Li Liu; Yin Jia; Hai-Qing Zhang (Biotechnology Letters, 2013)

Analysis of spectral difference between the foreside and backside of leaves in yellow rust disease detection for winter wheat - Lin Yuan; Jing-Cheng Zhang; Ke Wang; Rebecca-W. Loraamm; Wen-Jiang Huang; Ji-Hua Wang; Jin-Ling Zhao (Precision Agriculture, 2013)

Structures and biogenetic analysis of lipofuscin bis-retinoids - Ya-lin Wu; Jie Li; Ke Yao (Journal of Zhejiang University-SCIENCE B, 2013)

A low-pH medium in vitro or the environment within a macrophage decreases the transcriptional levels of fimA, fimZ and lrp in Salmonella enterica serovar Typhimurium - Ke-Chuan Wang; Yuan-Hsun Hsu; Yi-Ning Huang; Ter-Hsin Chen; Jiunn-Horng Lin; Shih-Ling Hsuan; Maw-Sheng Chien; Wei-Cheng Lee; Kuang-Sheng Yeh (Journal of Biosciences, 2013)

The member of high temperature requirement family HtrA2 participates in neuronal apoptosis after intracerebral hemorrhage in adult rats - Huiqing Sun; Lei Li; Feng Zhou; Lin Zhu; Kaifu Ke; Xiang Tan; Wei Xu; Ying Rui; Heyi Zheng; Zhengming Zhou; Huiguang Yang (Journal of Molecular Histology, 2013)

Estimating Pumping Rates and Identifying Potential Recharge Zones for Groundwater Management in Multi-Aquifers System - Hsien-Tsung Lin; Kai-Yuan Ke; Yih-Chi Tan; Shih-Ching Wu; Gao Hsu; Po-Chia Chen; Shi-Ting Fang (Water Resources Management, 2013)

Pattern of benthic biomass size spectra from shallow waters in the East China Seas - Er Hua; Zhinan Zhang; Richard M. Warwick; Ke Deng; Kuixuan Lin; Ruizhao Wang; Zishan Yu (Marine Biology, 2013)

Differential distribution and activation of microglia in the brain of male C57BL/6J mice - Ting-Ting Yang; Chingju Lin; Chao-Tien Hsu; Tzu-Feng Wang; Fang-Yi Ke; Yu-Min Kuo (Brain Structure and Function, 2013)

Neural correlates of stimulus spatial frequency-dependent contrast detection - Jianjun Meng; Ruilong Liu; Ke Wang; Tianmiao Hua; Zhong-Lin Lu; Minmin Xi (Experimental Brain Research, 2013)

An abrupt backreef infilling in a Holocene reef, Paraoir, Northwestern Luzon, Philippines - Shou-Yeh Gong; Tso-Ren Wu; Fernando P. Siringan; Ke Lin; Chuan-Chou Shen (Coral Reefs, 2013)

Erratum to: Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2013)

Combinational transformation of three wheat genes encoding fructan biosynthesis enzymes confers increased fructan content and tolerance to abiotic stresses in tobacco - Xiaomin Bie; Ke Wang; Maoyun She; Lipu Du; Shuangxi Zhang; Jiarui Li; Xiang Gao; Zhishan Lin; Xingguo Ye (Plant Cell Reports, 2012)

Nkx2-1: a novel tumor biomarker of lung cancer - Li Yang; Min Lin; Wen-jing Ruan; Liang-liang Dong; En-guo Chen; Xiao-hong Wu; Ke-jing Ying (Journal of Zhejiang University-SCIENCE B, 2012)

Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Application of 3D GPR attribute technology in archaeological investigations - Wen-Ke Zhao; Gang Tian; Bang-Bing Wang; Zhan-Jie Shi; Jin-Xin Lin (Applied Geophysics, 2012)

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Association between polymorphisms of the CYP11A1 gene and polycystic ovary syndrome in Chinese women - Cheng-wei Zhang; Xin-lin Zhang; Yan-jie Xia; Yun-xia Cao; Wen-jun Wang; Pei Xu; Ye-na Che; Xiao-ke Wu; Long Yi; Qian Gao; Yong Wang (Molecular Biology Reports, 2012)

Involvement of CtBP2 in LPS-induced microglial activation - Guowei Zhang; Yaohua Yan; Lihua Kang; Qi Cao; Kaifu Ke; Xinmin Wu; Yilu Gao; Qinglei Hang; Chunmiao Li; Lin Zhu; Qin Yuan; Qiyun Wu; et al. (Journal of Molecular Histology, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Longitudinal patterns of spring-intermonsoon phytoplankton biomass, species compositions and size structure in the Bay of Bengal - Gang Li; Zhixin Ke; Qiang Lin; Guangyan Ni; Pingping Shen; Huaxue Liu; Jianqiang Yin; Kaizhi Li; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2012)

Latitudinal variability (6°S–20°N) of early summer phytoplankton species compositions and size-fractioned productivity from Java Sea to South China Sea - Gang Li; Liangmin Huang; Huaxue Liu; Zhixin Ke; Qiang Lin; Guangyan Ni; Jianqiang Yin; Kaizhi Li; Xingyu Song; Pingping Shen; Yehui Tan (Marine Biology Research, 2012)

Overexpression of a novel chrysanthemum NAC transcription factor gene enhances salt tolerance in tobacco - Qing-Lin Liu; Ke-Dong Xu; Liang-Jun Zhao; Yuan-Zhi Pan; Bei-Bei Jiang; Hai-Qing Zhang; Guang-Li Liu (Biotechnology Letters, 2011)

Effects of sand burial, soil water content and distribution pattern of seeds in sand on seed germination and seedling survival of Eremosparton songoricum (Fabaceae), a rare species inhabiting the moving sand dunes of the Gurbantunggut Desert of China - Hui-Liang Liu; Xiang Shi; Jian-Cheng Wang; Lin-Ke Yin; Zhen-Ying Huang; Dao-Yuan Zhang (Plant and Soil, 2011)

Late Mesozoic extensional tectonics of the Liaodong Peninsula massif: Response of crust to continental lithosphere destruction of the North China Craton - Wei Lin; QingChen Wang; Jun Wang; Fei Wang; Yang Chu; Ke Chen (Science China Earth Sciences, 2011)

HLA polymorphism of the Zhuang population reflects the common HLA characteristics among Zhuang-Dong language-speaking populations - Li Shi; Xiao-qin Huang; Lei Shi; Yu-fen Tao; Yu-feng Yao; Liang Yu; Ke-qin Lin; Wen Yi; Hao Sun; Katsushi Tokunaga; Jia-you Chu (Journal of Zhejiang University-SCIENCE B, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Evaluation on the two filling functions for the recovery of forest information in mountainous shadows on Landsat ETM + Image - Amir reza Shahtahmassebi; Ke Wang; Zhangquan Shen; Jinsong Deng; Wenjuan Zhu; Ning Han; Fengfang Lin; Nathan Moore (Journal of Mountain Science, 2011)

Gametogenic cycle and biochemical composition of the clam Mactra chinensis (Mollusca: Bivalvia): Implications for aquaculture and wild stock management - Qi Li; Lin Yang; Qiaozhen Ke; Lingfeng Kong (Marine Biology Research, 2011)

Seasonal water use patterns of woody species growing on the continuous dolostone outcrops and nearby thin soils in subtropical China - Yun-peng Nie; Hong-song Chen; Ke-lin Wang; Wei Tan; Peng-yan Deng; Jing Yang (Plant and Soil, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Chemical-protein interactome and its application in off-target identification - Lun Yang; Ke-Jian Wang; Li-Shan Wang; Anil G. Jegga; Sheng-Ying Qin; Guang He; Jian Chen; Yue Xiao; Lin He (Interdisciplinary Sciences: Computational Life Sciences, 2011)

Pseudonocardia sichuanensis sp. nov., a novel endophytic actinomycete isolated from the root of Jatropha curcas L. - Sheng Qin; Ke Xing; Shi-Min Fei; Qiang Lin; Xiu-Min Chen; Cheng-Liang Cao; Yong Sun; Yun Wang; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2011)

Algal Growth Control Within Natural Water Purification Systems: Macrophyte Light Shading Effects - T. Y. Yeh; T. Y. Ke; Y. L. Lin (Water, Air, & Soil Pollution, 2011)

Adenosine postconditioning protects against myocardial ischemia–reperfusion injury though modulate production of TNF-α and prevents activation of transcription factor NF-kappaB - Jian-Juan Ke; Feng-Xu Yu; Yan Rao; Yan-Lin Wang (Molecular Biology Reports, 2011)

A multiple-dose pharmacokinetics of polyethylene glycol recombinant human interleukin-6 (PEG-rhIL-6) in rats - Xue-ling He; Hai-lin Yin; Jiang Wu; Ke Zhang; Yan Liu; Tao Yuan; Hai-lin Rao; Liang Li; Guang Yang; Xue-mei Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Factors Associated with Determination of Root 22Na+ Influx in the Salt Accumulation Halophyte Suaeda maritima - Jin-Lin Zhang; Anne M. Wetson; Suo-Min Wang; Ali R. Gurmani; Ai-Ke Bao; Chun-Mei Wang (Biological Trace Element Research, 2011)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Activation of PPARδ promotes mitochondrial energy metabolism and decreases basal insulin secretion in palmitate-treated β-cells - Li Jiang; Jun Wan; Lin-qiu Ke; Qing-guo Lü; Nan-wei Tong (Molecular and Cellular Biochemistry, 2010)

A meta-analysis of three polymorphisms in the endothelial nitric oxide synthase gene (NOS3) and their effect on the risk of diabetic nephropathy - Zhen Zeng; Lina Li; Zhao Zhang; Yang Li; Zhiyun Wei; Ke Huang; Lin He; Yongyong Shi (Human Genetics, 2010)

Isolation and functional characterization of DgZFP: a gene encoding a Cys2/His2-type zinc finger protein in chrysanthemum - Qing-Lin Liu; Ke-Dong Xu; Nan Ma; Li Zeng; Liang-Jun Zhao (Molecular Biology Reports, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Application and development of a decision-support system for assessing water shortage and allocation with climate change - Tzu-Ming Liu; C. P. Tung; K. Y. Ke; L. H. Chuang; C. Y. Lin (Paddy and Water Environment, 2009)

Detection of survivin-expressing circulating cancer cells in the peripheral blood of patients with esophageal squamous cell carcinoma and its clinical significance - Mei Cao; Shang-Mian Yie; Sheng-Min Wu; Shu Chen; Be Lou; Xu He; Shang-Rong Ye; Ke Xie; Lin Rao; En Gao; Nai-Yao Ye (Clinical & Experimental Metastasis, 2009)

Provenance and thermal history of the Bayan Har Group in the western‐central Songpan–Ganzi–Bayan Har terrane: Implications for tectonic evolution of the northern Tibetan Plateau - Guo‐Can Wang; Robert P. Wintsch; John I. Garver; Mary Roden‐Tice; She‐Fa Chen; Ke‐Xin Zhang; Qi‐Xiang Lin; Yun‐Hai Zhu; Shu‐Yuan Xiang; De‐Wei Li (Island Arc, 2009)
Triassic turbidites dominate the Songpan–Ganzi–Bayan Har (SGBH) terrane of the northern Tibetan Plateau. U‐Pb dating on single detrital zircon grains from the Triassic Bayan Har Group turbidites yield peaks at 400–500 m.y., 900–1000 m.y., 1800–1900 m.y., and 2400–2500 m.y., These results are consistent with recently published U‐Pb zircon ages of pre‐Triassic bedrock in the East Kunlun, Altyn, Qaidam, Qilian and Alaxa areas to the north, suggesting that provenance of the Bayan Har Group may include these rocks. The similarities in the compositions of the lithic arkosic sandstones of the Bayan Har Group with the sandstones of the Lower‐Middle Triassic formations in the East Kunlun terrane to the north also suggests a common northern provenance for both. A well exposed angular unconformity between the Carboniferous–Middle Permian mélange sequences and the overlying Upper Permian or Triassic strata indicates that regional deformation occurred between the Middle and Late Permian. This deformation may have been the result of a soft collision between the Qiangtang terrane and the North China Plate and the closure of the Paleo‐Tethyan oceanic basin. The Bayan Har Group turbidites were then deposited in a re‐opened marine basin on a shelf environment. Fission‐track dating of detrital zircons from the Bayan Har Group sandstones revealed pre‐ and post‐depositional age components, suggesting that the temperatures did not reach the temperatures necessary to anneal retentive zircon fission tracks (250–300°C). A 282–292 m.y. peak age defined by low U concentration, retentive zircons likely reflects a northern granitic source. Euhedral zircons from two lithic arkoses with abundant volcanic fragments in the southern area yielded a ∼237 m.y. zircon fission track (ZFT) peak age, likely recording the maximum age of deposition. A dominant post‐depositional 170–185 m.y. ZFT peak age suggests peak temperatures were reached in the Early Jurassic. Some samples appear to record a younger thermal event at ∼140 m.y., a short lived event that apparently affected only the least retentive zircons.

Variability of total and available copper concentrations in relation to land use and soil properties in Yangtze River Delta of China - Xiuying Zhang; Fenfang Lin; Yugen Jiang; Ke Wang; X. L. Feng (Environmental Monitoring and Assessment, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Overexpression of Thellungiella halophila H+-PPase (TsVP) in cotton enhances drought stress resistance of plants - Su-Lian Lv; Li-Jun Lian; Pei-Lin Tao; Zhao-Xia Li; Ke-Wei Zhang; Ju-Ren Zhang (Planta, 2009)

Expression and purification of Zantedeschia aethiopica agglutinin in Escherichia coli - Ling Lin; Xue-Fen Liu; Ling-Chuan Hu; Yin Zhou; Xiao-Fen Sun; Ke-Xuan Tang (Molecular Biology Reports, 2009)

Proteome alteration of U251 human astrocytoma cell after inhibiting retinoic acid synthesis - Ming Zhang; Chunling Wan; Baohu Ji; Zhao Zhang; Hui Zhu; Nan Tian; Yujuan La; Ke Huang; Lei Jiang; Guang He; Linhan Gao; Xinzhi Zhao; et al. (Molecular and Cellular Biochemistry, 2009)

Arseniasis prevalence and mortality in a multiethnic, endemic township in Guizhou, China - Ji-gang Chen; Guo-fang Lin; Yu-gang Chen; Chao-gang Jia; Yun-shu Zhou; Hong Meng; Wei-chao Guo; Klaus Golka; Ke Jian Liu; Jian-hua Shen (International Archives of Occupational and Environmental Health, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

The distribution of HBV genotypes and clinical significance in familial clustering in an infected population with unfavorable prognosis - Jinfeng Liu; Yongqin Li; Tianyan Chen; Yuan Yang; Ke Wang; Yingli He; Qian Yang; Feng Ye; Yan Jin; Ting Qiu; Shumei Lin; Min Liu; et al. (Archives of Virology, 2008)

Estimation of genetic variances in flood tolerance of poplar and selection of resistant F1 generations - Ke-Bing Du; Bao-Xian Shen; Lin Xu; Bing-Kun Tu (Agroforestry Systems, 2008)

shRNA-targeted Cyclooxygenase (COX)-2 inhibits proliferation, reduces invasion and enhances chemosensitivity in laryngeal carcinoma cells - Rui Wang; Xi Wang; Fang Lin; Ping Gao; Ke Dong; Hui-Zhong Zhang (Molecular and Cellular Biochemistry, 2008)

Bisbenzopyrans and alkaloids from the roots of Stemona cochinchinensis - Pham-Huu Dien; Li-Gin Lin; Chun-Ping Tang; Chang-Qiang Ke; Yang Ye (Natural Product Research, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Positive correlation between soil bacterial metabolic and plant species diversity and bacterial and fungal diversity in a vegetation succession on Karst - Xun-Yang He; Ke-Lin Wang; Wei Zhang; Zhi-Hui Chen; Yong-Guan Zhu; Hong-Song Chen (Plant and Soil, 2008)

Bioenergetic Investigation of the Effects of La(III) and Ca(II) on the Metabolic Activity of Tetrahymena thermophila BF5 - Jie Dai; Chuan-Ling Li; Ye-Zhong Zhang; Qi Xiao; Ke-Lin Lei; Yi Liu (Biological Trace Element Research, 2008)

Positive association between OLIG2 and schizophrenia in the Chinese Han population - Ke Huang; Wei Tang; Ruqi Tang; Zhao Xu; Zhangdong He; Zhiqiang Li; Yifeng Xu; Xingwang Li; Guang He; Guoying Feng; Lin He; YongYong Shi (Human Genetics, 2008)

Diversity and evolutionary relationship of nucleotide binding site-encoding disease-resistance gene analogues in sweet potato (Ipomoea batatas Lam.) - Guanshui Chen; Daren Pan; Yifei Zhou; Sheng Lin; Xiangde Ke (Journal of Biosciences, 2007)

Purification and characterization of a β-1,3-glucanase from the novel mycoparasite Periconia byssoides - Chao Lin; Jinkui Yang; Hui Sun; Xiaowei Huang; Ruibin Wang; Ke-Qin Zhang (Biotechnology Letters, 2007)

Purification and Properties of a β-1,3-glucanase from Chaetomium sp. that is Involved in Mycoparasitism - Hui Sun; Jinkui Yang; Chao Lin; Xiaowei Huang; Ruihuan Xing; Ke-Qin Zhang (Biotechnology Letters, 2006)

A Season-dependent Variation of Genotoxicity of Surface Water Samples from Taihu Lake, Yangzte Delta - Jian-Yong Wu; Lei Shen; Guang Gao; Guo-Fang Lin; Xin Ke; Jian-Hua Shen (Environmental Monitoring and Assessment, 2004)

Expression and production of bioactive human interleukin-18 in transgenic tobacco plants - Bin Zhang; Ying-Hua Yang; Yong-Ming Lin; Qing Rao; Guo-Guang Zheng; Ke-Fu Wu (Biotechnology Letters, 2003)

Novel Cu(II)-quinoline carboxamide complexes: Structural characterization, cytotoxicity and reactivity towards 5′-GMP - Junyong Zhang; Xiaokang Ke; Chao Tu; Jun Lin; Jian Ding; Liping Lin; Hoong-Kun Fun; Xiaozeng You; Zijian Guo (BioMetals, 2003)

Conversion of an obligate autotrophic bacteria to heterotrophic growth: expression of a heterogeneous phosphofructokinase gene in the chemolithotroph Acidithiobacillus thiooxidans - Ke Li Tian; Jian Qun Lin; Xiang Mei Liu; Ying Liu; Chang Kai Zhang; Wang Ming Yan (Biotechnology Letters, 2003)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

TGFβ1 stimulates the secretion of matrix metalloproteinase 2 (MMP2) and the invasive behavior in human ovarian cancer cells, which is suppressed by MMP inhibitor BB3103 - Sui-Wen Lin; Ming-Ting Lee; Ferng-Chun Ke; Ping-Ping H. Lee; Chang-Jen Huang; Margot M. Ip; Lily Chen; Jiuan-Jiuan Hwang (Clinical & Experimental Metastasis, 2000)